Method for manufacturing secondary battery

JP2025002942APending Publication Date: 2025-01-09SEMICON ENERGY LAB CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023103348
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-23
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0024】 予め、容器の内壁に添加元素を含む被膜を形成、または容器の内壁に添加元素をドープさせ、容器内の材料を蓋で密閉した状態として加熱処理することで、不純物を混入させることなく、大量の正極活物質の材料を一度に得る製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025002942000001_ABST
    Figure 2025002942000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a positive electrode active material at low production cost, and a secondary battery with high safety.SOLUTION: It is preferable to coat the inner wall of a container with a compound containing an additive element in advance, place a positive electrode active material in the container, and heat the container with a lid on to incorporate the additive element into the surface layer. The additive element is one or more selected from magnesium, fluorine, aluminum, titanium, and nickel.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material or a method for producing the same, a manufacturing apparatus for a positive electrode active material, and a secondary battery or a method for producing the same. [Background technology]

[0002] In recent years, various types of power storage devices have been actively developed, such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries, all-solid-state batteries, etc. In particular, the demand for high-output, high-capacity lithium-ion secondary batteries has rapidly expanded in line with the development of the semiconductor industry, and they have become indispensable in the modern information society as a rechargeable energy source.

[0003] With the increase in demand, there is a demand for improving the productivity of lithium-ion batteries and their materials. As part of this, development of an efficient method for producing a positive electrode active material, which is one of the materials for lithium-ion batteries, is underway. For example, Patent Document 1 discloses a method for producing a positive electrode active material using a rotary kiln capable of continuous processing.

[0004] Furthermore, Patent Documents 2 and 3 disclose a method for producing a positive electrode active material with good characteristics by performing annealing in an atmosphere containing a fluoride. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. WO2021 / 116819 Brochure [Patent Document 2] International Publication No. WO2020 / 201891 Brochure [Patent Document 3] International Publication No. WO2020 / 201892 Brochure Summary of the Invention [Problem to be solved by the invention]

[0006] Positive electrode active materials are expensive materials in lithium-ion secondary batteries, and the effect of improving productivity is high. At the same time, there is a strong demand for high performance (for example, high capacity, improved cycle characteristics, improved reliability or safety).

[0007] In view of the above, an object of one embodiment of the present invention is to provide a method for manufacturing a positive electrode active material at low production costs.Another object is to provide a method for manufacturing a positive electrode active material whose crystal structure is not easily destroyed even after repeated charging and discharging.Another object is to provide a method for manufacturing a positive electrode active material with excellent charge and discharge cycle characteristics.Another object is to provide a method for manufacturing a positive electrode active material with large charge and discharge capacity.Another object is to provide a secondary battery with high reliability or safety.

[0008] Another object is to provide a manufacturing apparatus capable of manufacturing a positive electrode active material at low production cost.

[0009] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]

[0010] The surface layer of the positive electrode active material is the region where lithium ions are first released during charging, and is the region where the lithium concentration is likely to be lower than in the interior. In addition, the atoms on the surface of the particles of the positive electrode active material in the surface layer can be said to be in a state where some of the bonds are broken. Therefore, the surface layer is easily unstable and can be said to be the region where deterioration of the crystal structure begins easily.

[0011] In order to make the surface layer stable in composition and crystal structure, the surface layer preferably has an additive element (e.g., magnesium or fluorine), and more preferably has a plurality of additive elements. The surface layer preferably has a higher concentration of one or more selected from the additive elements than the interior. The positive electrode active material preferably has a concentration gradient of one or more selected from the additive elements. The positive electrode active material more preferably has a different distribution depending on the additive element. For example, it is more preferable that the depth from the surface of the concentration peak differs depending on the additive element. The concentration peak here refers to the maximum concentration value in the surface layer or within 50 nm from the surface.

[0012] In order to efficiently incorporate the additive element into the surface layer portion, it is preferable to coat the inner wall of a container with a compound containing the additive element in advance, place the positive electrode active material in the container, and heat the container with the lid on to incorporate the additive element into the surface layer portion. The additive element is one or more selected from magnesium, fluorine, aluminum, titanium, and nickel.

[0013] The production method disclosed in this specification is a method for producing a secondary battery in which a region or film containing an additive element at a high concentration is formed on the inner surface of a container made of a heat-resistant material, a plurality of active material particles are stored in the container, a lid made of a heat-resistant material is closed on the container, the container is heated with the lid closed to add the additive element to surface layers of the active material particles, the lid is opened after the heat treatment, and the positive electrode active material is recovered from the container, and the positive electrode active material is used as a positive electrode.

[0014] In the above-mentioned configuration, a closed space is formed with a lid closed on the container, and the closed space is filled with a gas containing an additive element by a heat treatment, so that the concentration of the additive element is higher than that of the space outside the container. Also, in the above-mentioned configuration, the atmosphere during the heat treatment of the container with the lid closed is an oxygen atmosphere.

[0015] Positive electrode active materials or raw materials to be stored in the container include LCO, NCM, LFP, etc., and a representative example is lithium composite oxide LiMO 2(M is two or more metals including Co (e.g., Ni, Mn, Mg, Ti, Fe, Al, or Zn), and there is no particular limitation on the substitution position of the metal.) x Chief of Staff 2 and NCM is LiNi X Co Y Mn Z O 2 It is expressed as (X+Y+Z=1). LFP is LiFePO 4 It is expressed as:

[0016] The container is a firing container, and various containers such as a crucible, a sheath (also called a tray or sagger), a capsule, a pod, or a boat shape can be used, but a container with a lid is used. When the container is covered and heated, outward diffusion is suppressed, and the added elements gather on the surface layer of the positive electrode active material, allowing the surface layer to form a good barrier film.

[0017] The container is made of a material that is resistant to cracking even when subjected to thermal shock, specifically ceramics, such as alumina, zirconia, silicon nitride, silicon carbide, mullite, and mullite-cordierite. When ceramics are used as the container material, the concentration of the additive element on the container inner wall may be affected by the difference in density or surface unevenness. When a compound containing an additive element or lithium is heated in contact with a container made of a ceramic material having a surface unevenness, it may diffuse into small recesses in the container. Therefore, it is not limited to forming a coating on the inner wall of the container, and the additive element may be contained in the surface unevenness of the inner wall of the container, in which case it can be said that the inner wall of the container is doped with the additive element.

[0018] In addition, the material of the container itself may contain a compound containing an additive element. For example, mullite (3Al 2 O 3 2SiO 2 ), or cordierite (5SiO 2 2Al 2 O 3The container may be made of mullite or cordierite. The above-mentioned composition of mullite or cordierite is merely an example of ideal values ​​constituting the crystal structure, and the actual composition is not limited to the above-mentioned values, nor is it limited to a uniform composition, and may have a partially different composition.

[0019] By forming a coating containing an additive element on the inner wall of a container in advance, or by doping the inner wall of a container with an additive element, a positive electrode active material or its raw material can be stored in the container and heated to efficiently contain a high concentration of the additive element in the surface layer, thereby providing a positive electrode active material whose surface layer functions as an excellent barrier film. Alternatively, the surface layer, which is the outer periphery of the positive electrode active material, reinforces the positive electrode active material. The reinforcement here means suppressing structural changes in the surface layer and inside of the positive electrode active material, such as the release of oxygen and / or the shift of the layered structure consisting of an octahedron of transition metal M and oxygen. And / or suppressing the oxidative decomposition of the electrolyte on the surface of the positive electrode active material.

[0020] Therefore, the surface layer portion preferably has a different crystal structure from the inside. In addition, the surface layer portion preferably has a composition and crystal structure that are more stable at room temperature (25° C.) than the inside. For example, at least a part of the surface layer portion of the positive electrode active material of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface layer portion preferably has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface layer portion preferably has characteristics of both a layered rock salt type crystal structure and a rock salt type crystal structure.

[0021] The surface layer is the region where lithium ions are first released during charging, and is therefore more likely to have a lower lithium concentration than the interior. In addition, the atoms on the surface of the particles of the positive electrode active material in the surface layer can be said to have some of their bonds broken. This makes the surface layer more likely to become unstable, and the region where degradation of the crystal structure is likely to begin. For example, if the crystal structure of the layered structure consisting of transition metal M and oxygen octahedra in the surface layer becomes distorted, this effect will cascade down to the interior, causing the layered crystal structure to become distorted internally as well, leading to degradation of the crystal structure of the entire positive electrode active material. On the other hand, if the surface layer can be made sufficiently stable, Lix MO 2 Even when the value of x is small, for example 0.24 or less, the layered structure of the internal transition metal M and oxygen octahedra can be made less likely to break. Furthermore, the shifting of the layers of the internal transition metal M and oxygen octahedra can be suppressed.

[0022] In addition, it is preferable that the density of defects, including dislocations, inside the positive electrode active material is low. In addition, it is preferable that the positive electrode active material has a large crystallite size measured by XRD. In other words, it is preferable that the inside is highly crystalline. In addition, it is preferable that the surface of the positive electrode active material is smooth. These characteristics are important factors that support the reliability of the positive electrode active material when used in a secondary battery. If the reliability of the positive electrode active material is high, the upper limit of the charging voltage of the secondary battery can be increased, and a secondary battery with a high charge / discharge capacity can be obtained.

[0023] Internal dislocations can be observed, for example, by TEM. If the density of defects, including dislocations, is sufficiently low, they may not be observed in a specific 1 μm square of the observation sample. Note that dislocations are a type of crystal defect and are different from vacancy defects. Effect of the Invention

[0024] By forming a coating containing an additive element on the inner wall of a container in advance or doping the inner wall of the container with an additive element, and then heat treating the material in the container while it is sealed with a lid, a manufacturing method can be provided that can obtain a large amount of positive electrode active material at once without introducing impurities.

[0025] According to one embodiment of the present invention, a method for manufacturing a positive electrode active material with low production costs can be provided. A method for manufacturing a positive electrode active material with fewer steps and a short lead time can be provided. Alternatively, a method for manufacturing a positive electrode active material whose crystal structure is not easily destroyed even after repeated charging and discharging can be provided. Alternatively, a method for manufacturing a positive electrode active material with excellent charge-discharge cycle characteristics can be provided. Alternatively, a method for manufacturing a positive electrode active material with large charge-discharge capacity can be provided. Alternatively, a secondary battery with high reliability or safety can be provided.

[0026] Alternatively, it is possible to provide a manufacturing apparatus capable of manufacturing a positive electrode active material at low production costs.

[0027] According to one embodiment of the present invention, a positive electrode active material, a composite oxide, a power storage device, or a manufacturing method thereof can be provided. [Brief description of the drawings]

[0028] [Figure 1] 1A and 1B are a flow chart illustrating an example of a manufacturing method according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a flowchart illustrating an example of a manufacturing method according to one embodiment of the present invention. [Diagram 3] FIG. 3(A) is a schematic cross-sectional view of a heating furnace, FIG. 3(B) is a top view of a lid, and FIG. 3(C) is a schematic cross-sectional view of the container and the lid. [Figure 4] FIG. 4(A) is a schematic cross-sectional view of a manufacturing apparatus showing one embodiment of the present invention, FIG. 4(B) is an external view of a container showing one embodiment of the present invention, FIG. 4(C) is a view showing the positional relationship between the furnace tube and the container as viewed from the longitudinal direction of the furnace tube, FIG. 4(D) is a schematic cross-sectional view of the furnace tube, and FIG. 4(E) is a schematic cross-sectional view of the container and lid showing one embodiment of the present invention. [Diagram 5] FIG. 5(A) is a schematic cross-sectional view of a production apparatus showing one embodiment of the present invention, and FIG. 5(B) is a schematic cross-sectional view taken along the dashed line ab. [Figure 6] FIG. 6(A) is a cross-sectional view of the positive electrode active material, and FIG. 6(B1) and FIG. 6(B2) are a part of the cross-sectional view of the positive electrode active material. [Figure 7] Figure 7 is an example of a TEM image in which the crystal orientations are roughly consistent. [Figure 8] Figure 8(A) is an example of a STEM image in which the crystal orientations are roughly consistent, Figure 8(B) is an FFT pattern of the region of the rock-salt-type crystal RS, and Figure 8(C) is an FFT pattern of the region of the layered rock-salt-type crystal LRS. [Figure 9] FIG. 9 is a diagram illustrating the crystal structure of the positive electrode active material. [Figure 10] FIG. 10 is a diagram illustrating the crystal structure of a conventional positive electrode active material. [Figure 11] Fig. 11(A1) and Fig. 11(A2) are partial cross-sectional views of the positive electrode active material. Fig. 11(B1) to Fig. 11(C) show the results of calculations of the crystal plane and magnesium distribution of lithium cobalt oxide. [Figure 12] 12(A) and 12(B) are cross-sectional views of the positive electrode active material, and FIG. 12(C1) and FIG. 12(C2) are partial cross-sectional views of the positive electrode active material. [Figure 13] FIG. 13 shows an XRD pattern calculated from the crystal structure. [Figure 14] FIG. 14 shows an XRD pattern calculated from the crystal structure. [Figure 15] 15(A) and 15(B) show XRD patterns calculated from the crystal structure. [Figure 16] 16(A) and 16(B) are XPS spectra of the positive electrode active material. [Figure 17] FIG. 17 is a cross-sectional view of the positive electrode active material. [Figure 18] FIG. 18 is a cross-sectional view of the positive electrode active material. [Figure 19] FIG. 19 is a diagram illustrating a method for producing a positive electrode active material. [Figure 20] 20(A) and 20(B) are diagrams illustrating a method for producing a positive electrode active material. [Figure 21] 21A to 21D illustrate a positive electrode of one embodiment of the present invention. [Figure 22] 22A and 22B are diagrams illustrating a lithium-ion battery of one embodiment of the present invention. [Figure 23] 23A to 23C illustrate a lithium-ion battery of one embodiment of the present invention. [Figure 24] 24A to 24D illustrate a lithium-ion battery and a power storage system of one embodiment of the present invention. [Diagram 25]25(A) to 25(C) illustrate a lithium-ion battery of one embodiment of the present invention. [Figure 26] 26(A) to 26(C) illustrate a lithium-ion battery of one embodiment of the present invention. [Figure 27] 27(A) to 27(C) illustrate an electric vehicle of one embodiment of the present invention. [Figure 28] 28(A) to 28(D) are diagrams illustrating a transportation vehicle according to one embodiment of the present invention. [Figure 29] 29(A) to 29(C) are diagrams illustrating a two-wheeled vehicle or the like according to one embodiment of the present invention. [Diagram 30] 30A to 30D illustrate electronic devices or the like according to one embodiment of the present invention. [Diagram 31] 31(A) to 31(D) are diagrams showing an example of space equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the form and details of the present invention can be modified in various ways. Furthermore, the present invention is not to be interpreted as being limited to the description of the embodiments shown below.

[0030] (Embodiment 1) <<Method 1 for preparing positive electrode active material>> A manufacturing method 1 of a positive electrode active material 100 will be described with reference to FIGS.

[0031] <Step S11> In step S11 shown in FIG. 1(A), a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials, that is, lithium and transition metal materials, respectively.

[0032] As the lithium source, it is preferable to use a compound containing lithium, such as lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. It is preferable that the lithium source has high purity, and for example, it is preferable to use a material with a purity of 99.99% or more.

[0033] As the cobalt source, it is preferable to use a compound containing cobalt, such as cobalt oxide, cobalt hydroxide, or cobalt carbonate.

[0034] The cobalt source is preferably of high purity, for example, a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and even more preferably 5N (99.999%) or more may be used. By using a material of high purity, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is increased and / or the reliability of the secondary battery is improved.

[0035] In addition, the cobalt source preferably has high crystallinity, for example, single crystal grains. The crystallinity of the cobalt source can be evaluated using a TEM (transmission electron microscope) image, a STEM (scanning transmission electron microscope) image, a HAADF-STEM (high-angle annular dark-field scanning transmission electron microscope) image, an ABF-STEM (annular bright-field scanning transmission electron microscope) image, or by X-ray diffraction (XRD), electron beam diffraction, neutron beam diffraction, or the like. The above-mentioned methods for evaluating crystallinity can be applied not only to the evaluation of cobalt sources, but also to the evaluation of other crystallinity.

[0036] <Step S12> Next, in step S12 shown in FIG. 1(A), the lithium source and the cobalt source are pulverized and mixed to prepare a mixed material. The pulverization and mixing can be performed in a dry or wet manner. The wet method is preferable because it can be crushed into smaller pieces. When performing the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that does not easily react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. It is preferable to mix the lithium source and the cobalt source with dehydrated acetone with a purity of 99.5% or more, in which the moisture content is suppressed to 10 ppm or less, and then pulverize and mix them. By using dehydrated acetone with the above-mentioned purity, it is possible to reduce impurities that may be mixed in.

[0037] A ball mill, a bead mill, or the like can be used as a means for pulverization and mixing. When using a ball mill, aluminum oxide balls or zirconium oxide balls are preferably used as pulverization media. Zirconium oxide balls are preferred because they emit less impurities. When using a ball mill, a bead mill, or the like, the peripheral speed is preferably set to 100 mm / s or more and 2000 mm / s or less in order to suppress contamination from the media. In this embodiment, the peripheral speed is set to 838 mm / s (rotation speed 400 rpm, ball mill diameter 40 mm).

[0038] <Step S13> Next, in step S13 shown in FIG. 1(A), the mixed material is heated. The heating is preferably performed at 800° C. to 1100° C., more preferably at 900° C. to 1000° C., and even more preferably at about 950° C. If the temperature is too low, the decomposition and melting of the lithium source and the cobalt source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to lithium transpiration from the lithium source and / or cobalt being excessively reduced. For example, cobalt may change from trivalent to divalent, inducing oxygen defects.

[0039] If the heating time is too short, lithium cobalt oxide will not be synthesized, but if it is too long, productivity will decrease. For example, the heating time is preferably 1 hour or more and 100 hours or less, and more preferably 2 hours or more and 20 hours or less.

[0040] The rate of temperature rise depends on the heating temperature reached, but it is recommended to set it to between 80°C / h and 250°C / h. For example, if heating at 1000°C for 10 hours, the rate of temperature rise should be 200°C / h.

[0041] Heating is preferably performed in an atmosphere with little water, such as dry air, for example, an atmosphere with a dew point of -50°C or less, more preferably an atmosphere with a dew point of -80°C or less. In this embodiment, heating is performed in an atmosphere with a dew point of -93°C. In order to suppress impurities that may be mixed into the material, the CH 4 , CO, CO 2 , and H 2 It is advisable to keep the impurity concentrations of the above items below 5 ppb (parts per billion).

[0042] The heating atmosphere is preferably an atmosphere containing oxygen. For example, there is a method of continuously introducing dry air into the reaction chamber. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the reaction chamber and having oxygen flow through the reaction chamber is called flow.

[0043] When the heating atmosphere is an atmosphere containing oxygen, a method that does not allow oxygen to flow may be used. For example, the reaction chamber may be depressurized and then filled with oxygen (or purged) to prevent the oxygen from entering or leaving the reaction chamber. For example, the reaction chamber may be depressurized to -970 hPa and then filled with oxygen to 50 hPa.

[0044] After heating, the material may be naturally cooled, but it is preferable that the time required for the material to cool from the specified temperature to room temperature is within a range of 10 to 50 hours. However, cooling to room temperature is not always necessary, and it is sufficient to cool the material to a temperature that is acceptable for the next step.

[0045] The heating in this step may be performed using a rotary kiln or a roller hearth kiln. Heating using a rotary kiln may be performed while stirring in either a continuous or batch type.

[0046] <Step S14> Through the above steps, lithium cobalt oxide (LiCoO 2 ) can be synthesized.

[0047] Although the composite oxide is produced by the solid phase method in steps S11 to S14, the composite oxide may be produced by a coprecipitation method or a hydrothermal method.

[0048] <Step S15> Next, the lithium cobalt oxide is heated in step S15 shown in Fig. 1(A). Since this is the first heating of the lithium cobalt oxide, the heating in step S15 is sometimes called initial heating. Or, since this heating is performed before step S33 described below, it is sometimes called preheating or pretreatment.

[0049] As described above, the initial heating causes lithium to be desorbed from a portion of the surface layer of the lithium cobalt oxide. It is also expected to have the effect of increasing the crystallinity inside. In addition, impurities may be mixed into the lithium source and / or cobalt source prepared in step S11, etc. The initial heating makes it possible to reduce the impurities in the lithium cobalt oxide completed in step S14.

[0050] Furthermore, the initial heating has the effect of smoothing the surface of the lithium cobalt oxide. A smooth surface means that there are few irregularities, the composite oxide is generally rounded, and the corners are rounded. Furthermore, a surface with little foreign matter adhering to it is called smooth. Foreign matter is thought to be the cause of the irregularities, so it is preferable that it does not adhere to the surface.

[0051] For this initial heating, it is not necessary to prepare a lithium compound source, or a source of an additive element, or a material that functions as a flux.

[0052] If the heating time of this step is too short, sufficient effect is not obtained, but if it is too long, productivity decreases. For example, the heating conditions can be selected from those described in step S13. In addition to the heating conditions, the heating temperature of this step should be lower than the temperature of step S13 in order to maintain the crystal structure of the complex oxide. Furthermore, the heating time of this step should be shorter than the time of step S13 in order to maintain the crystal structure of the complex oxide. For example, heating should be performed at a temperature of 700°C to 1000°C for 2 hours to 20 hours.

[0053] The effect of enhancing the internal crystallinity is, for example, the effect of mitigating distortion, displacement, and the like resulting from a shrinkage difference or the like possessed by the lithium cobalt oxide produced in step S13.

[0054] The heating in step S13 may cause a temperature difference between the surface and the inside of the lithium cobalt oxide. The temperature difference may induce a shrinkage difference. It is also considered that the temperature difference causes the shrinkage difference because the fluidity of the surface and the inside is different. The energy related to the shrinkage difference gives the lithium cobalt oxide a difference in internal stress. The internal stress difference is also called strain, and the energy is sometimes called strain energy. The internal stress is removed by the initial heating in step S15, or in other words, the strain energy is considered to be homogenized by the initial heating in step S15. When the strain energy is homogenized, the strain of the lithium cobalt oxide is relaxed. As a result, the surface of the lithium cobalt oxide may become smooth. This is also called the surface being improved. In other words, it is considered that the shrinkage difference caused in the lithium cobalt oxide is relaxed after step S15, and the surface of the composite oxide becomes smooth.

[0055] Furthermore, the shrinkage difference may cause microscopic deviations, such as crystal deviations, in the lithium cobalt oxide. In order to reduce such deviations, it is advisable to carry out this step. Through this step, it is possible to equalize the deviations in the composite oxide. When the deviations are equalized, the surface of the composite oxide may become smooth. This is also referred to as the alignment of crystal grains. In other words, it is believed that through step S15, deviations of crystals and the like that have occurred in the composite oxide are alleviated, and the surface of the composite oxide becomes smooth.

[0056] When lithium cobalt oxide, which has a smooth surface, is used as the positive electrode active material, deterioration during charging and discharging as a secondary battery is reduced and cracking of the positive electrode active material can be prevented.

[0057] Note that lithium cobalt oxide (commercially available) synthesized in advance may be used in step S14. In this case, steps S11 to S13 can be omitted. By carrying out step S15 on lithium cobalt oxide synthesized in advance, lithium cobalt oxide with a smooth surface can be obtained.

[0058] <Step S20> 1B, a source of an additive element A (A source) to be added to the lithium cobalt oxide is prepared. A lithium source may be prepared together with the additive element A source.

[0059] The additive element A may be one or more elements selected from magnesium, fluorine, aluminum, titanium, and nickel.

[0060] In this embodiment, as shown in step S21, a Mg source and a F source are used. Magnesium fluoride is used as the Mg source, and lithium fluoride is used as the F source.

[0061] Then, pulverization or mixing is carried out as shown in step S22, and a source of additive element A (A source) is obtained in step S23.

[0062] Then, the additive element A source (A source) is placed in a container, and as shown in step S24, the additive element A is coated on the inner surface of the container. In this embodiment, a square container (made of ceramics) called a sheath is used, and the container or the inner surface of the lid is heated with a lid (made of ceramics) to contain the additive element A. The additive element A may be coated on the inner surface as a film, or may be impregnated into the inner surface of the container. Note that the additive element A impregnating the inner surface of the container is synonymous with the additive element A adhering to the unevenness of the inner surface of the container, the additive element A diffusing into the inner surface of the container, or the additive element A being added to the inner surface of the container.

[0063] When a large-capacity container is used, a large amount of the additive element A source (A source) can be coated on or impregnated into the inner surface of the container, compared to the amount of lithium cobalt oxide. In addition, if a large amount of the additive element A source (A source) can be coated on or impregnated into the inner surface of the container, the container can be used multiple times.

[0064] In this way, a container is prepared whose inner surface is coated with the A source.

[0065] Then, the lithium cobalt oxide that has been subjected to the initial heating is placed in a container whose inner surface is coated with the A source, and heating is performed as shown in step S33.

[0066] 1(B) shows an example in which a Mg source and a F source are prepared, but this is not particularly limited, and if one material is used as the A source as shown in FIG. 2, step S22 can be omitted. For example, if lithium fluoride is used as the A source and cordierite containing magnesium oxide is used as the container material, the same effect as that of containing fluorine and magnesium in the vicinity of the particle surface of lithium cobalt oxide can be obtained during heating in step S33.

[0067] FIG. 3(A) shows an example in which step S33 is performed in a heating furnace.

[0068] The heating furnace 220 shown in FIG. 3(A) has a heating furnace space 202, a hot plate 204, a pressure gauge 221, a heater unit 206, and a heat insulating material 208. It is preferable to place a lid 218 on a container 216 corresponding to a sheath and heat it. FIG. 3(B) shows a top view of the lid 218, and FIG. 3(C) shows a schematic cross-sectional view of the container 216 and the lid 218. A sealed space is created just by placing the lid 218 on the container 216, but since it is not completely sealed, the inside of the container does not become abnormally high pressure, and it is safe. Since a source of additive element A (typically fluoride) is added to the container 216 in advance, the inside of the space 219 formed by the container 216 and the lid 218 can be made into an atmosphere containing fluoride. During heating, if the state is maintained by covering the space 219 so that the concentration of gasified fluoride in the space 219 is constant or does not decrease, additive element A including fluorine and magnesium can be contained in the vicinity of the particle surface of lithium cobalt oxide 903. Since the space 219 has a smaller volume than the space 202 in the heating furnace, a small amount of fluoride volatilizes, and the atmosphere can be made to contain fluoride. That is, the atmosphere of the reaction system can be made to contain fluoride without significantly reducing the amount of fluoride contained in the lithium cobalt oxide 903. In addition, by using the lid 218, the lithium cobalt oxide 903 can be heated in an atmosphere containing fluoride easily and inexpensively.

[0069] Furthermore, before heating in the heating furnace space 202, a step of making the heating furnace space 202 an atmosphere containing oxygen and a step of placing the container 216 containing the lithium cobalt oxide 903 in the heating furnace space 202 are performed. By performing the steps in this order, the lithium cobalt oxide 903 can be heated in an atmosphere containing oxygen and fluoride. For example, the heating can be performed while flowing gas (flow). The gas can be introduced from the bottom surface of the heating furnace space 202 and exhausted to the top surface. Also, the heating furnace space 202 can be sealed during heating to make it a closed space so that the gas is not carried to the outside (purging).

[0070] There is no particular limitation on the method for making the space inside the heating furnace 202 into an oxygen-containing atmosphere, but examples include a method of evacuating the space inside the heating furnace 202 and then introducing an oxygen-containing gas such as oxygen gas or dry air, and a method of injecting an oxygen-containing gas such as oxygen gas or dry air for a certain period of time. Among these, it is preferable to evacuate the space inside the heating furnace 202 and then introduce oxygen gas (oxygen replacement). The air in the space inside the heating furnace 202 may be considered as an oxygen-containing atmosphere.

[0071] Also, a source of the additive element A (typically a fluoride) that has been soaked into the inner walls of the container 216 and the lid 218 can be re-flying by heating and attached to the lithium cobalt oxide 903 .

[0072] There is no particular limitation on the process for heating the heating furnace 220. Heating may be performed using a heating mechanism provided in the heating furnace 220.

[0073] Although there is no particular limitation on the arrangement of the lithium cobalt oxide 903 when it is placed in the container 216, it is preferable to arrange the lithium cobalt oxide 903 so that the upper surface of the lithium cobalt oxide 903 is flat with respect to the bottom surface of the container 216, in other words, so that the height of the upper surface of the lithium cobalt oxide 903 is uniform, as shown in FIG. 26 .

[0074] The heating in step S33 is preferably performed while controlling the pressure inside the furnace with the pressure gauge 221. The inside of the furnace is preferably in an atmospheric pressure state or a pressurized state. For example, it is considered that the surface of lithium cobalt oxide is easily melted when exposed to a pressurized state. For this reason, LiF and MgF 2 The surface of the lithium cobalt oxide heated together can be melted by applying pressure.

[0075] The cooling after the heating in step S33 may be natural cooling, but it is preferable that the time required for the temperature to fall from the specified temperature to room temperature is within 10 hours to 50 hours. For example, the temperature fall rate is preferably 80°C / h to 250°C / h, and more preferably 180°C / h to 210°C / h. The cooling rate in step S33 is preferably faster than that in step S13. A fast cooling rate is called rapid cooling. If rapid cooling is performed after the melting, a shell can be appropriately produced. Specifically, it becomes possible to produce a narrow shell. The temperature at the end of the temperature fall does not necessarily have to be room temperature, and it is sufficient to cool to a temperature that is acceptable for the next step.

[0076] Furthermore, when the lithium cobalt oxide 903 is heated, it is preferable to control the partial pressure of fluorine or a fluorine compound resulting from a fluorine source or the like within an appropriate range. The partial pressure can also be controlled by placing a lid on the container used in this step and heating it. As mentioned above, the lid can prevent the material from volatilizing or sublimating.

[0077] In the manufacturing method described in this embodiment, the material of the additive element A source (typically a fluoride), for example, LiF, which is a fluorine source, may function as a flux. This function allows the heating temperature to be lowered to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, to 742°C or higher and 950°C or lower, and the additive elements including magnesium are distributed in the surface layer, making it possible to manufacture a positive electrode active material with good characteristics.

[0078] However, since LiF has a lower specific gravity in a gaseous state than oxygen, LiF may volatilize or sublime when heated, and if it volatilizes, the amount of LiF in the lithium cobalt oxide 903 will decrease. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of LiF. Even if LiF is not used as the fluorine source, etc., Li on the lithium cobalt oxide surface may react with F of the fluorine source to produce LiF, which may then volatilize. Therefore, even if a fluorine compound with a higher melting point than LiF is used, it is still necessary to suppress the volatilization.

[0079] Therefore, it is preferable to heat the lithium cobalt oxide 903 in an atmosphere containing LiF, that is, to heat the lithium cobalt oxide 903 in a state where the partial pressure of LiF in the heating furnace is high. By such heating, it is possible to suppress the volatilization of LiF in the lithium cobalt oxide 903. In order to suppress the volatilization of LiF, it is preferable to place a lid on the container serving as the sheath. Since the container serving as the sheath and the lid are exposed to high temperatures, if they are made of materials with different thermal expansion coefficients, the gap between the container serving as the sheath and the lid may become large. Therefore, it is preferable that the container serving as the sheath and the lid are made of the same material.

[0080] The heating in this step is preferably performed so as not to cause adhesion between particles of the lithium cobalt oxide 903. If the particles of the lithium cobalt oxide 903 adhere to each other during heating, the contact area with oxygen in the atmosphere decreases, and the route along which the additive element (e.g., fluorine) diffuses is blocked, which may result in poor distribution of the additive element (e.g., magnesium and fluorine) in the surface layer.

[0081] It is also believed that if an additive element (e.g., fluorine) is uniformly distributed in the surface layer, a smooth positive electrode active material with few irregularities can be obtained. Therefore, in order to maintain the smooth state of the surface after the heating in step S15 or to make it even smoother in this process, it is better for the particles of lithium cobalt oxide 903 not to stick together.

[0082] In order to prevent the lithium cobalt oxide 903 particles from adhering to each other, the lithium cobalt oxide 903 may be heated in a rotary kiln.

[0083] FIG. 4(A) shows an example of a schematic cross-sectional view of a rotary kiln apparatus.

[0084] The manufacturing apparatus 110 has a rotating furnace core tube 111, a heating means 112, a vibration means 119, and a stage 118. The manufacturing apparatus 110 also has a rotation drive device 115 for the furnace core tube 111, a gas supply means 116a, and a gas exhaust means 116b. A container 120a containing a material is placed in the furnace core tube 111.

[0085] The furnace core tube 111 is a thick cylinder with one end serving as a supply port and the other end serving as a discharge port. The furnace core tube 111 rotates to agitate the object to be treated, i.e., the material to be heat-treated, contained in the container 120a.

[0086] The heating means 112 is disposed to surround the furnace core tube 111, and has a function of heating to 700° C. or more and 1200° C. or less. As the heating means 112, for example, a silicon carbide heater, a carbon heater, a metal heater, or a molybdenum disilicide heater can be used.

[0087] The gas supply means 116a has a function of controlling the atmosphere inside the furnace core tube 111 (also referred to as the inside of the processing chamber). An example of the gas supply means 116a is a gas introduction line. The gas introduced is oxygen. When replacing the atmosphere inside the furnace core tube 111, which is the kiln body, the internal gas is first exhausted by the gas exhaust means 116b, and then oxygen gas is supplied from the gas supply means 116a to create a desired oxygen atmosphere. The oxygen gas may be heated before being supplied into the furnace core tube from the gas supply means 116a.

[0088] In addition, although not shown, the gas exhaust means 116b may be provided with a pump for exhausting gas from inside the furnace core tube 111, a valve for preventing backflow, and a detoxification device (combustion detoxification device or plasma detoxification device) for rendering the gas harmless before being released into the outside air.

[0089] For the sake of simplicity, nothing is shown on either end of the furnace core tube 111 in Fig. 4(A), but a gate valve, a glove box, a load chamber, an unload chamber, or a quartz cover is provided. To maintain the cleanliness of the internal space of the furnace core tube 111 and to create an oxygen atmosphere, a gate valve or the like is provided on either end of the furnace core tube 111. After creating an oxygen atmosphere, a heat treatment may be performed without supplying oxygen and with both ends of the furnace core tube 111 closed. The oxygen atmosphere in the furnace core tube 111 may be controlled based on an oxygen concentration meter.

[0090] In the figure, the axis (central axis) of the furnace core tube 111 is not inclined to the horizontal plane, but the axis of the furnace core tube 111 is inclined to the horizontal plane (or the plane of the stage 118) and the container loading side is raised to make it easier to move the container inside the furnace core tube. The inclination angle of the axis of the furnace core tube can be changed by the practitioner as appropriate. The material in the container can also be stirred by increasing the rotation speed of the furnace core tube, but if the rotation speed of the furnace core tube is increased too much, the axis of the furnace core tube is inclined, so the container moves inside the furnace core tube, and the time to reach an area without a heater becomes shorter, and sufficient heat treatment is not performed. Furthermore, if the rotation speed is increased too much, the material may be biased against the inner wall of the container due to centrifugal force, and may not be mixed. Therefore, it is preferable that the rotation speed of the furnace core tube and the inclination angle of the axis are appropriately adjusted by the practitioner so that the heat treatment can be performed for a sufficient time.

[0091] In addition, since a plurality of containers 120a can be continuously inserted and heated in sequence, productivity is improved. Although an example in which two containers are arranged is shown in Fig. 4(A), the number of containers is not particularly limited, and three or more containers may be arranged.

[0092] The container 120a can also be called a capsule or a pod, and the inner surface of the container 120a is preferably coated with the A source by the same method as in FIG. 1(B) or FIG.

[0093] Although not shown, the container 120a may be moved inside the furnace core tube by pushing out one end of the container 120a using a transport robot installed in the load chamber. The movement of the container 120a inside the furnace core tube is not limited to a constant speed, and the container 120a may be moved to a position close to a heating means, rotated there and heated while stirring, and then pushed out to finish the heat treatment after sufficient heat treatment.

[0094] As shown in FIG. 4(B), it is preferable to cover the container 120a with a lid 120b, and FIG. 4(C) is a schematic diagram of the container lid 120b as viewed from one end of the furnace core tube 111. FIG. 4(D) is a schematic cross-sectional diagram of the container 120a, in which the outer diameter of the container 120a is indicated by r2. The outer diameter of the lid 120b is indicated by r3. In FIG. 4(C) and FIG. 4(D), an example is shown in which the outer diameter r2 of the container 120a and the outer diameter r3 of the lid 120b are almost the same, but the outer diameter r3 of the lid 120b may be smaller than the outer diameter r2 of the container. In other words, the outer diameter r3 of the lid is the same as or smaller than the outer diameter r2 of the container.

[0095] FIG. 4(C) also shows the inner diameter R1 of the furnace core tube 111. The outer diameter r2 of the container is set to be half or more and nine-tenths or less of the inner diameter R1 of the furnace core tube. If the furnace core tube is thick, the outer diameter r2 of the container can be made larger, and the closer it is to the inner diameter R1 of the furnace core tube, the more the amount of material that can be heated at one time can be increased. In addition, the closer the outer diameter r2 of the container is to the inner diameter R1 of the furnace core tube, the harder it is to rotate the container. Therefore, in order to sufficiently stir the material, it is better to have some space inside the furnace core tube, so the outer diameter r2 of the container and the inner diameter R1 of the furnace core tube are set to the optimal numerical range. In this specification and the like, the container 120a and the lid 120b are referred to as the container 120a, which is longer in the axial direction, and the lid 120b, which is shorter in the axial direction.

[0096] Also, Fig. 4(E) shows a schematic cross-sectional view of the container 120a and the lid 120b with the lid 120b removed, and shows the inner diameter r1 of the container 120a. Also, Fig. 4(E) shows the depth d1, and the total volume of the internal space of the container 120a with the lid closed can be calculated by r1 x r1 x π x d1. When closing the lid of the container 120a, a screw thread is provided in a spiral shape on the part of the lid 120b that contacts the container, and a screw groove is provided in a spiral shape on the inner peripheral surface of the opening of the container 120a, so that the lid and the container are rotated relative to each other to form a sealed structure (also called a screw-mouth structure). Linear screw threads (or linear grooves) are formed at equal intervals on this lid.

[0097] The vibration means 119 periodically moves up and down during the heat treatment. The vibration means 119 is provided in the gap of the heating means 112 surrounding the furnace core tube 111. A metal bar is used as the vibration means 119, and the metal bar is moved up and down by its own weight and a lifting mechanism using a spring or airflow to give an impact to the furnace core tube and vibrate the container in contact with the inner wall of the furnace core tube.

[0098] FIG. 4(A) shows an example in which vibration means 119 is provided in the vertical direction to vibrate the container, but this is not particularly limited, and vibration means 119 may be provided in the horizontal direction as shown in FIG. 5(A).

[0099] Fig. 5(A) is a schematic cross-sectional view of a manufacturing apparatus in which vibration means 119 is provided in the horizontal direction. The same reference numerals are used for parts common to Fig. 4(A). Fig. 4(A) shows an example in which one vibration means 119 is provided in the vertical direction, whereas Fig. 5(A) shows an example in which two vibration means 119 are provided. Of course, two or more vibration means 119 may be provided, and may be provided appropriately according to the length or diameter of the furnace core tube.

[0100] FIG. 5B is a cross-sectional view taken along the chain line ab in FIG. 5A.

[0101] Furthermore, even if the rotation of the furnace core tube is stopped when the temperature is decreased, and the vibration means 119 is also stopped, as long as sufficient stirring is performed when the temperature is increased and kept at a constant temperature, the material can be manufactured by crushing and sieving even if the material sticks in the container when the temperature is decreased. Therefore, if the material sticks, a crushing process or a sieving process is added. In this way, even if an additional process is required, as long as the material is of high quality and uniform, it will not be a problem in manufacturing secondary batteries.

[0102] By using the manufacturing apparatus 110 shown in FIG. 4(A) or FIG. 5(A), a manufacturing apparatus can be provided that can obtain a large amount of positive electrode active material at once without introducing impurities by heat-treating the material in the container sealed with a lid.

[0103] Using the heating furnace shown in Fig. 3 or the rotary kiln apparatus shown in Fig. 4, the additive element A can be added to the lithium cobalt oxide that has been initially heated in step S33. Adding the additive element A to the lithium cobalt oxide that has been initially heated allows the additive element A to be added evenly. Therefore, the order of adding the additive element A after the initial heating is preferable.

[0104] Then, when the material is removed from the container, the positive electrode active material 100 is obtained as shown in step S34. In step S34, the heated material is collected and crushed as necessary to obtain the positive electrode active material 100. At this time, it is preferable to further sieve the collected particles. Note that the positive electrode active material of one embodiment of the present invention has a smooth surface.

[0105] In step S33, by heating the container with a lid, outward diffusion is suppressed, and the additive element is collected in the surface layer of the positive electrode active material 100, so that the surface layer can form a good barrier film. In addition, elution of magnesium from the positive electrode active material is suppressed, and the O3' structure described later is more easily formed.

[0106] This process can be said to be a method of indirectly forming a barrier film by using a container, rather than directly mixing lithium cobalt oxide powder with powder of additive element A. Therefore, when mixing directly, if the amount of additive element A powder is large compared to the amount of lithium cobalt oxide powder, a remainder is generated, and it becomes troublesome to separate the reaction residue, but when a barrier film is indirectly formed using a container, such a problem does not occur.

[0107] (Embodiment 2) In this embodiment, a positive electrode active material 100 of one embodiment of the present invention which is manufactured using the manufacturing method and the manufacturing apparatus described in Embodiment 1 will be described with reference to FIGS.

[0108] Fig. 6(A) is a cross-sectional view of a positive electrode active material 100 according to one embodiment of the present invention. Fig. 6(B1) and Fig. 6(B2) are enlarged views of the vicinity of AB in Fig. 6(A).

[0109] As shown in Fig. 6(A) to Fig. 6(B2), the positive electrode active material 100 has a surface layer portion 100a and an inner portion 100b. In these figures, the boundary between the surface layer portion 100a and the inner portion 100b is indicated by a dashed line. Also, in Fig. 6(A), a part of a crystal grain boundary 101 is indicated by a dashed line.

[0110] In this specification, the surface layer 100a of the positive electrode active material 100 refers to, for example, a region within 50 nm from the surface toward the inside, more preferably within 35 nm from the surface toward the inside, even more preferably within 20 nm from the surface toward the inside, and most preferably within 10 nm from the surface toward the inside, perpendicular or approximately perpendicular from the surface. Note that approximately perpendicular is 80° or more and 100° or less. Surfaces caused by cracks and / or cracks may also be called the surface. The surface layer 100a is synonymous with the surface vicinity, the surface vicinity region, or the shell.

[0111] The region deeper than the surface layer 100a of the positive electrode active material is referred to as the inner portion 100b, which is synonymous with the inner region or the core.

[0112] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the surface layer portion 100a and the inner portion 100b. 2 O 3 This does not include metal oxides having no lithium sites that can contribute to charging and discharging, such as carbonates and hydroxyl groups that are chemically adsorbed after the preparation of the positive electrode active material. The attached metal oxides are, for example, metal oxides whose crystal structure does not match that of the inside 100b.

[0113] It also does not include electrolytes, organic solvents, binders, conductive materials, or compounds derived from these that are attached to the positive electrode active material 100.

[0114] Since the positive electrode active material 100 is a compound containing a transition metal and oxygen capable of inserting and extracting lithium, the interface between the region where the transition metal M (e.g., Co, Ni, Mn, Fe, etc.) that is oxidized and reduced with the insertion and extraction of lithium and oxygen is present and the region where it is not present is defined as the surface of the positive electrode active material. Surfaces caused by slips, cracks, and / or cracks may also be considered to be the surface of the positive electrode active material. When the positive electrode active material is subjected to analysis, a protective film may be attached to the surface, but the protective film is not included in the positive electrode active material. As the protective film, a single layer film or a multilayer film of carbon, metal, oxide, resin, etc. may be used.

[0115] Therefore, the surface of the positive electrode active material in STEM-EDX line analysis, etc., is the average amount of the transition metal M detected inside AVE and the background mean value M BG The point where oxygen is 50% of the sum of the two, and the average amount of oxygen detected inside is O AVE and the average background O BG If the points where the sum of the interior and the background is 50% are different for the transition metal M and oxygen, it is considered to be due to the influence of metal oxides and carbonates containing oxygen attached to the surface. Therefore, the average value M of the detection amount inside the transition metal M is used. AVE and the background mean value M BG In the case of a positive electrode active material having a plurality of transition metals M, the M of the element with the largest count number in the inner portion 100b can be used. AVE and M. BG The surface can be found using

[0116] The average background value of the transition metal M BG can be obtained by averaging the outermost range of 2 nm or more, preferably 3 nm or more, avoiding the vicinity where the amount of detected transition metal M starts to increase. AVEcan be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, at a depth of 30 nm or more, preferably 50 nm or more, from the region where the counts of the transition metal M and oxygen are saturated and stable, for example, the region where the detected amount of the transition metal M starts to increase. BG and the average internal detection amount of oxygen, O AVE can also be found in the same way.

[0117] The surface of the positive electrode active material 100 in a cross-sectional STEM (scanning transmission electron microscope) image or the like is the boundary between an area where an image derived from the crystal structure of the positive electrode active material is observed and an area where it is not observed, and is the outermost area where an atomic column derived from the atomic nucleus of a metal element having a larger atomic number than lithium among the metal elements constituting the positive electrode active material is confirmed. Alternatively, it is the intersection point of a tangent drawn to a brightness profile from the surface to the bulk in a STEM image and an axis in the depth direction. The surface in a STEM image or the like may be determined in conjunction with an analysis with higher spatial resolution.

[0118] In addition, the spatial resolution of STEM-EDX is about 1 nm. Therefore, the maximum value of the additive element profile may deviate by about 1 nm. For example, even if the maximum value of the additive element profile of magnesium or the like is outside the surface obtained above, it can be considered an error as long as the difference between the maximum value and the surface is less than 1 nm.

[0119] In addition, a peak in STEM-EDX line analysis refers to the detected intensity in each element profile or the maximum value of the characteristic X-rays for each element. Note that noise in STEM-EDX line analysis can be considered to be a measurement value with a half-width less than the spatial resolution (R), for example, R / 2 or less.

[0120] The effect of noise can be reduced by scanning the same location multiple times under the same conditions. For example, the integrated values ​​measured over six scans can be used as the profile for each element. The number of scans is not limited to six, and it is also possible to perform more than six scans and use the average as the profile for each element.

[0121] The STEM-EDX line analysis can be carried out, for example, as follows: First, a protective film is deposited on the surface of the positive electrode active material. For example, carbon can be deposited using an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies).

[0122] Next, the positive electrode active material is sliced ​​to prepare a STEM cross-section sample. For example, the slice processing can be performed using a FIB-SEM device (Hitachi High-Tech XVision200TBS). In this case, the pickup is performed using an MPS (micro-probing system), and the finishing processing conditions can be, for example, an acceleration voltage of 10 kV.

[0123] For STEM-EDX analysis, for example, a STEM device (Hitachi High-Tech HD-2700) can be used, and an EDAX Octane T Ultra W (two-wire) EDX detector can be used. During EDX analysis, the emission current of the STEM device is set to 6 μA or more and 10 μA or less, and a portion of the sliced ​​sample with minimal depth and unevenness is measured. The magnification is, for example, about 150,000 times. The conditions for EDX analysis can be drift correction, line width 42 nm, pitch 0.2 nm, and frame number 6 or more.

[0124] The crystal grain boundary 101 refers to, for example, a portion where particles of the positive electrode active material 100 are stuck together, a portion where the crystal orientation changes inside the positive electrode active material 100, i.e., a portion where the repetition of bright and dark lines in a STEM image or the like becomes discontinuous, a portion containing many crystal defects, a portion where the crystal structure is disordered, etc. The crystal defect refers to a defect that can be observed in a cross-sectional TEM (transmission electron microscope) or cross-sectional STEM image, i.e., a structure in which other atoms have entered between the lattices, a cavity, etc. The crystal grain boundary 101 can be said to be one of the planar defects. The vicinity of the crystal grain boundary 101 refers to a region within 10 nm of the crystal grain boundary 101.

[0125] <Contained elements> The positive electrode active material 100 contains lithium, cobalt, oxygen, and an additive element. Alternatively, the positive electrode active material 100 may be lithium cobalt oxide (LiCoO 2) to which an additive element is added. However, the positive electrode active material 100 of one embodiment of the present invention may have any crystal structure described below. Therefore, the composition of lithium cobalt oxide is not strictly limited to Li:Co:O=1:1:2.

[0126] The positive electrode active material of a lithium ion secondary battery needs to have a transition metal capable of oxidation and reduction in order to maintain charge neutrality even when lithium ions are inserted and removed. The positive electrode active material 100 of one embodiment of the present invention preferably uses cobalt as the transition metal responsible for the oxidation and reduction reaction. In addition to cobalt, at least one or two selected from nickel and manganese may be used. If the positive electrode active material 100 contains 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more of cobalt, it is preferable because it has many advantages such as being relatively easy to synthesize, being easy to handle, and having excellent cycle characteristics.

[0127] In addition, when the transition metal of the positive electrode active material 100 is 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more of cobalt, lithium nickel oxide (LiNiO 2 ) and other composite oxides in which nickel accounts for the majority of the transition metal, Li x Chief of Staff 2 The stability is better when x in the formula is small. This is thought to be because the influence of distortion due to the Jahn-Teller effect is smaller in cobalt than in nickel. The strength of the Jahn-Teller effect in transition metal compounds varies depending on the number of electrons in the d orbital of the transition metal. In layered rock-salt type composite oxides in which low-spin nickel (III) in octahedral coordination accounts for the majority of the transition metal, such as lithium nickel oxide, the influence of the Jahn-Teller effect is large, and distortion is likely to occur in the octahedral layers of nickel and oxygen. This raises concerns about the collapse of the crystal structure during charge-discharge cycles. In addition, nickel ions are larger than cobalt ions and are close to the size of lithium ions. Therefore, in layered rock-salt type composite oxides in which nickel accounts for the majority of the transition metal, such as lithium nickel oxide, there is an issue that cation mixing of nickel and lithium is likely to occur.

[0128] The additive element contained in the positive electrode active material 100 is preferably one or more selected from magnesium, fluorine, aluminum, titanium, and nickel. The sum of the transition metals among the additive elements is preferably less than 25 atomic %, more preferably less than 10 atomic %, and even more preferably less than 5 atomic %.

[0129] That is, the positive electrode active material 100 can include lithium cobalt oxide having magnesium and fluorine added thereto, lithium cobalt oxide having magnesium, fluorine and titanium added thereto, lithium cobalt oxide having magnesium, fluorine and aluminum added thereto, lithium cobalt oxide having magnesium, fluorine and nickel added thereto, lithium cobalt oxide having magnesium, fluorine, nickel and aluminum added thereto, and the like.

[0130] The additive element is preferably dissolved in the positive electrode active material 100. Therefore, for example, when performing a line analysis by STEM-EDX, the depth at which the amount of the additive element detected increases is preferably located deeper than the depth at which the amount of the transition metal M detected increases, i.e., closer to the inside of the positive electrode active material 100.

[0131] In this specification, the depth at which the amount of a certain element detected in a STEM-EDX line analysis increases refers to the depth at which measurement values ​​that can be determined to be not noise in terms of intensity, spatial resolution, etc., are successively obtained.

[0132] As described below, these additive elements further stabilize the crystal structure of the positive electrode active material 100. In this specification and the like, the additive element is synonymous with a mixture or a part of a raw material.

[0133] The additive elements do not necessarily have to include magnesium, fluorine, aluminum, titanium, and nickel.

[0134] For example, if the positive electrode active material 100 is substantially free of manganese, the above-mentioned advantages of being relatively easy to synthesize and easy to handle, and having excellent cycle characteristics, will be even greater. The weight of manganese contained in the positive electrode active material 100 is preferably, for example, 600 ppm or less, more preferably 100 ppm or less.

[0135] <Crystal structure> <Li x Chief of Staff 2 When the x inside is 1≫ The positive electrode active material 100 according to one embodiment of the present invention is in a discharged state, i.e., Li x Chief of Staff 2 In the case of x=1, it is preferable that the layered rock-salt type composite oxide belongs to the space group R-3m. The layered rock-salt type composite oxide has a high discharge capacity, has a two-dimensional lithium ion diffusion path, is suitable for lithium ion insertion / extraction reactions, and is excellent as a positive electrode active material for secondary batteries. Therefore, it is particularly preferable that the inner part 100b, which occupies most of the volume of the positive electrode active material 100, has a layered rock-salt type crystal structure. The layered rock-salt type crystal structure is shown in FIG. 9 with R-3m O3 attached.

[0136] On the other hand, the surface layer portion 100a of the positive electrode active material 100 according to one embodiment of the present invention preferably has a function of reinforcing the layered structure of the inner portion 100b, which is made up of octahedra of cobalt and oxygen, so that it is not broken even if lithium is removed from the positive electrode active material 100 by charging. Alternatively, the surface layer portion 100a preferably functions as a barrier film for the positive electrode active material 100. Alternatively, the surface layer portion 100a, which is the outer periphery of the positive electrode active material 100, preferably reinforces the positive electrode active material 100. The reinforcement referred to here means suppressing structural changes in the surface layer portion 100a and the inner portion 100b of the positive electrode active material 100, such as oxygen desorption, and / or suppressing oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0137] Therefore, it is preferable that the surface layer portion 100a has a different crystal structure from the inner portion 100b. It is also preferable that the surface layer portion 100a has a composition and a crystal structure that are more stable at room temperature (25° C.) than the inner portion 100b. For example, it is preferable that at least a part of the surface layer portion 100a of the positive electrode active material 100 of one embodiment of the present invention has a rock-salt type crystal structure. Alternatively, it is preferable that the surface layer portion 100a has both a layered rock-salt type crystal structure and a rock-salt type crystal structure. Alternatively, it is preferable that the surface layer portion 100a has characteristics of both a layered rock-salt type crystal structure and a rock-salt type crystal structure.

[0138] The surface layer 100a is the region from which lithium ions are first released during charging, and is a region where the lithium concentration is likely to be lower than that of the interior 100b. The atoms on the surface of the particles of the positive electrode active material 100 in the surface layer 100a are in a state where some of the bonds are broken. Therefore, the surface layer 100a is likely to become unstable, and is a region where degradation of the crystal structure is likely to begin. On the other hand, if the surface layer 100a can be made sufficiently stable, Li x Chief of Staff 2 Even when x is small, for example, 0.24 or less, the layered structure of the inner 100b composed of cobalt and oxygen octahedra can be made difficult to break. Furthermore, the displacement of the layer composed of the inner 100b cobalt and oxygen octahedra can be suppressed.

[0139] In order to make the surface layer 100a have a stable composition and crystal structure, it is preferable that the surface layer 100a has an additive element, and more preferably has a plurality of additive elements. It is also preferable that the surface layer 100a has a higher concentration of one or more selected from the additive elements than the inner portion 100b. It is also preferable that the one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient. It is also more preferable that the distribution of the positive electrode active material 100 differs depending on the additive element. For example, it is more preferable that the depth from the surface of the concentration peak differs depending on the additive element. The concentration peak here refers to the maximum value of the concentration in the surface layer 100a or within 50 nm from the surface.

[0140] For example, some of the additive elements, such as magnesium, fluorine, nickel, titanium, silicon, phosphorus, boron, and calcium, preferably have a concentration gradient that increases from the inside 100b toward the surface, as shown by the gradation in Fig. 6 (B1). An additive element having such a concentration gradient will be referred to as an additive element X.

[0141] Another additive element, such as aluminum or manganese, preferably has a concentration gradient and a concentration peak in a region deeper than additive element X, as shown by the shade of the hatch in FIG. 6(B2). The concentration peak may be present in surface layer portion 100a or may be deeper than surface layer portion 100a. For example, it is preferable that the peak is present in a region of 5 nm to 30 nm from the surface toward the inside. An additive element having such a concentration gradient is referred to as additive element Y.

[0142] 〔magnesium〕 For example, magnesium, which is one of the additive elements X, is divalent, and magnesium ions are more stable at the lithium site than at the cobalt site in the layered rock-salt crystal structure, so they are more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site in the surface layer 100a makes it easier to maintain the layered rock-salt crystal structure. This is because magnesium present at the lithium site is easily absorbed by the CoO 2 It is speculated that this is because it acts as a pillar to support the layers. x Chief of Staff 2 In the above, when x is, for example, 0.24 or less, the desorption of oxygen around magnesium can be suppressed. In addition, the presence of magnesium is expected to increase the density of the positive electrode active material 100. In addition, if the magnesium concentration in the surface layer portion 100a is high, it is expected that the corrosion resistance against hydrofluoric acid generated by decomposition of the electrolyte solution will be improved.

[0143] At an appropriate concentration, magnesium does not adversely affect the insertion and desorption of lithium during charging and discharging, and the above benefits can be enjoyed. However, excessive magnesium may adversely affect the insertion and desorption of lithium. Furthermore, the effect of stabilizing the crystal structure may be reduced. This is thought to be because magnesium enters the cobalt site in addition to the lithium site. In addition, unnecessary magnesium compounds (oxides, fluorides, etc.) that do not substitute for either the lithium site or the cobalt site may segregate on the surface of the positive electrode active material, and may become resistance components of the secondary battery. In addition, as the magnesium concentration of the positive electrode active material increases, the discharge capacity of the positive electrode active material may decrease. This is thought to be because too much magnesium enters the lithium site, reducing the amount of lithium that contributes to charging and discharging.

[0144] Therefore, it is preferable that the amount of magnesium contained in the entire positive electrode active material 100 is appropriate. For example, the number of magnesium atoms is preferably 0.002 to 0.06 times the number of cobalt atoms, more preferably 0.005 to 0.03 times, and even more preferably about 0.01 times. The amount of magnesium contained in the entire positive electrode active material 100 may be a value obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.

[0145] 〔nickel〕 Nickel, which is one of the additive elements X, can exist on either the cobalt site or the lithium site. When nickel exists on the cobalt site, it has a lower redox potential than cobalt, which leads to an increase in discharge capacity, which is preferable.

[0146] In addition, when nickel is present at the lithium site, the shift in the layered structure consisting of octahedra of cobalt and oxygen can be suppressed. The change in volume caused by charging and discharging is also suppressed. The elastic modulus also increases, that is, the material becomes harder. This is because nickel present at the lithium site and CoO 2This is presumably because they function as pillars supporting the layers together. Therefore, it is expected that the crystal structure will be more stable especially when the battery is charged at high temperatures, for example, at 45°C or higher, which is preferable.

[0147] The distance between the cations and anions in nickel oxide (NiO) is smaller than that in MgO and CoO, and is smaller than that in LiCoO 2 The distance between the cations and anions is close to the average distance between the cations and anions in LiCoO 2 The orientation is likely to match.

[0148] In addition, the order of ionization tendency is smallest for magnesium, followed by aluminum, cobalt, and nickel. Therefore, nickel is thought to be less likely to dissolve into the electrolyte during charging than the other elements listed above. Therefore, it is thought to be highly effective in stabilizing the crystal structure of the surface layer when in a charged state.

[0149] Furthermore, nickel is Ni 2+ , Ni 3+ , Ni 4+ Of which, Ni 2+ is the most stable, and nickel has a higher trivalent ionization energy than cobalt. Therefore, it is known that nickel and oxygen alone do not form a spinel crystal structure. Therefore, nickel is thought to have the effect of suppressing the phase change from the layered rock salt type to the spinel type crystal structure.

[0150] On the other hand, an excess of nickel is undesirable because it increases the influence of distortion due to the Jahn-Teller effect, and too much nickel can also adversely affect the insertion and extraction of lithium.

[0151] Therefore, it is preferable that the amount of nickel contained in the entire positive electrode active material 100 is appropriate. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably more than 0% and 7.5% or less of the number of cobalt atoms, preferably 0.05% to 4%, preferably 0.1% to 2%, and more preferably 0.2% to 1%. Alternatively, more than 0% and 4% or less is preferable. Alternatively, more than 0% and 2% or less is preferable. Alternatively, more than 0.05% to 7.5% or less is preferable. Alternatively, more than 0.1% to 7.5% or less is preferable. Alternatively, more than 0.1% to 4% is preferable. The amount of nickel shown here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.

[0152] 〔aluminum〕 Aluminum, which is one of the additive elements Y, can be present at the cobalt site in the layered rock salt crystal structure. Since aluminum is a typical trivalent element and its valence does not change, lithium around the aluminum is unlikely to move even during charging and discharging. Therefore, aluminum and the lithium around it function as pillars and can suppress changes in the crystal structure. Aluminum also has the effect of suppressing the elution of surrounding cobalt and improving continuous charging resistance. In addition, since the Al-O bond is stronger than the Co-O bond, it can suppress the detachment of oxygen around the aluminum. These effects improve the thermal stability. Therefore, if aluminum is included as an additive element, the safety of the positive electrode active material 100 when used in a secondary battery can be improved. In addition, the positive electrode active material 100 can be made to have a crystal structure that is unlikely to collapse even when repeatedly charged and discharged.

[0153] On the other hand, an excess of aluminum may adversely affect the insertion and extraction of lithium.

[0154] Therefore, it is preferable that the amount of aluminum contained in the entire positive electrode active material 100 is appropriate. For example, the number of aluminum atoms contained in the entire positive electrode active material 100 is preferably 0.05% to 4% of the number of cobalt atoms, preferably 0.1% to 2% and more preferably 0.3% to 1.5%. Alternatively, 0.05% to 2% is preferable. Alternatively, 0.1% to 4% is preferable. The amount contained in the entire positive electrode active material 100 here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material 100 using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.

[0155] [Fluorine] In addition, fluorine, which is one of the additive elements X, is a monovalent anion, and when part of the oxygen in the surface layer portion 100a is replaced by fluorine, the lithium desorption energy is reduced. This is because the redox potential of the cobalt ion accompanying lithium desorption differs depending on the presence or absence of fluorine. In other words, when there is no fluorine, the cobalt ion changes from trivalent to tetravalent as lithium desorption occurs. On the other hand, when there is fluorine, the cobalt ion changes from divalent to trivalent as lithium desorption occurs. The redox potential of the cobalt ion differs between the two. Therefore, when part of the oxygen in the surface layer portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the desorption and insertion of lithium ions near the fluorine is likely to occur smoothly. Therefore, when the positive electrode active material 100 is used in a secondary battery, the charge / discharge characteristics, large current characteristics, etc. can be improved. In addition, the presence of fluorine in the surface layer portion 100a having the surface that is in contact with the electrolyte can effectively improve corrosion resistance against hydrofluoric acid. As described in a later embodiment, when the melting point of a fluoride such as lithium fluoride is lower than the melting point of the other additive element sources, it can function as a flux (also called a flux agent) that lowers the melting point of the other additive element sources.

[0156] In addition, titanium oxide, which is one of the additive elements X, is known to have superhydrophilicity. Therefore, by making the surface layer portion 100a of the positive electrode active material 100 have titanium oxide, the wettability to a highly polar solvent may be improved. When the positive electrode active material 100 is used as a secondary battery, the contact at the interface between the positive electrode active material 100 and the highly polar electrolyte may be improved, and an increase in internal resistance may be suppressed.

[0157] In addition, when phosphorus, which is one of the additive elements X, is contained in the surface layer portion 100a, Li x Chief of Staff 2 When the value of x in the above is kept small, it is preferable because short circuits can be suppressed. For example, it is preferable that the compound containing phosphorus and oxygen exists in the surface layer portion 100a.

[0158] In the case where the positive electrode active material 100 contains phosphorus, it is possible that the hydrogen fluoride generated by decomposition of the electrolytic solution or electrolyte reacts with the phosphorus, thereby decreasing the hydrogen fluoride concentration in the electrolyte, which is preferable.

[0159] The electrolyte is LiPF 6 If the electrolyte has a hydrogen fluoride content of 100%, hydrogen fluoride may be generated by hydrolysis. In addition, hydrogen fluoride may be generated by a reaction between polyvinylidene fluoride (PVDF), which is used as a component of the positive electrode, and an alkali. By reducing the hydrogen fluoride concentration in the electrolyte, corrosion of the current collector and / or peeling of the coating 104 may be suppressed. In addition, a decrease in adhesion due to gelation and / or insolubilization of PVDF may be suppressed.

[0160] When the positive electrode active material 100 contains phosphorus together with magnesium, Li x Chief of Staff 2In this case, the stability is extremely high when x is small, which is preferable. When the positive electrode active material 100 contains phosphorus, the number of phosphorus atoms is preferably 1% to 20% of the number of cobalt atoms, more preferably 2% to 10%, and even more preferably 3% to 8%. Or preferably 1% to 10%. Or preferably 1% to 8%. Or preferably 2% to 20%. Or preferably 2% to 8%. Or preferably 3% to 20%. Or preferably 3% to 10%. In addition, the number of magnesium atoms is preferably 0.1% to 10% of the number of cobalt atoms, more preferably 0.5% to 5%, and more preferably 0.7% to 4%. Or preferably 0.1% to 5%. Or preferably 0.1% to 4%. Or preferably 0.5% to 10%. Or preferably 0.5% to 4%. Or preferably 0.7% to 10%. Alternatively, the phosphorus and magnesium concentrations shown here may be values ​​obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GC-MS, ICP-MS, or the like, or may be based on values ​​of the composition of raw materials in the process of producing the positive electrode active material 100.

[0161] Furthermore, when the positive electrode active material 100 has a crack, the progression of the crack can be suppressed by the presence of phosphorus, more specifically, a compound containing phosphorus and oxygen, inside the positive electrode active material with the crack on its surface, for example, in the embedded portion 102.

[0162] [Synergistic effect of multiple elements] Furthermore, when the surface layer 100a contains both magnesium and nickel, there is a possibility that the divalent nickel can exist more stably near the divalent magnesium. x Chief of Staff 2 Even when x in the matrix is ​​small, the elution of magnesium can be suppressed, which can contribute to the stabilization of the surface layer portion 100a.

[0163] For the same reason, in the manufacturing process, when adding an additive element to lithium cobalt oxide, it is preferable that magnesium is added in a process before nickel. Alternatively, it is preferable that magnesium and nickel are added in the same process. Magnesium has a large ionic radius and tends to remain in the surface layer of lithium cobalt oxide regardless of the process in which it is added, whereas nickel can diffuse widely inside lithium cobalt oxide in the absence of magnesium. Therefore, if nickel is added before magnesium, there is a concern that nickel will diffuse into the lithium cobalt oxide and will not remain in the surface layer in a desired amount.

[0164] In addition, it is preferable to have additive elements with different distributions, such as additive element X and additive element Y, in combination, since it is possible to stabilize the crystal structure in a wider region. For example, when the positive electrode active material 100 has both magnesium and nickel, which are part of the additive element X, and aluminum, which is one of the additive elements Y, it is possible to stabilize the crystal structure in a wider region than when it has only one of the additive elements X and Y. In this way, when the positive electrode active material 100 has both additive element X and additive element Y, the additive element Y, such as aluminum, is not essential to the surface, since the additive element X, such as magnesium or nickel, can sufficiently stabilize the surface. Rather, it is preferable that aluminum is widely distributed in a deeper region. For example, it is preferable that aluminum is continuously detected in a region from the surface to a depth of 1 nm to 25 nm. It is preferable to widely distribute aluminum in a region from 0 nm to 100 nm from the surface, preferably from 0.5 nm to 50 nm from the surface, since it is possible to stabilize the crystal structure in a wider region.

[0165] When a plurality of additive elements are contained as described above, the effects of the respective additive elements are synergistic and can contribute to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are contained, the effect of providing a stable composition and crystal structure is high, and this is preferable.

[0166] However, if the surface layer 100a is occupied only by a compound of the additive element and oxygen, it is not preferable because it makes it difficult to insert and remove lithium. For example, it is not preferable for the surface layer 100a to be occupied only by MgO, a structure in which MgO and NiO(II) are solid-solved, and / or a structure in which MgO and CoO(II) are solid-solved. Therefore, the surface layer 100a must contain at least cobalt, and in the discharged state, it must also contain lithium, and must have a path for the insertion and removal of lithium.

[0167] In order to ensure sufficient paths for lithium insertion and desorption, it is preferable that the surface layer 100a has a higher cobalt concentration than magnesium. For example, the ratio Mg / Co of the number of magnesium atoms Mg to the number of cobalt atoms Co is preferably 0.62 or less. It is also preferable that the surface layer 100a has a higher cobalt concentration than nickel. It is also preferable that the surface layer 100a has a higher cobalt concentration than aluminum. It is also preferable that the surface layer 100a has a higher cobalt concentration than fluorine.

[0168] Furthermore, since there is a risk that an excessive amount of nickel will hinder the diffusion of lithium, it is preferable that the surface layer portion 100a has a higher concentration of magnesium than nickel. For example, it is preferable that the number of nickel atoms is 1 / 6 or less of the number of magnesium atoms.

[0169] In addition, it is preferable that some of the added elements, particularly magnesium, nickel and aluminum, have a higher concentration in the surface layer 100a than in the interior 100b, but it is also preferable that they are present randomly and dilutely in the interior 100b. When magnesium and aluminum are present at an appropriate concentration in the lithium site of the interior 100b, it has the effect of making it easier to maintain the layered rock-salt crystal structure as described above. When nickel is present at an appropriate concentration in the interior 100b, it is possible to suppress the deviation of the layered structure consisting of octahedra of cobalt and oxygen as described above. When magnesium and nickel are present together, a synergistic effect of suppressing the elution of magnesium can be expected as described above.

[0170] It is also preferable that the crystal structure changes continuously from the inside 100b toward the surface due to the concentration gradient of the added element as described above, or that the crystal orientation of the surface layer 100a and the inside 100b is roughly the same.

[0171] For example, it is preferable that the crystal structure changes continuously from the inside 100b of the layered rock salt type toward the surface and surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type. It is also preferable that the orientation of the surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type and the inside 100b of the layered rock salt type are approximately the same.

[0172] In this specification, the layered rock-salt type crystal structure belonging to the space group R-3m, which is possessed by a composite oxide containing lithium and a transition metal such as cobalt, refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Defects such as deficiencies of cations or anions may be present. Strictly speaking, the layered rock-salt type crystal structure may have a structure in which the lattice of the rock-salt type crystal is distorted.

[0173] The rock-salt crystal structure is a cubic crystal structure, such as that of the space group Fm-3m, in which cations and anions are arranged alternately. Note that cations or anions may be missing.

[0174] Moreover, the fact that it has both the characteristics of the layered rock salt type and the rock salt type crystal structure can be determined by electron beam diffraction, TEM images, cross-sectional STEM images, etc.

[0175] In the rock salt type, there is no distinction in the cation sites, but in the layered rock salt type, there are two types of cation sites in the crystal structure, one of which is mostly occupied by lithium and the other by a transition metal. The layered structure in which two-dimensional planes of cations and two-dimensional planes of anions are alternately arranged is the same for both the rock salt type and the layered rock salt type. Among the bright spots in the electron diffraction pattern that correspond to the crystal planes that form this two-dimensional plane, when the central spot (transmitted spot) is set as the origin 000, the bright spot closest to the central spot is, for example, the (111) plane in the rock salt type in an ideal state, and, for example, the (003) plane in the layered rock salt type. For example, rock salt type MgO and layered rock salt type LiCoO 2 When comparing the electron diffraction patterns of LiCoO 2 The distance between the bright spots on the (003) surface of LiCoO is observed to be about half the distance between the bright spots on the (111) surface of MgO. 2 In the case of a material with these two phases, the electron diffraction pattern shows that there exists a plane orientation in which bright spots of high brightness and bright spots of low brightness are arranged alternately. Bright spots common to both the rock salt type and the layered rock salt type have high brightness, while bright spots occurring only in the layered rock salt type have low brightness.

[0176] Furthermore, when a layered rock-salt crystal structure is observed from a direction perpendicular to the c-axis in cross-sectional STEM images, layers observed with strong brightness and layers observed with weak brightness are observed alternating. This characteristic is not seen in the rock-salt type, as there is no distinction in the cation sites. In the case of a crystal structure that has characteristics of both the rock-salt type and the layered rock-salt type, when observed from a specific crystal orientation, layers observed with strong brightness and layers observed with weak brightness are observed alternating in cross-sectional STEM images, and furthermore, a metal with an atomic number higher than that of lithium is present in part of the weak brightness layer, i.e., the lithium layer.

[0177] Layered rock-salt crystals and the anions of rock-salt crystals have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions of the O3' type and monoclinic O1(15) crystals described below also have a cubic close-packed structure. Therefore, when a layered rock-salt crystal and a rock-salt crystal come into contact, there are crystal faces where the cubic close-packed structure composed of anions is aligned.

[0178] Alternatively, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock-salt type has a space group of R-3m and a rhombohedral structure, but to make the structure easier to understand, it is generally represented as a compound hexagonal lattice, and the (0001) plane of the layered rock-salt type has a hexagonal lattice. The triangular lattice of the cubic {111} plane has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock-salt type. When the two lattices are compatible, it can be said that the orientation of the cubic close-packed structure is aligned.

[0179] However, the space group of the layered rock salt crystal and O3' type crystal is R-3m, which is different from the space group Fm-3m (the space group of general rock salt crystals) of the rock salt crystal, so the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock salt crystal and O3' type crystal and the rock salt crystal. In this specification, when the orientation of the cubic close-packed structure formed by anions in the layered rock salt crystal, O3' type and rock salt crystal is aligned, it may be said that the crystal orientation is approximately the same. In addition, the three-dimensional structural similarity in which the crystal orientation is approximately the same, or the same crystallographic orientation, is called topotaxis.

[0180] The fact that the crystal orientations of the two regions roughly match can be determined from TEM (Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope) images, electron diffraction patterns, FFT patterns of TEM images and STEM images, etc. XRD (X-ray Diffraction), electron diffraction, neutron diffraction, etc. can also be used as materials for determination.

[0181] An example of a TEM image in which the orientation of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincides is shown in Figure 7. Images reflecting the crystal structure can be obtained in TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc.

[0182] For example, in high-resolution TEM images, contrast originating from crystal planes is observed. When an electron beam is incident perpendicular to the c-axis of a layered rock-salt type composite hexagonal lattice, for example, the contrast originating from the (0003) plane is observed as a repetition of bright and dark bands (bright strips) due to the diffraction and interference of the electron beam. Therefore, a repetition of bright and dark lines is observed in the TEM image, and the bright lines (for example, the L shown in Figure 7) are not clearly distinguishable from each other. RS and L LRS ) is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal planes are roughly aligned, that is, that the crystal orientations are roughly aligned. Similarly, when the angle between the dark lines is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal orientations are roughly aligned.

[0183] In addition, in HAADF-STEM images, contrast proportional to the atomic number is obtained, and elements with higher atomic numbers are observed brighter. For example, in the case of layered rock-salt lithium cobalt oxide belonging to the space group R-3m, cobalt (atomic number 27) has the highest atomic number, so the electron beam is strongly scattered at the position of the cobalt atom, and the arrangement of the cobalt atoms is observed as a bright line or an arrangement of strongly bright dots. Therefore, when lithium cobalt oxide with a layered rock-salt crystal structure is observed perpendicular to the c-axis, the arrangement of the cobalt atoms is observed as a bright line or an arrangement of strongly bright dots perpendicular to the c-axis, and the arrangements of the lithium atoms and oxygen atoms are observed as dark lines or low-brightness areas. The same is true when lithium cobalt oxide has fluorine (atomic number 9) and magnesium (atomic number 12) as added elements.

[0184] Therefore, when bright and dark lines are repeatedly observed in two regions with different crystal structures in a HAADF-STEM image and the angle between the bright lines is 5 degrees or less or 2.5 degrees or less, it can be determined that the atomic arrangements are roughly the same, that is, the crystal orientations are roughly the same. Similarly, when the angle between the dark lines is 5 degrees or less or 2.5 degrees or less, it can also be determined that the crystal orientations are roughly the same.

[0185] In ABF-STEM, elements with smaller atomic numbers appear brighter; however, like HAADF-STEM, it is possible to obtain contrast according to the atomic number, and therefore it is possible to determine the crystal orientation in the same way as with HAADF-STEM images.

[0186] Figure 8(A) shows an example of a STEM image in which the orientations of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincide. Figure 8(B) shows the FFT pattern of the region of the rock-salt crystal RS, and Figure 8(C) shows the FFT pattern of the region of the layered rock-salt crystal LRS. The composition, JCPDS card number, and the d-value and angle calculated from these are shown on the left of Figure 8(B) and Figure 8(C), and the measured values ​​are shown on the right. The spot marked with O is the zeroth order diffraction.

[0187] The spot marked A in Figure 8(B) is due to the 11-1 reflection of the cubic crystal. The spot marked A in Figure 8(C) is due to the 0003 reflection of the layered rock salt type. From Figures 8(B) and 8(C), it can be seen that the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly consistent. In other words, it can be seen that the line passing through AO in Figure 8(B) is roughly parallel to the line passing through AO in Figure 8(C). In this case, roughly consistent and roughly parallel mean that the angle is 5 degrees or less, or 2.5 degrees or less.

[0188] In this way, in the FFT pattern and the electron beam diffraction pattern, when the orientation of the layered rock salt type crystal and the rock salt type crystal roughly coincides, the <0003> orientation of the layered rock salt type and the <11-1> orientation of the rock salt type may roughly coincide. In this case, it is preferable that these reciprocal lattice points are spot-like, that is, not continuous with other reciprocal lattice points. The fact that the reciprocal lattice points are spot-like and not continuous with other reciprocal lattice points means that the crystallinity is high.

[0189] In addition, when the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly the same as described above, depending on the incidence orientation of the electron beam, a spot not derived from the 0003 reflection of the layered rock salt type may be observed in a reciprocal lattice space different from the orientation of the 0003 reflection of the layered rock salt type. For example, the spot marked B in FIG. 8(C) is derived from the 1014 reflection of the layered rock salt type. This may be observed at an angle of 52° to 56° from the orientation of the reciprocal lattice point (A in FIG. 8(C)) derived from the 0003 reflection of the layered rock salt type (i.e., ∠AOB is 52° to 56°), and at a position where d is 0.19 nm to 0.21 nm. Note that this index is an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 0003 and 1014 may be used.

[0190] Similarly, a spot not originating from the 11-1 reflection of a cubic crystal may be observed in a reciprocal lattice space different from the orientation where the 11-1 reflection of a cubic crystal is observed. For example, the spot marked B in FIG. 8(B) originates from the 200 reflection of a cubic crystal. This is a diffraction spot observed at an angle of 54° to 56° (i.e., ∠AOB is 54° to 56°) from the orientation of the reflection originating from the 11-1 of a cubic crystal (A in FIG. 8(B)). Note that this index is only an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 11-1 and 200 may be used.

[0191] It is known that the layered rock salt type positive electrode active material, including lithium cobalt oxide, is likely to have the (0003) plane and its equivalent, as well as the (10-14) plane and its equivalent, as crystal planes. Therefore, by carefully observing the shape of the positive electrode active material with an SEM or the like, it is possible to process the observation sample into a thin slice using an FIB or the like so that the electron beam is [12-10] incident in a TEM or the like so that the (0003) plane is easily observed. When it is desired to determine the coincidence of the crystal orientation, it is preferable to slice the layered rock salt type so that the (0003) plane is easily observed.

[0192] <Li x Chief of Staff 2 The x inside is small≫ The positive electrode active material 100 according to one embodiment of the present invention has the above-described distribution of additive elements and / or crystal structure in a discharged state, and thus has a high degree of conductivity. x Chief of Staff 2 The crystal structure when x is small is different from that of conventional positive electrode active materials. <x≦0.24をいうこととする。

[0193] Using Figs. 9 to 13, Li x Chief of Staff 2 The change in crystal structure accompanying the change in x in the positive electrode active material 100 of one embodiment of the present invention will be described by comparing a conventional positive electrode active material with the positive electrode active material 100 of one embodiment of the present invention.

[0194] The change in the crystal structure of a conventional positive electrode active material is shown in FIG. 10. The conventional positive electrode active material shown in FIG. 10 is made of lithium cobalt oxide (LiCoO 2 In particular, the change in the crystal structure of lithium cobalt oxide that does not contain any added element is described in Non-Patent Documents 1 to 3, etc.

[0195] Figure 10 shows R-3m O3 and Li x Chief of Staff 2 The crystal structure of lithium cobalt oxide with x=1 in the figure shows that lithium occupies octahedral sites and CoO 2There are three layers. Therefore, this crystal structure is sometimes called the O3 type crystal structure. 2 A layer is a structure in which an octahedral structure in which cobalt is six-coordinated with oxygen is connected in a plane with edge sharing. This is sometimes called a layer consisting of cobalt and oxygen octahedra.

[0196] In addition, it is known that conventional lithium cobalt oxide has a crystal structure that belongs to the monoclinic space group P2 / m when the symmetry of lithium increases when x is about 0.5. This structure has CoO 2 There is one layer, so it is sometimes called O1 type or monoclinic O1 type.

[0197] In addition, when x = 0, the positive electrode active material has a crystal structure of the trigonal space group P-3m1, and also has CoO 2 There is one layer. Therefore, this crystal structure is sometimes called O1 type, or trigonal O1 type. In addition, the trigonal crystal is sometimes converted into a composite hexagonal lattice and called hexagonal O1 type.

[0198] Conventional lithium cobalt oxides with x = 0.12 have a crystal structure of the space group R-3m. This structure is similar to the trigonal O1 type CoO 2 and LiCoO such as R-3mO3 2 It can be said that the structure of and the structure of are stacked alternately. Therefore, this crystal structure is sometimes called the H1-3 type crystal structure. In addition, since the actual insertion and desorption of lithium does not necessarily occur uniformly in the positive electrode active material and the lithium concentration may be uneven, the H1-3 type crystal structure is experimentally observed from about x = 0.25. In addition, the number of cobalt atoms per unit cell in the H1-3 type crystal structure is actually twice as much as other structures. However, in Figure 10 and other parts of this specification, in order to make it easier to compare with other crystal structures, the c-axis of the H1-3 type crystal structure is shown as 1 / 2 of the unit cell.

[0199] As an example of the H1-3 type crystal structure, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell can be expressed as Co (0,0,0.42150±0.00016), O1 (0,0,0.27671±0.00045), and O2 (0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Which unit cell should be used to express the crystal structure of the positive electrode active material can be determined, for example, by Rietveld analysis of the XRD pattern. In this case, it is sufficient to adopt a unit cell with a small GOF (goodness of fit) value.

[0200] Li x Chief of Staff 2 When the battery is repeatedly charged and discharged such that x in the formula is 0.24 or less, conventional lithium cobalt oxide repeatedly undergoes a change in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 crystal structure and the R-3m O3 structure in the discharged state.

[0201] However, these two crystal structures are similar to CoO 2 As shown by the dotted lines and arrows in Figure 10, in the H1-3 crystal structure, CoO 2 The layers are significantly different from the R-3m O3 in the discharged state. Such dynamic structural changes can adversely affect the stability of the crystal structure.

[0202] Furthermore, the difference in volume between these two crystal structures is large: per the same number of cobalt atoms, the difference in volume between the H1-3 crystal structure and the discharged R-3m O3 crystal structure exceeds 3.5%, typically 3.9% or more.

[0203] In addition, the H1-3 crystal structure has the same structure as the trigonal O1 structure, i.e., CoO 2 A structure with continuous layers is likely to be unstable.

[0204] Therefore, when charging and discharging are repeated so that x is 0.24 or less, the crystal structure of conventional lithium cobalt oxide collapses. The collapse of the crystal structure causes a deterioration in cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.

[0205] On the other hand, in the positive electrode active material 100 according to one embodiment of the present invention shown in FIG. x Chief of Staff 2 The change in the crystal structure between the discharged state where x is 1 and the state where x is 0.24 or less is smaller than that of conventional positive electrode active materials. More specifically, the change in the crystal structure between the discharged state where x is 1 and the state where x is 0.24 or less is smaller than that of conventional positive electrode active materials. 2 The layer misalignment can be reduced. Also, the change in volume per cobalt atom can be reduced. Therefore, the positive electrode active material 100 according to one embodiment of the present invention is less likely to lose its crystal structure even when it is repeatedly charged and discharged such that x is 0.24 or less, and excellent cycle characteristics can be achieved. In addition, the positive electrode active material 100 according to one embodiment of the present invention is Li x Chief of Staff 2 In the state where x is 0.24 or less, the positive electrode active material 100 can have a more stable crystal structure than the conventional positive electrode active material. x Chief of Staff 2 When the value of x in the formula (1) is kept at 0.24 or less, short circuits are unlikely to occur. In such a case, the safety of the secondary battery is further improved, which is preferable.

[0206] Li x Chief of Staff 2 The crystal structures of the interior 100b of the positive electrode active material 100 when x is 1, approximately 0.2, and approximately 0.15 are shown in FIG. 9. The interior 100b occupies most of the volume of the positive electrode active material 100 and is the part that contributes greatly to charging and discharging. 2 Layer shift and volume change are the most problematic areas.

[0207] When x=1, the positive electrode active material 100 has the same crystal structure of R-3m O3 as conventional lithium cobalt oxide.

[0208] However, the positive electrode active material 100 has a crystal structure different from that of conventional lithium cobalt oxide when x is 0.24 or less, for example, about 0.2 or about 0.15, in which case the lithium cobalt oxide has an H1-3 type crystal structure.

[0209] The positive electrode active material 100 according to one embodiment of the present invention when x=0.2 has a crystal structure belonging to the trigonal space group R-3m. 2 The symmetry of the layers is the same as that of O3. Therefore, this crystal structure is called the O3' type crystal structure. Figure 9 shows this crystal structure with R-3m O3'.

[0210] The O3' type crystal structure can show the coordinates of cobalt and oxygen in the unit cell within the range of Co(0,0,0.5), O(0,0,x), 0.20≦x≦0.25. The lattice constant of the unit cell is preferably 2.797≦a≦2.837(Å), more preferably 2.807≦a≦2.827(Å), typically a=2.817(Å). The c-axis is preferably 13.681≦c≦13.881(Å), more preferably 13.751≦c≦13.811(Å), typically c=13.781(Å).

[0211] In addition, the positive electrode active material 100 according to one embodiment of the present invention when x=0.15 has a crystal structure belonging to the monoclinic space group P2 / m. This is because CoO 2 There is one layer. In addition, the amount of lithium present in the positive electrode active material 100 is about 15 atomic % in the discharged state. Therefore, this crystal structure is called a monoclinic O1(15) type crystal structure. This crystal structure is shown in Figure 9 with the P2 / m monoclinic O1(15) attached.

[0212] The monoclinic O1(15) crystal structure has the coordinates of cobalt and oxygen in the unit cell as follows: Co1(0.5,0,0.5), Co2(0,0.5,0.5), O1(X O1 ,0,Z O1 ), 0.23≦X O1 ≦0.24, 0.61≦Z O1 ≦0.65, O2(X O2 ,0.5,Z O2 ), 0.75≦X O2 ≦0.78, 0.68≦Z O2 The lattice constant of the unit cell is in the range of ≦0.71. a = 4.880 ± 0.05 Å, b = 2.817 ± 0.05 Å, c = 4.839 ± 0.05 Å, α=90°, β=109.6±0.1°, γ=90°.

[0213] It is possible to show the lattice constants of this crystal structure in the space group R-3m if a certain degree of error is allowed. In this case, the coordinates of cobalt and oxygen in the unit cell are Co(0,0,0.5), O(0,0,Z O ), 0.21≦Z O ≦0.23. The lattice constant of the unit cell is a = 2.817 ± 0.02 Å, c=13.68±0.1 Å.

[0214] In both the O3' and monoclinic O1(15) crystal structures, ions of cobalt, nickel, magnesium, etc. occupy 6-coordinate oxygen sites, although lighter elements such as lithium and magnesium may occupy 4-coordinate oxygen sites.

[0215] As shown by the dotted line in Fig. 9, the discharged R-3m O3, O3', and monoclinic O1(15) type crystal structures show a large difference in the CoO 2 There is almost no layer misalignment.

[0216] The difference in volume per the same number of cobalt atoms between R-3m O3 in a discharged state and the O3' type crystal structure is 2.5% or less, more specifically 2.2% or less, typically 1.8%.

[0217] The difference in volume per the same number of cobalt atoms between R-3m O3 in a discharged state and the monoclinic O1(15) type crystal structure is 3.3% or less, more specifically 3.0% or less, typically 2.5%.

[0218] Table 1 shows the difference in volume per cobalt atom between R-3m O3 in a discharged state, O3', monoclinic O1(15), H1-3 type, and trigonal O1. For the lattice constants of each crystal structure used in the calculation of Table 1, literature values ​​can be referred to for R-3m O3 and trigonal O1 in a discharged state (ICSD coll.code.172909 and 88721). For H1-3, Non-Patent Document 3 can be referred to. For O3' and monoclinic O1(15), they can be calculated from experimental values ​​of XRD.

[0219] [Table 1]

[0220] In this way, in the positive electrode active material 100 according to one embodiment of the present invention, Li x Chief of Staff 2 When x in the positive electrode active material is small, that is, when a large amount of lithium is released, the change in the crystal structure is suppressed more than in the conventional positive electrode active material. In addition, the change in volume is also suppressed when compared per the same number of cobalt atoms. Therefore, the positive electrode active material 100 does not easily lose its crystal structure even when repeatedly charged and discharged so that x is 0.24 or less. Therefore, the positive electrode active material 100 suppresses the decrease in charge / discharge capacity during charge / discharge cycles. In addition, since the positive electrode active material 100 can stably use more lithium than the conventional positive electrode active material, the positive electrode active material 100 has a large discharge capacity per weight and per volume. Therefore, by using the positive electrode active material 100, a secondary battery with a high discharge capacity per weight and per volume can be manufactured.

[0221] The positive electrode active material 100 is Li x Chief of Staff 2 It has been confirmed that when x is 0.15 or more and 0.24 or less, it may have an O3' type crystal structure, and it is presumed that it also has an O3' type crystal structure when x is more than 0.24 and 0.27 or less. x Chief of Staff 2 It has been confirmed that when x is greater than 0.1 and less than 0.2, typically between 0.15 and 0.17, the crystal structure may be monoclinic O1(15) type. However, the crystal structure is Li x Chief of Staff 2 Since the range of x is influenced by not only the number of charge / discharge cycles, the charge / discharge current, the temperature, the electrolyte, etc., the range of x is not necessarily limited to the above range.

[0222] Therefore, the positive electrode active material 100 is Li x Chief of Staff 2 When x is more than 0.1 and not more than 0.24, the positive electrode active material 100 may have only O3' type, may have only monoclinic O1(15) type, or may have both crystal structures. All particles in the inside 100b of the positive electrode active material 100 may not have O3' type and / or monoclinic O1(15) type crystal structures. They may contain other crystal structures, or may be partially amorphous.

[0223] Also Li x Chief of Staff 2 To make the x in the battery small, it is generally necessary to charge the battery at a high charging voltage. x Chief of Staff 2 In other words, a state where x is small can be said to be a state where the battery is charged at a high charging voltage. For example, when the battery is charged by CC / CV at a voltage of 4.6 V or more based on the potential of lithium metal in an environment of 25°C, an H1-3 type crystal structure appears in a conventional positive electrode active material. Therefore, a charging voltage of 4.6 V or more based on the potential of lithium metal can be said to be a high charging voltage. In addition, in this specification and the like, unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal.

[0224] Therefore, the positive electrode active material 100 of one embodiment of the present invention can be said to be preferable because it can maintain a crystal structure having the symmetry of R-3m O3 even when charged at a high charging voltage, for example, a voltage of 4.6 V or more at 25° C. In other words, it can be said to be preferable because it can adopt an O3'-type crystal structure when charged at a higher charging voltage, for example, a voltage of 4.65 V or more and 4.7 V or less at 25° C. In other words, it can be said to be preferable because it can adopt a monoclinic O1(15)-type crystal structure when charged at an even higher charging voltage, for example, a voltage of more than 4.7 V and 4.8 V or less at 25° C.

[0225] In the case of the positive electrode active material 100, when the charging voltage is further increased, the H1-3 type crystal may be observed. As described above, the crystal structure is affected by the number of charge / discharge cycles, the charge / discharge current, the temperature, the electrolyte, and the like. Therefore, when the charging voltage is lower, for example, even when the charging voltage is 4.5 V or more and less than 4.6 V at 25° C., the positive electrode active material 100 of one embodiment of the present invention may have the O3′ type crystal structure. Similarly, when the positive electrode active material 100 is charged at a voltage of 4.65 V or more and 4.7 V or less at 25° C., the positive electrode active material 100 may have the monoclinic O1(15) type crystal structure.

[0226] In addition, when graphite is used as the negative electrode active material in the secondary battery, the voltage of the secondary battery is lower than the above by the potential of the graphite. The potential of graphite is about 0.05 V to 0.2 V based on the potential of lithium metal. Therefore, in the case of a secondary battery using graphite as the negative electrode active material, the battery has the same crystal structure at a voltage obtained by subtracting the potential of graphite from the above voltage.

[0227] In addition, in FIG. 9, O3' and monoclinic O1(15) are shown as having lithium with equal probability at all lithium sites, but this is not limited to this. Lithium may be present biasedly at some lithium sites, for example, in the monoclinic O1(Li 0.5 Chief of Staff 2 The distribution of lithium can be analyzed, for example, by neutron diffraction.

[0228] The crystal structures of O3' and monoclinic O1(15) types also have random lithium between the layers, but CdCl 2 It can be said that the crystal structure is similar to that of the CdCl type. 2 A similar crystal structure to the Li-type is lithium nickel oxide (Li 0.06 NiO 2 The crystal structure is close to that when the battery is charged to 100%. However, pure lithium cobalt oxide or layered rock salt-type positive electrode active materials that contain a lot of cobalt are usually CdCl 2 It is known that it does not have a typical crystal structure.

[0229] In addition, it is preferable that the concentration gradient of the additive element is the same in multiple locations on the surface layer 100a of the positive electrode active material 100. In other words, it is preferable that the reinforcement resulting from the additive element is present homogeneously in the surface layer 100a. Even if a portion of the surface layer 100a is reinforced, if there is a portion without reinforcement, stress may be concentrated in the portion without reinforcement. If stress is concentrated in a portion of the positive electrode active material 100, defects such as cracks may occur there, which may lead to cracking of the positive electrode active material and a decrease in discharge capacity.

[0230] However, the additive element does not necessarily have to have the same concentration gradient in the entire surface layer portion 100a of the positive electrode active material 100. Enlarged views of the vicinity of CD in Fig. 6(A) are shown in Fig. 11(A1) and Fig. 11(A2). An example of the distribution of additive element X in the vicinity of CD in Fig. 6(A) is shown in Fig. 11(A1), and an example of the distribution of additive element Y in the vicinity of CD is shown in Fig. 11(A2).

[0231] Here, the vicinity of CD has a layered rock salt type crystal structure of R-3m, and the surface is (001) oriented. The (001) oriented surface may have a different distribution of the additive element from the other surfaces. For example, the (001) oriented surface and its surface layer 100a may have a distribution of one or more concentration peaks selected from the additive element X and the additive element Y limited to a shallower portion from the surface compared to the surfaces other than the (001) oriented surface. Alternatively, the (001) oriented surface and its surface layer 100a may have a lower concentration of one or more selected from the additive element X and the additive element Y compared to the surfaces other than the (001) oriented surface. Alternatively, the (001) oriented surface and its surface layer 100a may have a concentration of one or more selected from the additive element X and the additive element Y below the lower detection limit.

[0232] In the layered rock-salt crystal structure of R-3m, the cations are arranged parallel to the (001) plane. This is because CoO 2 The structure is composed of alternately stacked layers and lithium layers parallel to the (001) plane. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane.

[0233] Chief of Staff 2 Since the layer is relatively stable, it is more stable for the surface of the positive electrode active material 100 to have a (001) orientation. The main diffusion path of lithium ions during charging and discharging is not exposed to the (001) plane.

[0234] On the other hand, the diffusion path of lithium ions is exposed on the surface other than the (001) orientation. Therefore, the surface and the surface layer 100a other than the (001) orientation are important regions for maintaining the diffusion path of lithium ions, and at the same time, they are regions from which lithium ions are first desorbed and are therefore prone to become unstable. Therefore, it is extremely important to reinforce the surface and the surface layer 100a other than the (001) orientation in order to maintain the crystal structure of the entire positive electrode active material 100.

[0235] Therefore, in the positive electrode active material 100 according to another embodiment of the present invention, it is important that the distribution of the additive elements in the surface other than the (001) orientation and the surface layer 100a thereof is as shown in Fig. 6(B1) or 6(B2). Of the additive elements, nickel is particularly preferably detected in the surface other than the (001) orientation and the surface layer 100a thereof. On the other hand, the concentration of the additive element in the (001) oriented surface and the surface layer 100a thereof may be low or absent as described above.

[0236] For example, the magnesium distribution in the (001) oriented surface and its surface layer 100a preferably has a half-width of 10 nm to 200 nm, more preferably 50 nm to 150 nm, and even more preferably 80 nm to 120 nm. Also, the magnesium distribution in the non-(001) oriented surface and its surface layer 100a preferably has a half-width of more than 200 nm to 500 nm, more preferably more than 200 nm to 300 nm, and even more preferably 230 nm to 270 nm.

[0237] The nickel distribution in the non-(001) oriented surface and in the surface layer 100a thereof preferably has a half-width of 30 nm to 150 nm, more preferably 50 nm to 130 nm, and even more preferably 70 nm to 110 nm.

[0238] High-purity LiCoO, which will be described in a later embodiment. 2 In the method of preparing the silicon nitride film, the additive element is mixed in and heated after the preparation, and the additive element spreads mainly through the diffusion path of lithium ions, so that the distribution of the additive element in the surface other than the (001) orientation and in the surface layer portion 100a thereof can be easily controlled to a preferred range.

[0239] Using FIG. 11(B1) to FIG. 11(C), high purity LiCoO 2 After preparing the alloy, additive elements were mixed in and heated, and the results of calculations on the distribution of additive elements will be described.

[0240] FIG. 11(B1) shows the results of calculations for a (104) oriented surface and its surface layer 100a. The calculations were performed using the classical molecular dynamics method. LiCoO 2 (LCO), and LiF and MgF as magnesium, lithium and fluorine sources at the top and bottom of the system. 2 The ensemble is NVT, and the density of the initial structure is 1.8 g / cm 3 The temperature of the system is 2000K, the elapsed time is 100psec, the potential is optimized with the LCO crystal structure, the other atoms are mixed with UFF, the number of atoms in the system is about 10,000, and the charge of the system is neutral. To simplify the figure, only Co and Mg atoms are shown.

[0241] FIG. 11(B2) shows the results of similar calculations up to 200 psec, and FIG. 11(B3) shows the results up to 1200 psec.

[0242] From the above calculations, it is inferred that magnesium diffuses through the following process: (1) Lithium is desorbed from LCO by heat. (2) Magnesium enters the lithium layer of LCO and diffuses inward. (3) Lithium from LiF enters the lithium layer of LCO and supplements the lithium desorbed in (1).

[0243] In Figure 11(B1), after 100 psec, it is clear that magnesium atoms are diffusing into the LCO. The magnesium atoms diffuse along the arrangement of cobalt atoms, and in Figure 11(B3), after 1200 psec, almost all of the magnesium atoms prepared at the top of the system are incorporated into the LCO.

[0244] Figure 11(C) shows the results of calculations similar to those of Figure 11(B1), except that the orientation is (001). Figure 11(C) shows that the magnesium atoms remain on the surface of the LCO. However, Figure 11(C) shows the results of calculations after 100 psec has elapsed. In the actual cathode active material 100, for example, heating is performed for more than two hours to prepare the material, so it is believed that the magnesium atoms diffuse slowly into the interior of the LCO.

[0245] This high purity LiCoO 2 By using a manufacturing method in which additive elements are mixed and heated after the (001) plane is manufactured, it is possible to achieve a more favorable distribution of additive elements in the surfaces other than the (001) orientation and in the surface layer portion 100a thereof than in the (001) plane.

[0246] In the manufacturing method involving initial heating, which will be described later, the lithium in the surface layer 100a is converted to LiCoO 2 This is expected to result in the magnesium and other additive elements being more easily distributed in the surface layer at high concentrations.

[0247] In addition, the surface of the positive electrode active material 100 is preferably smooth and has few irregularities, but this is not necessarily the case for the entire surface of the positive electrode active material 100. A composite oxide having a layered rock salt type crystal structure of R-3m is prone to slippage in a plane parallel to the (001) plane, for example, a plane in which lithium is arranged. For example, as shown in FIG. 12(A), when a (001) plane is present, slippage may occur parallel to the (001) plane as shown by the arrow in FIG. 12(B) by a process such as pressing, resulting in deformation.

[0248] In this case, the surface newly generated as a result of the slip and its surface layer 100a may not contain the additive element or the concentration may be below the detection limit. EF in FIG. 12(B) is an example of the surface newly generated as a result of the slip and its surface layer 100a. Enlarged views of the vicinity of EF are shown in FIG. 12(C1) and FIG. 12(C2). Unlike FIG. 6(B1) to FIG. 6(B2), additive element X and additive element Y are not distributed in FIG. 12(C1) and FIG. 12(C2).

[0249] However, since slippage tends to occur parallel to the (001) plane, the newly formed surface and its surface layer 100a tend to have a (001) orientation. In this case, the diffusion path of lithium ions is not exposed and it is relatively stable, so there is almost no problem even if the added element is not present or its concentration is below the detection limit.

[0250] As mentioned above, the composition is LiCoO2 In the complex oxide with a layered rock-salt type crystal structure of R-3m, the cobalt atoms are arranged parallel to the (001) plane. 2 Of these, cobalt, which has the highest atomic number, has the highest brightness. Therefore, in a HAADF-STEM image, the arrangement of bright atoms can be considered to be the arrangement of cobalt atoms. The repetition of this arrangement of bright atoms is synonymous with crystal fringes or lattice fringes.

[0251] <Grain Boundaries> It is more preferable that the additive element contained in the positive electrode active material 100 of one embodiment of the present invention is distributed as described above, and that at least a part of the additive element is unevenly distributed in the crystal grain boundaries 101 and their vicinity.

[0252] In this specification and the like, uneven distribution refers to the concentration of an element in a certain region being different from that in other regions, and is synonymous with segregation, precipitation, non-uniformity, bias, or the presence of a mixture of areas with high concentration and areas with low concentration.

[0253] For example, it is preferable that the magnesium concentration at and near the grain boundaries 101 of the positive electrode active material 100 is higher than that in other regions of the interior 100b. It is also preferable that the fluorine concentration at and near the grain boundaries 101 is higher than that in other regions of the interior 100b. It is also preferable that the nickel concentration at and near the grain boundaries 101 is higher than that in other regions of the interior 100b. It is also preferable that the aluminum concentration at and near the grain boundaries 101 is higher than that in other regions of the interior 100b.

[0254] The grain boundary 101 is one of the planar defects. Therefore, like the grain surface, it is easily unstable and the crystal structure is likely to change. Therefore, if the concentration of the added element at and near the grain boundary 101 is high, the change in the crystal structure can be more effectively suppressed.

[0255] Furthermore, when the magnesium concentration and fluorine concentration are high at and near the grain boundaries 101, even if cracks occur along the grain boundaries 101 of the positive electrode active material 100 of one embodiment of the present invention, the magnesium concentration and fluorine concentration are high near the surface where the cracks occur. Therefore, the corrosion resistance to hydrofluoric acid can be improved even in the positive electrode active material after the cracks occur.

[0256] <Particle size> If the particle size of the positive electrode active material 100 of one embodiment of the present invention is too large, there are problems such as difficulty in diffusing lithium, and the surface of the active material layer becomes too rough when applied to a current collector. On the other hand, if the particle size is too small, there are problems such as difficulty in supporting the active material layer when applied to a current collector, and excessive reaction with an electrolyte. Therefore, the median diameter (D50) is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less. Alternatively, 1 μm or more and 40 μm or less is preferable. Alternatively, 1 μm or more and 30 μm or less is preferable. Alternatively, 2 μm or more and 100 μm or less is preferable. Alternatively, 2 μm or more and 30 μm or less is preferable. Alternatively, 5 μm or more and 100 μm or less is preferable. Alternatively, 5 μm or more and 40 μm or less is preferable.

[0257] <Analysis method> A certain positive electrode active material is Li x Chief of Staff 2 When x in the formula (I) is small, whether the positive electrode active material 100 according to one embodiment of the present invention has an O3′ type and / or a monoclinic O1(15) type crystal structure can be determined by the following formula (I): x Chief of Staff 2 This can be determined by analyzing a positive electrode having a positive electrode active material with a small x using XRD, electron beam diffraction, neutron beam diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), or the like.

[0258] In particular, XRD is preferred in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, can compare the degree of crystallinity and the orientation of the crystals, can analyze the periodic distortion of the lattice and the crystallite size, can obtain sufficient accuracy even when the positive electrode obtained by disassembling the secondary battery is measured as it is, etc. Among XRD, powder XRD can obtain diffraction peaks that reflect the crystal structure of the inside 100b of the positive electrode active material 100, which occupies most of the volume of the positive electrode active material 100.

[0259] When analyzing the crystallite size by powder XRD, it is preferable to perform the measurement while excluding the influence of orientation due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling a secondary battery, prepare a powder sample, and then perform the measurement.

[0260] As described above, the positive electrode active material 100 according to one embodiment of the present invention is Li x Chief of Staff 2 It is characterized by the fact that there is little change in the crystal structure when x is 1 and when it is 0.24 or less. When charged at high voltage, materials in which the crystal structure that undergoes large changes accounts for 50% or more of the crystal structure are not desirable because they cannot withstand high-voltage charging and discharging.

[0261] It should also be noted that the addition of an additive element alone may not result in an O3' or monoclinic O1(15) crystal structure. For example, even if lithium cobalt oxide with magnesium and fluorine or lithium cobalt oxide with magnesium and aluminum has something in common, depending on the concentration and distribution of the additive element, Li x Chief of Staff 2 In some cases, x is 0.24 or less and the O3' and / or monoclinic O1(15) crystal structures account for 60% or more, and in other cases, the H1-3 crystal structure accounts for 50% or more.

[0262] Furthermore, even in the positive electrode active material 100 of one embodiment of the present invention, an H1-3 type or trigonal O1 type crystal structure may be generated when x is too small, such as 0.1 or less, or under conditions where the charging voltage exceeds 4.9 V. Therefore, in order to determine whether or not the positive electrode active material 100 of one embodiment of the present invention is a material, analysis of the crystal structure, such as XRD, and information on the charging capacity or charging voltage, etc. are required.

[0263] However, when the positive electrode active material has a small x, its crystal structure may change when it is exposed to air. For example, the crystal structure may change from O3' type or monoclinic O1(15) type to H1-3 type. Therefore, it is preferable to handle all samples used for crystal structure analysis in an inert atmosphere such as an argon atmosphere.

[0264] Furthermore, whether or not the distribution of the additive elements in a certain positive electrode active material is in the state described above can be determined by analyzing it using, for example, XPS, energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.

[0265] The crystal structure of surface layer 100a, crystal grain boundaries 101, etc. can be analyzed by electron beam diffraction of a cross section of positive electrode active material 100, etc.

[0266] ≪Charging method≫ For example, charging for determining whether a certain complex oxide is the positive electrode active material 100 of one embodiment of the present invention can be performed by preparing a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) with a lithium counter electrode and charging the coin cell.

[0267] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive material, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.

[0268] Lithium metal can be used for the counter electrode. When a material other than lithium metal is used for the counter electrode, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification are the potential of the positive electrode.

[0269] The electrolyte contained 1 mol / L lithium hexafluorophosphate (LiPF 6 ) is used, and the electrolyte can be a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of 3:7 with 2 wt% vinylene carbonate (VC).

[0270] The separator can be a 25 μm thick porous polypropylene film.

[0271] The positive electrode can and the negative electrode can may be made of stainless steel (SUS).

[0272] The coin cell prepared under the above conditions is charged at an arbitrary voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). The charging method is not particularly limited as long as the charging can be performed at an arbitrary voltage for a sufficient time. For example, when charging by CCCV, the current in CC charging can be 20mA / g or more and 100mA / g or less. CV charging can be completed at 2mA / g or more and 10mA / g or less. In order to observe the phase change of the positive electrode active material, it is desirable to charge at such a small current value. The temperature is 25°C or 45°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, and a positive electrode active material with an arbitrary charge capacity can be obtained. When various analyses are performed after this, it is preferable to seal it in an argon atmosphere in order to suppress reactions with external components. For example, XRD can be performed by sealing it in a sealed container in an argon atmosphere. In addition, it is preferable to quickly take out the positive electrode after charging is completed and provide it for analysis. Specifically, it is preferable to do so within one hour after the completion of charging, and more preferably within 30 minutes.

[0273] In addition, when analyzing the crystal structure in the charged state after multiple charge / discharge cycles, the multiple charge / discharge conditions may be different from the above-mentioned charging conditions. For example, charging can be performed by constant current charging at a current value of 20 mA / g to 100 mA / g up to an arbitrary voltage (e.g., 4.6 V, 4.65 V, 4.7 V, 4.75 V, or 4.8 V), followed by constant voltage charging until the current value becomes 2 mA / g to 10 mA / g, and discharging can be performed by constant current discharging at 2.5 V and 20 mA / g to 100 mA / g.

[0274] Furthermore, when analyzing the crystal structure in the discharged state after multiple charge / discharge cycles, constant current discharge can be performed at, for example, 2.5 V and a current value of 20 mA / g or more and 100 mA / g or less.

[0275] <XRD> The XRD measurement apparatus and conditions are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. XRD equipment: Bruker AXS, D8 ADVANCE X-ray source:Cu Output: 40kV, 40mA Divergence angle: Div.Slit, 0.5° Detector: LynxEye Scan method: 2θ / θ continuous scan Measurement range (2θ): 15° to 90° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm The obtained XRD patterns were analyzed using the analysis software DIFFRAC.EVA to determine the background and CuKα 2 It is preferable to remove the line peaks.

[0276] If the measurement sample is a powder, it can be set by placing it in a glass sample holder, sprinkling the sample on a greased silicone non-reflective plate, etc. If the measurement sample is a positive electrode, the positive electrode can be attached to the substrate with double-sided tape, and the positive electrode active material layer can be set to match the measurement surface required by the device.

[0277] The CuKα structure calculated from the crystal structure of the O3' type, the monoclinic O1(15) type, and the H1-3 type crystal structure model. 1 The ideal powder XRD patterns of the Li line are shown in Figs. 13, 14, 15(A) and 15(B). x Chief of Staff 2 LiCoO with x=1 2 The ideal XRD patterns calculated from the crystal structure of O3 and trigonal O1 with x = 0 are also shown. Figures 15(A) and 15(B) show the XRD patterns of the O3' type crystal structure, the monoclinic O1(15) type crystal structure, and the H1-3 type crystal structure. Figure 15(A) shows an enlarged view of the region where 2θ is between 18° and 21°, and Figure 15(B) shows an enlarged view of the region where 2θ is between 42° and 46°. Note that LiCoO 2 (O3) and CoO 2 The pattern of (O1) was created using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA), from crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 4). The 2θ range was set to 15° to 75°, with a step size of 0.01 and a wavelength of λ1 of 1.540562×10 -10 m and λ2 were not set, and monochromator was set to single. The pattern of the H1-3 type crystal structure was similarly created from the crystal structure information described in Non-Patent Document 3. The patterns of the O3' type and monoclinic O1(15) type crystal structures were estimated from the XRD pattern of the positive electrode active material of one embodiment of the present invention, and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and XRD patterns were created in the same manner as the others.

[0278] As shown in Figures 13, 15(A) and 15(B), in the O3' type crystal structure, diffraction peaks appear at 2θ = 19.25 ± 0.12° (19.13° or more and less than 19.37°) and 2θ = 45.47 ± 0.10° (45.37° or more and less than 45.57°).

[0279] In addition, in the monoclinic O1(15) crystal structure, diffraction peaks appear at 2θ = 19.47 ± 0.10° (19.37° to 19.57°) and 2θ = 45.62 ± 0.05° (45.57° to 45.67°).

[0280] However, as shown in Figures 14, 15(A) and 15(B), no peaks appear at these positions in the H1-3 type crystal structure and trigonal O1. x Chief of Staff 2 The appearance of peaks at 19.13° or more and less than 19.37° and / or 19.37° or more and 19.57° or less, and at least 45.37° or more and less than 45.57° and / or at least 45.57° or more and 45.67° or less when x is small can be said to be a characteristic of the positive electrode active material 100 of one embodiment of the present invention.

[0281] This can also be said to be because the positions at which XRD diffraction peaks appear are close between the crystal structures of x = 1 and x ≦ 0.24. More specifically, for the main diffraction peaks of the crystal structures of x = 1 and x ≦ 0.24 that appear at 2θ between 42° and 46°, the difference in 2θ is 0.7° or less, more preferably 0.5° or less.

[0282] The positive electrode active material 100 according to one embodiment of the present invention is Li x Chief of Staff 2When x in the formula is small, the particles have an O3'-type and / or monoclinic O1(15)-type crystal structure, but not all of the particles may have an O3'-type and / or monoclinic O1(15)-type crystal structure. They may contain other crystal structures, or may be partially amorphous. However, when the XRD pattern is subjected to Rietveld analysis, the O3'-type and / or monoclinic O1(15)-type crystal structure is preferably 50% or more, more preferably 60% or more, and even more preferably 66% or more. If the O3'-type and / or monoclinic O1(15)-type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more, the positive electrode active material can have sufficiently excellent cycle characteristics.

[0283] Furthermore, even after 100 or more charge / discharge cycles from the start of measurement, when Rietveld analysis is performed, the O3' type and / or monoclinic O1(15) type crystal structure is preferably 35% or more, more preferably 40% or more, and even more preferably 43% or more.

[0284] Similarly, when Rietveld analysis is performed, it is preferable that the H1-3 type and O1 type crystal structures account for 50% or less.

[0285] The sharpness of the diffraction peaks in the XRD pattern indicates the high crystallinity. Therefore, it is preferable that each diffraction peak after charging is sharp, that is, the half-width, for example, the full width at half maximum is narrow. The half-width varies depending on the XRD measurement conditions and the value of 2θ, even for peaks generated from the same crystal phase. In the case of the above-mentioned measurement conditions, the full width at half maximum is preferably, for example, 0.2° or less, more preferably 0.15° or less, and even more preferably 0.12° or less, in peaks observed at 2θ=43° or more and 46° or less. It is not necessary for all peaks to meet this requirement. If some peaks meet this requirement, it can be said that the crystallinity of the crystal phase is high. Such high crystallinity contributes to the stabilization of the crystal structure after charging sufficiently.

[0286] In addition, the crystallite size of the O3' type and monoclinic O1(15) crystal structures of the positive electrode active material 100 is approximately equal to that of LiCoO 2 Therefore, even if the XRD measurement conditions were the same as for the positive electrode before and after charging and discharging, the Li x Chief of Staff 2 When x in the LiCoO phase is small, the peaks of the O3' and / or monoclinic O1(15) crystal structures are clearly observed. 2 In the case of 15, even if some of the crystal structures resemble those of O3' and / or monoclinic O1(15), the crystallite size is small and the peaks are broad and small. The crystallite size can be determined from the half-width of the XRD peak.

[0287] In the positive electrode active material 100 according to one embodiment of the present invention, as described above, it is preferable that the influence of the Jahn-Teller effect is small. As long as the influence of the Jahn-Teller effect is small, a transition metal such as nickel or manganese may be contained as an additive element in addition to cobalt.

[0288] <XPS> In X-ray photoelectron spectroscopy (XPS), in the case of inorganic oxides, when monochromatic aluminum Kα rays are used as the X-ray source, it is possible to analyze a region from the surface to a depth of about 2 to 8 nm (usually 5 nm or less), so the concentration of each element can be quantitatively analyzed in a region about half the depth of the surface layer 100a. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is often about ±1 atomic %, and the lower detection limit is about 1 atomic %, depending on the element.

[0289] In the positive electrode active material 100 according to one embodiment of the present invention, the concentration of one or more selected from the additive elements is preferably higher in the surface layer portion 100a than in the interior portion 100b. This is synonymous with the fact that the concentration of one or more selected from the additive elements in the surface layer portion 100a is preferably higher than the average concentration of the entire positive electrode active material 100. Therefore, for example, it can be said that the concentration of one or more additive elements selected from the surface layer portion 100a measured by XPS or the like is preferably higher than the average concentration of the additive elements in the entire positive electrode active material 100 measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry). For example, it is preferable that the magnesium concentration of at least a part of the surface layer portion 100a measured by XPS or the like is higher than the magnesium concentration of the entire positive electrode active material 100. It is also preferable that the nickel concentration of at least a part of the surface layer portion 100a is higher than the nickel concentration of the entire positive electrode active material 100. It is also preferable that the aluminum concentration in at least a part of the surface layer 100a is higher than the aluminum concentration in the entire positive electrode active material 100. It is also preferable that the fluorine concentration in at least a part of the surface layer 100a is higher than the fluorine concentration in the entire positive electrode active material 100.

[0290] In addition, in at least a part of the surface layer 100a measured by XPS, it is preferable that a bond between magnesium and fluorine exists, and it is even more preferable that a bond between magnesium and fluorine and oxygen exists (O-Mg-F bond). These bonds in the surface layer 100a are one of the factors indicating that the flux effect of the fluoride is fully exerted, the surface of the additive element source and lithium cobalt oxide is melted, and magnesium is sufficiently segregated. Therefore, it is suggested that the additive element is distributed uniformly and in a sufficient amount in the surface layer 100a.

[0291] 16(A) and 16(B) show an example of the analysis result of a positive electrode active material having bonds of magnesium, fluorine, and oxygen in the surface layer portion 100a. 3 O 4 , Li as a lithium source 2 CO 3The material was prepared by mixing LiF and MgO as the additive element sources, heating them in a dry air atmosphere at 1000°C for 10 hours, cooling, and then further heating them in a dry air atmosphere at 800°C for 2 hours.

[0292] The excitation X-rays used in the XPS measurements were monochromatic Al, and the detection area was 100 μmφ. The take-off angle (the angle between the inclination of the sample stage and the detection direction of the detector) was 45° or 15°. The detection depth at a take-off angle of 45° was approximately 4 to 5 nm, and at a take-off angle of 15° the detection depth was approximately 2 nm. The correction standards were Mg1s and C1s.

[0293] Regarding the obtained XPS spectrum of Mg1s, if an O-Mg-F bond exists, the bond energy of the Mg is MgO and MgF 2 Waveform separation was performed assuming that the peak was somewhere between these two. Figure 16(A) shows the results of waveform separation for Mg1s when the take-off angle was 45°, and Figure 16(B) shows the results of waveform separation for Mg1s when the take-off angle was 15°. In both cases, the solid line (DATA) shows the actual measured value, and the white line with a black border (SUM) shows the spectrum after smoothing the actual measured value. The dashed line for Mg1 shows the waveform-separated MgO, that is, the bond between magnesium and oxygen. The dashed line for Mg2 shows the waveform-separated O-Mg-F bond. The lower detection limit for Mg2 (O-Mg-F bond) is approximately 10%, and the waveform analysis result error is approximately ±2%.

[0294] In Figure 16(A), Mg1 (magnesium-oxygen bond) was 75.1% and Mg2 (O-Mg-F bond) was 24.9%. In Figure 16(B), Mg1 (magnesium-oxygen bond) was 80.4% and Mg2 (O-Mg-F bond) was 19.6%.

[0295] As described above, Mg2 (O-Mg-F bond) was confirmed at both take-off angles of 45° and 15°. In addition, because the ratio of Mg2 (O-Mg-F bond) was higher at the surface-sensitive take-off angle of 15°, it was believed that Mg2 (O-Mg-F bond) was mainly present in a very shallow region up to 2 nm from the surface.

[0296] The surface and surface layer 100a of the positive electrode active material 100 according to one embodiment of the present invention do not include carbonates, hydroxyl groups, etc. that are chemically adsorbed after the preparation of the positive electrode active material 100. Also, the electrolyte, binder, conductive material, or compounds derived from these that are attached to the surface of the positive electrode active material 100 are not included. Therefore, when quantifying the elements contained in the positive electrode active material, correction may be made to exclude carbon, hydrogen, excess oxygen, excess fluorine, etc. that can be detected by surface analysis such as XPS. For example, XPS allows the type of bond to be separated by analysis, and correction may be made to exclude C-F bonds derived from the binder.

[0297] Furthermore, before being subjected to various analyses, the sample such as the positive electrode active material and the positive electrode active material layer may be washed in order to remove the electrolyte, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material. At this time, lithium may dissolve in the solvent used for washing, but even in this case, the added element is unlikely to dissolve, and therefore the atomic ratio of the added element is not affected.

[0298] The concentration of the added element may be compared in terms of the ratio to cobalt. By using the ratio to cobalt, the influence of carbonates and the like chemically adsorbed after the preparation of the positive electrode active material can be reduced and comparison is preferably made. For example, the ratio of the number of magnesium atoms to the number of cobalt atoms, Mg / Co, as determined by XPS analysis, is preferably 0.4 to 1.5. On the other hand, the ratio of Mg / Co as determined by ICP-MS analysis is preferably 0.001 to 0.06.

[0299] Similarly, in the positive electrode active material 100, in order to secure a sufficient path for the insertion and desorption of lithium, it is preferable that the concentrations of lithium and cobalt in the surface layer portion 100a are higher than the concentrations of one or more additive elements selected from the additive elements contained in the surface layer portion 100a measured by XPS or the like. For example, it is preferable that the concentration of at least a part of cobalt in the surface layer portion 100a measured by XPS or the like is higher than the concentration of magnesium in at least a part of the surface layer portion 100a measured by XPS or the like. Similarly, it is preferable that the concentration of lithium is higher than the concentration of magnesium. It is also preferable that the concentration of cobalt is higher than the concentration of nickel. It is also preferable that the concentration of lithium is higher than the concentration of nickel. It is also preferable that the concentration of cobalt is higher than the concentration of aluminum. It is also preferable that the concentration of lithium is higher than the concentration of aluminum. It is also preferable that the concentration of cobalt is higher than the concentration of fluorine. It is also preferable that the concentration of lithium is higher than the concentration of fluorine.

[0300] Furthermore, it is more preferable that the additive element Y, such as aluminum, is widely distributed in a deep region, for example, a region having a depth from the surface of 5 nm to 50 nm. Therefore, although the additive element Y, such as aluminum, is detected in the analysis of the entire positive electrode active material 100 using ICP-MS, GD-MS, etc., it is more preferable that the concentration of the additive element Y is below the lower detection limit in XPS, etc.

[0301] Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is subjected to XPS analysis, the number of magnesium atoms is preferably 0.4 times or more and 1.2 times or less, more preferably 0.65 times or more and 1.0 times or less, relative to the number of cobalt atoms. The number of nickel atoms is preferably 0.15 times or less, more preferably 0.03 times or more and 0.13 times or less, relative to the number of cobalt atoms. The number of aluminum atoms is preferably 0.12 times or less, more preferably 0.09 times or less, relative to the number of cobalt atoms. The number of fluorine atoms is preferably 0.3 times or more and 0.9 times or less, more preferably 0.1 times or more and 1.1 times or less, relative to the number of cobalt atoms. The above ranges indicate that these additive elements are not attached to a narrow range on the surface of the positive electrode active material 100, but are widely distributed in a preferred concentration in the surface layer portion 100a of the positive electrode active material 100.

[0302] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, the peak showing the bond energy between fluorine and other elements is preferably 682 eV or more and less than 685 eV, and more preferably about 684.3 eV. This value is different from both the bond energy of lithium fluoride, 685 eV, and the bond energy of magnesium fluoride, 686 eV. In other words, when the positive electrode active material 100 of one embodiment of the present invention contains fluorine, the bond is preferably other than that of lithium fluoride and magnesium fluoride.

[0303] Furthermore, when the positive electrode active material 100 of one embodiment of the present invention is subjected to XPS analysis, the peak showing the bond energy between magnesium and another element is preferably equal to or greater than 1302 eV and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bond energy of magnesium fluoride, 1305 eV, and is close to the bond energy of magnesium oxide. In other words, when the positive electrode active material 100 of one embodiment of the present invention contains magnesium, the bond is preferably other than that of magnesium fluoride.

[0304] <Valence of transition metal M> The transition metal M preferably has a different valence between the surface layer portion 100a and the interior portion 100b. More specifically, the transition metal M in the interior portion 100b preferably has more trivalent atoms than atoms with other valences, and the transition metal M in the surface layer portion 100a preferably has more divalent atoms than atoms with other valences.

[0305] If the surface layer 100a contains a large amount of divalent transition metals, the surface layer 100a contains a large amount of metal oxides with a transition metal:oxygen ratio of 1:1 (atomic ratio), such as CoO(II), MnO(II), and Ni(II). These metal oxides tend to form stable solid solutions with magnesium oxide, which is also an oxide of a divalent metal. This allows the surface layer 100a to become a more stable and excellent coating layer.

[0306] The valence of the transition metal can be analyzed by EELS (electron energy loss spectroscopy), XAFS (X-ray absorption fine structure analysis), XPS (X-ray photoelectron spectroscopy), ESR (electron spin resonance), Mössbauer spectroscopy, etc. Among them, EELS is preferable because it has high spatial resolution and can analyze even a thin layer of the surface layer 100a of several nm.

[0307] When analyzing the valence of a transition metal M by EELS, the valence is L 3 / L 2 It can be judged by the ratio of L 3 / L 2 For example, when cobalt in the surface layer 100a and the inner layer 100b is analyzed by EELS, the L of cobalt in the inner layer 100b is 3 / L 2 is less than 3.8, and the cobalt contained in the surface layer portion 100a is L 3 / L 2 is preferably 3.8 or more.

[0308] <EDX> It is preferable that one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient. It is more preferable that the depth from the surface of the concentration peak differs depending on the additive element in the positive electrode active material 100. The concentration gradient of the additive element can be evaluated, for example, by exposing a cross section of the positive electrode active material 100 using a focused ion beam (FIB) or the like and analyzing the cross section using energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.

[0309] Among EDX measurements, EDX area analysis is performed by scanning an area and evaluating the area in two dimensions. EDX line analysis is performed by scanning a line and evaluating the distribution of atomic concentration within the positive electrode active material. Line analysis may also be used to extract data from a linear area of ​​EDX area analysis. Point analysis is used to measure an area without scanning it.

[0310] By EDX surface analysis (e.g., element mapping), the concentration of the added element can be quantitatively analyzed in the surface layer 100a, the inside 100b, and the vicinity of the grain boundary 101 of the positive electrode active material 100. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. Furthermore, analysis of thinning the sample such as STEM-EDX is more preferable because it can analyze the concentration distribution in the depth direction from the surface to the center of the positive electrode active material in a specific region without being affected by the distribution in the depth direction.

[0311] Therefore, when EDX areal analysis or EDX point analysis is performed on positive electrode active material 100 of one embodiment of the present invention, it is preferable that the concentration of each additional element, particularly additional element X, in surface layer portion 100a is higher than that in interior portion 100b.

[0312] For example, when EDX surface analysis or EDX point analysis is performed on a positive electrode active material 100 having magnesium as an additive element, the magnesium concentration in the surface layer 100a is preferably higher than the magnesium concentration in the interior 100b. When EDX line analysis is performed, the peak of the magnesium concentration in the surface layer 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. The magnesium concentration is preferably attenuated to 60% or less of the peak at a point 1 nm deep from the peak top. It is also preferable that the magnesium concentration is attenuated to 30% or less of the peak at a point 2 nm deep from the peak top. The peak of concentration here refers to the maximum value of the concentration.

[0313] In the positive electrode active material 100 having magnesium and fluorine as additive elements, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the peak of the fluorine concentration and the peak of the magnesium concentration is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.

[0314] In addition, when EDX analysis is performed, the fluorine concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Furthermore, if the fluorine concentration peak is slightly closer to the surface than the magnesium concentration peak, resistance to hydrofluoric acid is increased, which is more preferable. For example, the fluorine concentration peak is more preferably 0.5 nm or more closer to the surface than the magnesium concentration peak, and even more preferably 1.5 nm or more closer to the surface.

[0315] In the positive electrode active material 100 having nickel as an additive element, the nickel concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. In the positive electrode active material 100 having magnesium and nickel, the nickel distribution is preferably superimposed on the magnesium distribution. For example, the difference in the depth direction between the nickel concentration peak and the magnesium concentration peak is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.

[0316] Furthermore, when the positive electrode active material 100 contains aluminum as an added element, it is preferable that the peak of the magnesium, nickel, or fluorine concentration is closer to the surface than the peak of the aluminum concentration in the surface layer portion 100a when EDX analysis is performed. For example, the peak of the aluminum concentration is preferably present at a depth of 0.5 nm to 50 nm from the surface to the center of the positive electrode active material 100, and more preferably at a depth of 5 nm to 50 nm.

[0317] In addition, when EDX line analysis, surface analysis, or point analysis is performed on the positive electrode active material 100, the ratio of the number of atoms of magnesium Mg and cobalt Co (Mg / Co) at the peak of magnesium concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.4. The ratio of the number of atoms of aluminum Al and cobalt Co (Al / Co) at the peak of aluminum concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.45. The ratio of the number of atoms of nickel Ni and cobalt Co (Ni / Co) at the peak of nickel concentration is preferably 0 to 0.2, more preferably 0.01 to 0.1. The ratio of the number of atoms of fluorine F and cobalt Co (F / Co) at the peak of fluorine concentration is preferably 0 to 1.6, more preferably 0.1 to 1.4.

[0318] The surface of the positive electrode active material 100 in the EDX analysis results can be estimated, for example, as follows: For an element that is uniformly present in the interior 100b of the positive electrode active material 100, such as oxygen or cobalt, the point where the amount detected in the interior 100b is half that of the interior 100b is defined as the surface.

[0319] Since the positive electrode active material 100 is a composite oxide, the surface can be estimated using the amount of detected oxygen. Specifically, first, the average oxygen concentration O ave At this time, oxygen O, which is thought to be due to chemical adsorption or background, is found in the area that is clearly outside the surface. bg If O is detected, the measurement bg The average oxygen concentration is calculated by subtracting ave This average value O ave That is, 1 / 2O ave The measurement point showing the measurement value closest to the above can be estimated to be the surface of the positive electrode active material.

[0320] The surface can also be estimated in the same manner as above using the amount of cobalt detected. Alternatively, the sum of the amounts of multiple transition metals detected can be used to estimate the surface. The amount of transition metals detected, including cobalt, is less susceptible to the effects of chemical adsorption, making it suitable for estimating the surface.

[0321] Furthermore, when the positive electrode active material 100 is subjected to a line analysis or an area analysis, the ratio of the number of atoms of the additive element A to the cobalt Co in the vicinity of the crystal grain boundary 101 (A / Co) is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Still more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 0.020 or more and 0.30 or less. Or it is preferably 0.020 or more and 0.20 or less. Or it is preferably 0.025 or more and 0.50 or less. Or it is preferably 0.025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less.

[0322] For example, when the added element is magnesium, when the positive electrode active material 100 is subjected to a line analysis or area analysis, the ratio of the number of magnesium atoms to the number of cobalt atoms (Mg / Co) in the vicinity of the crystal grain boundary 101 is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Still more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 0.020 or more and 0.30 or less. Or it is preferably 0.020 or more and 0.20 or less. Or it is preferably 0.025 or more and 0.50 or less. Or it is preferably 0.025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less. Furthermore, when the above-mentioned range is present in multiple locations, for example, three or more locations, of the positive electrode active material 100, this indicates that the added element is not attached to a narrow area on the surface of the positive electrode active material 100, but is widely distributed at a preferred concentration in the surface layer portion 100a of the positive electrode active material 100.

[0323] EPMA EPMA (Electron Probe Microanalysis) can also quantify elements. Area analysis can analyze the distribution of each element.

[0324] When the cross section of the positive electrode active material 100 according to one embodiment of the present invention is subjected to EPMA surface analysis, it is preferable that one or more selected from the additive elements have a concentration gradient, as in the EDX analysis results. It is more preferable that the depth of the concentration peak from the surface differs depending on the additive element. The preferable range of the concentration peak of each additive element is also the same as in the case of EDX.

[0325] However, EPMA analyzes the region from the surface to a depth of about 1 μm. Therefore, the quantitative values ​​of each element may differ from the measurement results obtained by other analytical methods. For example, when the surface analysis of the positive electrode active material 100 is performed by EPMA, the concentration of each added element present in the surface layer 100a may be lower than the result of XPS.

[0326] <Charging curve and dQ / dVvsV curve> The positive electrode active material 100 according to one embodiment of the present invention may exhibit a characteristic voltage change during charging. The voltage change can be read from a dQ / dVvsV curve obtained by differentiating (dQ / dV) the capacity (Q) of the charging curve with respect to the voltage (V). For example, it is considered that a non-equilibrium phase change occurs around the peak in the dQ / dVvsV curve, and the crystal structure changes significantly. In this specification and the like, a non-equilibrium phase change refers to a phenomenon that causes a non-linear change in a physical quantity.

[0327] The positive electrode active material 100 according to one embodiment of the present invention may have a broad peak near 4.55 V in the dQ / dV vs. V curve. The peak near 4.55 V reflects the change in voltage that occurs when the phase changes from the O3 type crystal structure to the O3' type crystal structure. Therefore, the broadness of this peak means that there is less change in the energy required to extract lithium, i.e., there is less change in the crystal structure, compared to when the peak is sharp. The smaller these changes are, the greater the amount of CoO 2 This is preferable since it is less susceptible to layer shift and volume change.

[0328] More specifically, when the maximum value appearing between 4.5 V and 4.6 V in the dQ / dV vs. V curve of the charging curve is taken as the first peak, it can be said that the full width at half maximum of the first peak is sufficiently broad and is preferable if it is 0.10 V or more. In this specification and the like, the full width at half maximum of the first peak is defined as the average value HWHM of the first peak and the first minimum value when the minimum value of the dQ / dV value appearing between 4.3 V and 4.5 V is taken as the first minimum value. 1 and the average value HWHM between the first peak and the second minimum when the minimum value of the dQ / dV value appearing between 4.6 V and 4.8 V is set as the second minimum value. 2 The difference between and.

[0329] The charging for obtaining the dQ / dV vs. V curve can be, for example, a constant current charge of 10 mA / g up to 4.9 V. When obtaining the dQ / dV of the initial charge, it is preferable to start the above charging after discharging to 2.5 V at 20 mA / g or more and 100 mA / g or less before the measurement.

[0330] The data acquisition interval during charging can be set to acquire the voltage and current at 1 second intervals or when there is a voltage fluctuation of 1 mV. The charge capacity is the product of the current value and time.

[0331] The difference between the nth and (n+1)th data of the charge capacity is defined as the nth value of the capacity change dQ. Similarly, the difference between the nth and (n+1)th data of the voltage is defined as the nth value of the voltage change dV.

[0332] However, since the above data is subject to the influence of minute noise, the dQ / dV value may be calculated from the moving average of the voltage and charge capacity differences over a certain number of intervals. The number of intervals may be set to, for example, 500.

[0333] Specifically, the average value of dQ from the nth to the n+500th is calculated, and similarly the average value of dV from the nth to the n+500th is calculated. dQ (average of 500) / dV (average of 500) can be used as the dQ / dV value. Similarly, the moving average value of 500 sections can be used for the voltage on the horizontal axis in the dQ / dVvsV graph. Note that when using a moving average of 500 sections as described above, it is preferable not to use the data from the 501st data from the end to the last data in the dQ / dVvsV graph because the data is heavily influenced by noise.

[0334] In addition, when analyzing the dQ / dV vs. V curve after multiple charge / discharge cycles, the multiple charge / discharge conditions may be different from the above-mentioned charging conditions. For example, charging may be performed at any voltage (e.g., 4.6V, 4.65V, 4.7V, 4.75V, or 4.8V) at a constant current of 20-100mA / g, followed by constant voltage charging until the current value becomes 2mA / g-10mA / g, and discharging at 2.5V at a constant current of 20-100mA / g.

[0335] At around 4.55 V, the phase changes from the O3 type crystal structure to the O3' type crystal structure.x Chief of Staff 2 The x in the figure is about 0.3. This has the same symmetry as the O3 type crystal structure with x=1 explained in Figure 10, but the CoO 2 The distance between layers is slightly different. In this specification, when distinguishing between O3 type crystal structures with different values ​​of x, the O3 type crystal structure with x = 1 is called O3 (2θ = 18.85), and the O3 type crystal structure with x = 0.3 is called O3 (2θ = 18.57). This is because the position of the peak that appears at 2θ of about 19° in XRD measurement is the same as that of CoO 2 This is to correspond to the interlayer distance.

[0336] <Discharge curve and dQ / dVvsV curve> Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is charged at a high voltage and then discharged at a low current of, for example, 40 mA / g or less, a characteristic voltage change may appear near the end of discharge. This change can be clearly confirmed by the presence of at least one peak in the range of voltages up to 3.5 V, lower than the peak that appears around 3.9 V, in the dQ / dV vs. V curve obtained from the discharge curve.

[0337] <ESR> The positive electrode active material 100 of one embodiment of the present invention preferably contains cobalt and nickel and magnesium as additional elements. 3+ Ni 3+ and some Li + Mg 2+ It is preferable that Li is substituted with Li. + Mg 2+ With the replacement of Ni 3+ is reduced to Ni 2+ In addition, some Li + Mg 2+ and with that, Mg 2+ Nearby Co 3+ is reduced to Co 2+ In addition, some Co 3+ Mg 2+ and with that, Mg 2+ Nearby Co 3+is oxidized to Co 4+ This may be the case.

[0338] Therefore, the positive electrode active material 100 is Ni 2+ , Ni 3+ , Co 2+ and Co 4+ It is preferable that the positive electrode active material has at least one of the following: 2+ , Ni 3+ , Co 2+ and Co 4+ The spin density due to one or more of the following is 2.0×10 17 spins / g or more 1.0×10 21 It is preferable that the positive electrode active material 100 has the above-mentioned spin density, because the crystal structure is stable, particularly in the charged state. If the magnesium concentration is too high, the Ni 2+ , Ni 3+ , Co 2+ and Co 4+ The spin density may be reduced due to one or more of the above.

[0339] The spin density in the positive electrode active material can be analyzed, for example, by using an electron spin resonance (ESR) method.

[0340] <Surface roughness and specific surface area> The positive electrode active material 100 according to one embodiment of the present invention preferably has a smooth surface with few irregularities. A smooth surface with few irregularities indicates that the effect of the flux described below is sufficiently exerted and the surfaces of the additive element source and the lithium cobalt oxide are melted. Therefore, this is one factor indicating that the distribution of the additive element in the surface layer portion 100a is good.

[0341] Whether the surface is smooth and has few projections and recesses can be determined, for example, from a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material 100, the specific surface area of ​​the positive electrode active material 100, or the like.

[0342] For example, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 as follows.

[0343] First, the cathode active material 100 is processed by FIB or the like to expose the cross section. At this time, it is preferable to cover the cathode active material 100 with a protective film, a protective agent, or the like. Next, an SEM image of the interface between the protective film or the like and the cathode active material 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, Gaussian blurring (σ=2) is performed, and then binarization is performed. Furthermore, interface extraction is performed using image processing software. Furthermore, the interface line between the protective film or the like and the cathode active material 100 is selected using an automatic selection tool or the like, and data is extracted to a spreadsheet software or the like. Using the functions of the spreadsheet software or the like, correction is performed from a regression curve (quadratic regression), and a parameter for calculating roughness is obtained from the data after the slope correction, and the root mean square surface roughness (RMS) is calculated by calculating the standard deviation. In addition, this surface roughness is the surface roughness at least at 400 nm of the outer periphery of the particle of the cathode active material.

[0344] The particle surfaces of the positive electrode active material 100 of this embodiment preferably have a root mean square (RMS) surface roughness, which is an index of roughness, of less than 3 nm, preferably less than 1 nm, and more preferably less than 0.5 nm.

[0345] The image processing software for noise processing, interface extraction, etc. is not particularly limited, but for example, "ImageJ" described in Non-Patent Documents 6 to 8 can be used. The spreadsheet software is also not particularly limited, but for example, Microsoft Office Excel can be used.

[0346] For example, the actual specific surface area S measured by the constant volume gas adsorption method R and the ideal specific surface area S i The smoothness of the surface of the positive electrode active material 100 can also be expressed as a numerical value based on the ratio of the surface smoothness to the surface smoothness.

[0347] Ideal specific surface area S iis calculated assuming that all particles have the same diameter, the same weight, and an ideal spherical shape.

[0348] The median diameter D50 can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a gas adsorption method by a constant volume method, for example.

[0349] The positive electrode active material 100 according to one embodiment of the present invention has an ideal specific surface area S calculated from the median diameter D50. i and the actual specific surface area S R Ratio of S R / S i It is preferable that the ratio is 2.1 or less.

[0350] Alternatively, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 by the following method.

[0351] First, a surface SEM image of the positive electrode active material 100 is obtained. At this time, a conductive coating may be applied as a pretreatment for observation. The observation surface is preferably perpendicular to the electron beam. When comparing multiple samples, the measurement conditions and observation area are the same.

[0352] Next, using image processing software (such as "ImageJ"), the above SEM image is converted to, for example, an 8-bit image (called a grayscale image). Grayscale images contain luminance (brightness information). For example, in an 8-bit grayscale image, luminance can be expressed as 2 to the power of 8 = 256 gradations. Dark areas have lower gradations, and bright areas have higher gradations. The change in luminance can be quantified in relation to the number of gradations. This number is called the grayscale value. Obtaining the grayscale value makes it possible to numerically evaluate the unevenness of the positive electrode active material.

[0353] Furthermore, it is possible to display the brightness change of the target area in a histogram. A histogram is a three-dimensional representation of the gradation distribution in the target area, and is also called a brightness histogram. By obtaining a brightness histogram, it becomes possible to visually understand and evaluate the unevenness of the positive electrode active material.

[0354] In the positive electrode active material 100 according to one embodiment of the present invention, the difference between the maximum and minimum values ​​of the grayscale value is preferably 120 or less, more preferably 115 or less, and even more preferably 70 or more and 115 or less. The standard deviation of the grayscale value is preferably 11 or less, more preferably 8 or less, and even more preferably 4 or more and 8 or less.

[0355] ≪Current pause method≫ The distribution of additive elements such as magnesium contained in the surface layer of the positive electrode active material 100 of one embodiment of the present invention may change slightly during repeated charging and discharging. For example, the distribution of the additive elements may become better, and the electronic conduction resistance may decrease. As a result, the electrical resistance at the beginning of the charge and discharge cycle, that is, the resistance component R(0.1s) with a fast response measured by the current rest method, may decrease.

[0356] For example, when comparing the nth (n is a natural number greater than 1) charge with the n+1th charge, the resistance component R(0.1s) with a fast response measured by the current rest method may be lower in the n+1th charge than in the nth charge. Accordingly, the n+1th discharge capacity may be higher than the nth discharge capacity. When n is 1, that is, when comparing the first charge with the second charge, the second charge capacity may be larger, especially in a positive electrode active material that does not contain an additive element, so n is preferably, for example, 2 to 10. However, this is not limited to the case as long as it is in the early stage of the charge / discharge cycle. When the charge / discharge capacity is about the same as the rated capacity, for example, 97% or more of the rated capacity, it can be said to be in the early stage of the charge / discharge cycle.

[0357] <Raman spectroscopy> As described above, it is preferable that at least a part of the surface layer portion 100a of the positive electrode active material 100 of one aspect of the present invention has a rock salt-type crystal structure. Therefore, when the positive electrode active material 100 and the positive electrode having the same are analyzed by Raman spectroscopy, it is preferable that a crystal structure of a cubic system including a rock salt type as well as a layered rock salt crystal structure is observed. In the STEM image and the electron backscatter diffraction pattern described later, cobalt substituted at the lithium position with a certain frequency in the depth direction at the time of observation, and cobalt present at the oxygen four-coordination position, etc. cannot be detected as bright spots in the STEM image and the electron backscatter diffraction pattern. On the other hand, since Raman spectroscopy is an analysis that captures the vibration mode of bonds such as Co-O, even if the abundance of the corresponding Co-O bond is small, a peak of the wave number of the corresponding vibration mode may be observed. Furthermore, Raman spectroscopy can measure a range of several μm in area and about 1 μm in depth of the surface layer portion, so that a state existing only on the particle surface can be captured with high sensitivity. 2 , and since it can measure a range of about 1 μm in depth, it can sensitively capture the state existing only on the particle surface.

[0358] For example, when the laser wavelength is 532 nm, in the layered rock salt type LiCoO 2 , peaks (vibration modes: E -1 to 490 cm -1 , 580 cm -1 to 600 cm -1 ) are observed at g , A 1g . On the other hand, in cubic CoO x (0 < x < 1) (rock salt type Co 1-y O (0 < y < 1) or spinel type Co 3 O 4 ), a peak (vibration mode: A 1g ) is observed at 665 cm 4 -1 to 685 cm -1 .

[0359] Therefore, the integrated intensity of each peak is defined as I1 for 470 cm -1 to 490 cm -1 , I2 for 580 cm -1 to 600 cm -1 , and I3 for 665 cm -1 to 685 cm -1 ​​​​​​​​​​​​​​When I3 is taken as I3, the value of I3 / I2 is preferably 1% or more and 10% or less, and more preferably 3% or more and 9% or less.

[0360] When a cubic crystal structure such as a rock-salt type is observed in the above range, it can be said that surface layer portion 100a of positive electrode active material 100 has a rock-salt type crystal structure in a preferred range.

[0361] <Microelectron diffraction pattern> As in Raman spectroscopy, it is preferable that the characteristics of the rock salt type crystal structure are observed in the electron microbeam diffraction pattern as well as the layered rock salt crystal structure. However, in the STEM image and the electron microbeam diffraction pattern, taking into consideration the above-mentioned difference in sensitivity, it is preferable that the characteristics of the rock salt type crystal structure are not too strong in the surface layer 100a, especially in the outermost surface (for example, 1 nm deep from the surface). This is because the lithium layer can secure a diffusion path for lithium and have a stronger function of stabilizing the crystal structure if an additive element such as magnesium is present in the lithium layer while maintaining the layered rock salt type crystal structure, rather than the outermost surface being covered with a rock salt type crystal structure.

[0362] Therefore, for example, when a micro-beam diffraction pattern of a region having a depth of 1 nm or less from the surface and a micro-beam diffraction pattern of a region having a depth of 3 nm to 10 nm are obtained, it is preferable that the difference in lattice constant calculated from these patterns be small.

[0363] For example, the difference in lattice constant calculated from a measurement point at a depth of 1 nm or less from the surface and a measurement point at a depth of 3 nm to 10 nm is preferably 0.1 Å or less for the a-axis and 1.0 Å or less for the c-axis, more preferably 0.05 Å or less for the a-axis and more preferably 0.6 Å or less for the c-axis, even more preferably 0.04 Å or less for the a-axis and even more preferably 0.3 Å or less for the c-axis.

[0364] <Additional Features> The positive electrode active material 100 may have recesses, cracks, depressions, V-shaped cross sections, and the like. These are one type of defect, and repeated charging and discharging may cause elution of cobalt, collapse of the crystal structure, cracking of the positive electrode active material 100, desorption of oxygen, and the like. However, if a buried portion 102 as shown in FIG. 6(A) is present so as to fill these, elution of cobalt and the like can be suppressed. Therefore, the positive electrode active material 100 can have excellent reliability and cycle characteristics.

[0365] As described above, if the additive element contained in the positive electrode active material 100 is excessive, it may adversely affect the insertion and desorption of lithium. In addition, when the positive electrode active material 100 is used in a secondary battery, it may cause an increase in internal resistance and a decrease in charge / discharge capacity. On the other hand, if the additive element is insufficient, it may not be distributed over the entire surface layer portion 100a, and the effect of suppressing deterioration of the crystal structure may be insufficient. Thus, the additive element needs to be at an appropriate concentration in the positive electrode active material 100, but it is not easy to adjust the concentration.

[0366] Therefore, when the positive electrode active material 100 has a region where the additive element is unevenly distributed, a part of the excess additive element atoms is removed from the inside 100b of the positive electrode active material 100, and the additive element concentration in the inside 100b can be made appropriate. This makes it possible to suppress an increase in internal resistance and a decrease in charge / discharge capacity when the positive electrode active material 100 is used as a secondary battery. The ability to suppress an increase in the internal resistance of a secondary battery is an extremely preferable characteristic, particularly in charge / discharge at a large current, for example, at 400 mA / g or more.

[0367] Furthermore, in the positive electrode active material 100 having a region where the additive element is unevenly distributed, it is permissible to mix an excess of the additive element to some extent in the manufacturing process, which is preferable because it provides a wider margin in production.

[0368] A coating portion may be attached to at least a portion of the surface of the positive electrode active material 100. Fig. 17 shows an example of a positive electrode active material 100 having a coating portion 104 attached thereto.

[0369] The coating portion 104 is preferably formed by the accumulation of decomposition products of the electrolyte and the organic electrolyte solution during charging and discharging. x Chief of Staff 2 In the case where charging is repeated such that x in the positive electrode active material 100 is 0.24 or less, it is expected that the charge-discharge cycle characteristics will be improved by having a coating portion derived from the electrolyte on the surface of the positive electrode active material 100. This is for reasons such as suppressing an increase in impedance on the surface of the positive electrode active material or suppressing the elution of cobalt. For example, the coating portion 104 preferably contains carbon, oxygen, and fluorine. Furthermore, when LiBOB and / or SUN (suberonitrile) are used as the electrolyte, a good quality coating portion is easily obtained. Therefore, the coating portion 104 having one or more selected from boron, nitrogen, sulfur, and fluorine may be a good quality coating portion and is preferable. In addition, the coating portion 104 does not have to cover the entire positive electrode active material 100. For example, it is sufficient that 50% or more of the surface of the positive electrode active material 100 is covered, more preferably 70% or more, and even more preferably 90% or more.

[0370] Furthermore, when the positive electrode active material is charged at 4.5 V or higher, or when it is charged and discharged in a high temperature environment, such as 45° C. or higher, progressive defects may develop in the positive electrode active material that progress from the surface to the inside. The phenomenon in which defects progress to form holes in the positive electrode active material can be called pitting corrosion, and the holes generated by this phenomenon are also called pits in this specification.

[0371] FIG. 18 shows a schematic cross-sectional view of a positive electrode active material 51 having pits. A crystal plane 55 parallel to the arrangement of cations is also shown. Since FIG. 18 is a cross-sectional view, pits 54 and pits 58 are shown as holes, but the opening shape of these pits is not circular but has depth and is shaped like a groove. Also, as shown by pits 54 and pits 58, unlike recesses 52, they tend to occur parallel to the arrangement of lithium ions.

[0372] The surface layer of the positive electrode active material 51 where the added element is present is indicated by 53 and 56. The surface layer where the pits have occurred has less added element than 53 and 56 or the concentration is below the detection limit, and it is expected that the function of the barrier film is reduced. It is also thought that the crystal structure of the lithium cobalt oxide breaks down in the vicinity of where the pits are formed, resulting in a crystal structure different from that of the layered rock salt type. When the crystal structure breaks down, it inhibits the diffusion and release of lithium ions, which are carrier ions, and therefore the pits are thought to be a factor in the deterioration of cycle characteristics.

[0373] The source of the pits may be point defects. It is thought that point defects in the positive electrode active material change with repeated charging and discharging, and are either chemically or electrochemically eroded by the surrounding electrolyte, or the material deteriorates, causing the pits. This deterioration does not occur uniformly on the surface of the positive electrode active material, but rather occurs locally.

[0374] In addition, as shown by the crack 57 in FIG. 18, the expansion and contraction of the positive electrode active material due to charging and discharging may cause defects such as cracks (also called fissures). In this specification, cracks and pits are different. Even if cracks are present immediately after the preparation of the positive electrode active material, pits do not exist. Pits can be said to be holes formed by several layers of cobalt and oxygen being removed by charging and discharging under high voltage conditions of, for example, 4.5 V or more or at high temperatures (45° C. or more), and can also be said to be places where cobalt has dissolved. The cracks refer to, for example, new surfaces formed by the application of physical pressure, or fissures caused by the grain boundaries 101. Cracks may also occur due to the expansion and contraction of the positive electrode active material due to charging and discharging. Pits may also occur from cracks and / or cavities inside the positive electrode active material.

[0375] In this specification, the space group is expressed using the short notation of the international notation (or Hermann-Mauguin notation). Also, the crystal plane and crystal direction are expressed using Miller indices. Individual planes indicating crystal planes are expressed using (). In crystallography, the numbers are marked with a superscript bar when notating space groups, crystal planes, and crystal directions, but in this specification, due to format restrictions, instead of placing a bar above the number, a - (minus sign) may be placed before the number. Also, individual directions indicating directions within a crystal are expressed with [ ], collective directions indicating all equivalent directions are expressed with < >, individual planes indicating crystal planes are expressed with ( ), and collective planes with equivalent symmetry are expressed with {}. Also, trigonal crystals represented by the space group R-3m are generally expressed as a composite hexagonal lattice of hexagonal crystals for ease of understanding of the structure, and Miller indices may use not only (hkl) but also (hkil). Here, i is -(h+k).

[0376] In this specification, the term "particle" does not necessarily refer to a spherical shape (a circular cross-sectional shape), but may refer to an elliptical, rectangular, trapezoidal, triangular, rectangular with rounded corners, asymmetrical shape, or the like, and further, the individual particles may be irregular in shape.

[0377] The theoretical capacity of a positive electrode active material refers to the amount of electricity when all of the lithium that can be inserted and removed from the positive electrode active material is removed. For example, LiCoO 2 The theoretical capacity of LiNiO is 274mAh / g. 2 The theoretical capacity of LiMn is 274mAh / g. 2 O 4 The theoretical capacity is 148mAh / g.

[0378] In addition, the amount of lithium remaining in the positive electrode active material that can be inserted or removed can be determined by the x in the composition formula, for example, Li x Chief of Staff 2 In the case of a positive electrode active material in a secondary battery, x = (theoretical capacity - charging capacity) / theoretical capacity. For example, LiCoO 2 When a secondary battery using this as the positive electrode active material is charged at 219.2mAh / g, Li 0.2 Chief of Staff 2Or we can say x=0.2. x Chief of Staff 2 A small x in the formula is, for example, 0.1. <x≦0.24をいう。

[0379] When properly synthesized lithium cobalt oxide is used in the positive electrode, the stoichiometric ratio is approximately LiCoO 2 where x = 1. The lithium cobalt oxide contained in the secondary battery after discharge is also LiCoO 2 It can be said that x = 1. The end of discharge here means, for example, when the current is 100 mAh or less and the voltage is 3.0 V or 2.5 V or less.

[0380] Li x Chief of Staff 2 It is preferable that the charge capacity and / or discharge capacity used in the calculation of x in the above should be measured under conditions that are free of or have little influence from short circuits and / or decomposition of the electrolyte, etc. For example, data from a secondary battery that has experienced a sudden change in capacity that may be due to a short circuit should not be used in the calculation of x.

[0381] The space group of a crystal structure is identified by XRD, electron beam diffraction, neutron beam diffraction, etc. Therefore, in this specification and the like, "belonging to a certain space group," "belonging to a certain space group," or "being a certain space group" can be rephrased as "identified with a certain space group."

[0382] Also, if the anions have a structure in which three layers are stacked with a mutual shift, such as ABCABC, it is called a cubic close-packed structure. Therefore, the anions do not have to be strictly cubic lattices. At the same time, since real crystals always have defects, the analysis results do not necessarily have to be the same as the theory. For example, in the FFT (fast Fourier transform) pattern of an electron diffraction pattern or a TEM image, etc., a spot may appear at a position slightly different from the theoretical position. For example, if the orientation with respect to the theoretical position is 5 degrees or less, or 2.5 degrees or less, it can be said to have a cubic close-packed structure.

[0383] Homogeneity refers to the phenomenon in which, in a solid consisting of multiple elements (e.g., A, B, C), a certain element (e.g., A) is distributed with similar characteristics in a specific region. Note that it is sufficient that the concentration of the element in the specific regions is substantially the same. For example, it is sufficient that the difference in element concentration between the specific regions is within 10%. Examples of specific regions include the surface layer, the surface, the convex parts, the concave parts, the interior, etc.

[0384] A positive electrode active material to which an additive element is added may be expressed as a composite oxide, a positive electrode material, a positive electrode material, a positive electrode material for secondary batteries, or the like. In this specification and the like, the positive electrode active material of one embodiment of the present invention preferably includes a compound. In this specification and the like, the positive electrode active material of one embodiment of the present invention preferably includes a composition. In this specification and the like, the positive electrode active material of one embodiment of the present invention preferably includes a composite.

[0385] In addition, when describing the characteristics of individual particles of the positive electrode active material in the following embodiments, etc., it is not necessary that all particles have that characteristic. For example, if 50% or more, preferably 70% or more, and more preferably 90% or more of three or more randomly selected particles of the positive electrode active material have that characteristic, it can be said that there is a sufficient effect of improving the characteristics of the positive electrode active material and the secondary battery having it.

[0386] As the charging voltage of a secondary battery increases, the voltage of the positive electrode generally increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at high voltages. Since the crystal structure of the positive electrode active material is stable in a charged state, it is possible to suppress a decrease in charge / discharge capacity due to repeated charging and discharging.

[0387] Moreover, a short circuit in a secondary battery not only causes problems in the charging and / or discharging operations of the secondary battery, but may also lead to heat generation and fire. In order to realize a safe secondary battery, it is preferable that a short circuit current is suppressed even at a high charging voltage. The positive electrode active material of one embodiment of the present invention suppresses a short circuit current even at a high charging voltage. Therefore, a secondary battery that achieves both high discharge capacity and safety can be obtained.

[0388] Unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) of the secondary battery are described in the state before degradation. The decrease in discharge capacity due to aging and burn-in treatments during the secondary battery manufacturing stage is not called degradation. For example, when a lithium-ion secondary cell and a lithium-ion secondary battery pack (hereinafter referred to as a lithium-ion secondary battery) have a discharge capacity of 97% or more of the rated capacity, it can be said to be in the state before degradation. The rated capacity of lithium-ion secondary batteries for portable devices complies with JIS C 8711:2019. For other lithium-ion secondary batteries, the rated capacity complies with not only the above JIS standard but also with each JIS, IEC standard, etc. for electric vehicle propulsion and industrial use.

[0389] In this specification, the state of the materials in a secondary battery before deterioration is referred to as an initial product or initial state, and the state after deterioration (the state when the secondary battery has a discharge capacity less than 97% of the rated capacity) may be referred to as a product in use or in use state, or a used product or used state.

[0390] This embodiment mode can be used in combination with other embodiment modes.

[0391] (Embodiment 3) <<Method 2 for preparing positive electrode active material>> A method 2 for producing a positive electrode active material, which is one embodiment of the present invention and is different from the method 1 for producing a positive electrode active material, will be described with reference to Fig. 19, Fig. 20(A), and Fig. 20(B). The method 2 for producing a positive electrode active material differs from the method 1 for producing a positive electrode active material mainly in the number of times that an additive element is added and the mixing method. For the rest of the description, the description of the method 1 can be referred to.

[0392] In FIG. 19, steps S11 to S15 are carried out in the same manner as in FIG. 1(A) to prepare lithium cobalt oxide that has been subjected to initial heating.

[0393] <Step S21> In step S20a shown in Fig. 20(A), a source of additive element A1 is prepared. The source of additive element A1 can be selected from the additive elements A described in step S21 shown in Fig. 1(B). For example, one or more selected from magnesium, fluorine, and calcium can be suitably used as the additive element A1. In step S21 of Fig. 20(A), a case where a magnesium source (Mg source) and a fluorine source (F source) are used as the first additive element source is illustrated.

[0394] Steps S21 to S23 shown in Fig. 20A can be performed under the same conditions as steps S21 to S23 shown in Fig. 1B. As a result, an additive element source (A1 source) can be obtained in step S23.

[0395] As shown in Fig. 20(A), the additive element source (A1 source) is stored in a first container. Next, the inner surface of the container is coated under the same conditions as in step S24 shown in Fig. 1(B). In this embodiment, a square container (made of ceramics) called a sheath is used, and the container is covered with a lid (made of ceramics) and heated to cause the additive element A to be contained in the inner surface of the container or the inner surface of the lid. The additive element A1 may be coated on the inner surface as a film, or may be allowed to soak into the irregularities on the inner surface of the container.

[0396] When a large-capacity container is used, a large amount of the additive element A1 source (A1 source) can be coated or impregnated on the inner surface of the first container, compared to the amount of lithium cobalt oxide. In addition, if a large amount of the additive element A1 source (A1 source) can be coated or impregnated on the inner surface of the first container, it can be used multiple times.

[0397] In this way, a container is prepared whose inner surface is coated with the A1 source, as shown in FIG. 20(A).

[0398] Then, the lithium cobalt oxide that has been subjected to the initial heating is placed in a container whose inner surface is coated with the A1 source, and heating is performed as shown in step S33 of FIG.

[0399] <Step S34a> Next, in step S33, the heated material is collected to produce lithium cobalt oxide containing the additive element A1. The lithium cobalt oxide at this stage is also called a composite oxide (step S34a in FIG. 19).

[0400] <Step S40> In step S40 shown in FIG. 20(B), the additive element A2 is prepared.

[0401] <Step S41> In step S41 shown in Fig. 20(B), a second additive element source is prepared. The second additive element source can be selected from the additive elements A described in step S21 shown in Fig. 1(B) and used. For example, the additive element A2 can be one or more selected from nickel, titanium, boron, zirconium, and aluminum. Fig. 20(B) illustrates an example in which a nickel source (Ni source) and an aluminum source (Al source) are used as the second additive element source.

[0402] Steps S41 to S43 shown in Fig. 20B can be performed under the same conditions as steps S21 to S23 shown in Fig. 1B. As a result, an additive element source (A2 source) can be obtained in step S43.

[0403] Next, as shown in FIG. 20(B), the additive element source (A2 source) is stored in the second container. Then, the inner surface of the container is coated under the same conditions as in step S24 shown in FIG. 1(B) (step S44 in FIG. 20). In this embodiment, a square container (made of ceramics) called a sheath is used, and the container is covered with a lid (made of ceramics) and heated to contain the additive element A2 on the inner surface of the container or the inner surface of the lid. The additive element A2 may be coated on the inner surface as a film, or may be allowed to soak into the irregularities on the inner surface of the second container.

[0404] <Step S53> Next, step S53 shown in Fig. 19 can be performed under the same conditions as step S33 shown in Fig. 1(A). The conditions for step S53 relating to the heating step may be a lower temperature and a shorter time than those for step S33. Through the above steps, in step S54, the cathode active material 100 according to one embodiment of the present invention can be produced. The cathode active material according to one embodiment of the present invention has a smooth surface.

[0405] As shown in Figures 19, 20(A), and 20(B), in the manufacturing method 2, the additive element A1 and the additive element A2 are introduced separately into the lithium cobalt oxide. By introducing them separately, the profile of each additive element in the depth direction can be changed. For example, it is possible to profile the additive element A1 so that the concentration is higher in the surface layer portion than in the inside, and profile the additive element A2 so that the concentration is higher in the inside than in the surface layer portion.

[0406] By undergoing the initial heating described in this embodiment, a positive electrode active material with a smooth surface can be obtained.

[0407] The initial heating shown in this embodiment is performed on lithium cobalt oxide. Therefore, the initial heating is preferably performed under conditions of a heating temperature lower than that for obtaining lithium cobalt oxide and a heating time shorter than that for obtaining lithium cobalt oxide. The step of adding an additive element to lithium cobalt oxide is preferably performed after the initial heating. The addition step can be divided into two or more steps. By following such a step order, the smoothness of the surface obtained by the initial heating is preferably maintained.

[0408] This embodiment mode can be used in combination with other embodiment modes.

[0409] (Embodiment 4) In this embodiment, the configuration of a lithium ion battery will be described.

[0410] [Positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and may further include at least one of a conductive additive and a binder. The positive electrode active material may be the same as that described in the second embodiment.

[0411] FIG. 21(A) shows an example of a schematic cross-sectional view of a positive electrode.

[0412] The current collector 550 can be, for example, a metal foil. The positive electrode can be formed by applying a slurry onto a metal foil and drying it. Note that pressing may be performed after drying. The positive electrode is formed by forming an active material layer on the current collector 550.

[0413] The slurry is a material liquid used for forming an active material layer on the current collector 550, and contains an active material, a binder, and a solvent, and preferably further contains a conductive assistant. The slurry is also called an electrode slurry or an active material slurry, and a positive electrode slurry is used when a positive electrode active material layer is formed, and a negative electrode slurry is also used when a negative electrode active material layer is formed.

[0414] The positive electrode active material 561 has a function of taking in and / or releasing lithium ions with charging and discharging. The positive electrode active material 561 used as one embodiment of the present invention can be a material that does not deteriorate much with charging and discharging even at high charging voltages. In this specification and the like, unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal. In this specification and the like, a high charging voltage is, for example, a charging voltage of 4.6V or more, preferably 4.65V or more, more preferably 4.7V or more, even more preferably 4.75V or more, and most preferably 4.8V or more.

[0415] The positive electrode active material 561 used in one embodiment of the present invention can be any material that does not deteriorate much due to charging and discharging even at a high charging voltage, and can be any material described in embodiment 1 or embodiment 2. Note that the positive electrode active material 561 can be two or more materials with different particle sizes as long as the material does not deteriorate much due to charging and discharging even at a high charging voltage.

[0416] The conductive assistant is also called a conductive agent or conductive material, and may be a carbon material. By attaching the conductive assistant between a plurality of active materials, the plurality of active materials are electrically connected to each other, and the conductivity is increased. In this specification, the term "attachment" does not only refer to the physical adhesion between the active material and the conductive assistant, but also includes the case where a covalent bond is formed, the case where the conductive assistant is bonded by van der Waals forces, the case where the conductive assistant covers a part of the surface of the active material, the case where the conductive assistant is embedded in the surface irregularities of the active material, and the case where the conductive assistant is electrically connected even if they are not in contact with each other.

[0417] Specific examples of carbon materials that can be used as the conductive assistant include carbon black (furnace black, acetylene black, graphite, etc.).

[0418] FIG. 21(A) illustrates carbon black 553 as a conductive additive.

[0419] A binder (resin) may be mixed to bond a current collector 550 such as a metal foil to an active material as the positive electrode of a lithium ion battery. The binder is also called a binding agent. The binder is a polymer material, and if a large amount of the binder is included, the ratio of the active material in the positive electrode decreases, and the discharge capacity of the lithium ion battery decreases. Therefore, it is preferable to mix the binder in a minimum amount. In FIG. 21(A), the regions not filled with the positive electrode active material 561, the second active material 562, and the carbon black 553 indicate voids or binders.

[0420] 21(A) shows an example in which the positive electrode active material 561 is illustrated as a sphere, but is not particularly limited thereto. For example, the cross-sectional shape of the positive electrode active material 561 may be an ellipse, a rectangle, a trapezoid, a pyramid, a polygon with rounded corners, or an asymmetric shape. For example, FIG. 21(B) shows an example in which the positive electrode active material 561 has a polygonal shape with rounded corners.

[0421] 21B, graphene 554 is used as a carbon material used as a conductive additive. In FIG. 21B, a positive electrode active material layer including a positive electrode active material 561, graphene 554, and carbon black 553 is formed over a current collector 550.

[0422] In the step of mixing the graphene 554 and the carbon black 553 to obtain an electrode slurry, the weight of the carbon black to be mixed is preferably 1.5 to 20 times, more preferably 2 to 9.5 times, that of the graphene.

[0423] In addition, when the mixture of graphene 554 and carbon black 553 is within the above range, the dispersion stability of carbon black 553 is excellent during slurry preparation, and agglomeration is unlikely to occur. In addition, when the mixture of graphene 554 and carbon black 553 is within the above range, a higher electrode density can be achieved than a positive electrode using only carbon black 553 as a conductive additive. By increasing the electrode density, the capacity per unit weight can be increased. Specifically, the density of the positive electrode active material layer measured by weight can be 3.5 g / cc or more.

[0424] Although the electrode density is lower than that of a positive electrode using only graphene as a conductive additive, by mixing the first carbon material (graphene) and the second carbon material (acetylene black) within the above range, it can be used for rapid charging. Therefore, it is particularly effective when used as an in-vehicle lithium-ion battery.

[0425] Fig. 21C illustrates an example of a positive electrode using carbon fiber 555 instead of graphene. Fig. 21C illustrates an example different from Fig. 21B. When carbon fiber 555 is used, aggregation of carbon black 553 can be prevented and dispersibility can be improved.

[0426] In FIG. 21C, the regions not filled with the positive electrode active material 561, the carbon fibers 555, and the carbon black 553 indicate voids or binders.

[0427] In addition, Fig. 21(D) shows another example of the positive electrode. Fig. 21(C) shows an example in which carbon fiber 555 is used in addition to graphene 554. When both graphene 554 and carbon fiber 555 are used, aggregation of carbon black such as carbon black 553 can be prevented and dispersibility can be further improved.

[0428] Note that in FIG. 21D, regions that are not filled with the positive electrode active material 561, the carbon fibers 555, the graphene 554, and the carbon black 553 indicate voids or binders.

[0429] A lithium ion battery can be manufactured by using any one of the positive electrodes shown in Figures 21(A) to 21(D), stacking a separator on the positive electrode, placing the stack in which the negative electrode is stacked on the separator in a container (outer body, metal can, etc.) that houses the stack, and filling the container with a liquid electrolyte.

[0430] <Binder> As the binder, it is preferable to use a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Also, as the binder, fluororubber can be used.

[0431] <Positive electrode current collector> As the current collector, a material having high electrical conductivity, such as metals such as stainless steel, gold, platinum, aluminum, and titanium, and alloys thereof, can be used. In addition, it is preferable that the material used for the positive electrode current collector does not dissolve at the potential of the positive electrode. In addition, an aluminum alloy to which an element that improves heat resistance, such as silicon, titanium, neodymium, scandium, or molybdenum, is added can be used. In addition, it may be formed of a metal element that reacts with silicon to form a silicide. Examples of the metal element that reacts with silicon to form a silicide include zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, and nickel. The current collector can be appropriately used in the form of a foil, plate, sheet, net, punched metal, or expanded metal. It is preferable to use a current collector having a thickness of 5 μm or more and 30 μm or less.

[0432] [Negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a conductive assistant and a binder.

[0433] <Negative electrode active material> As the negative electrode active material, for example, an alloy material and / or a carbon material can be used.

[0434] The carbon material used for the negative electrode active material may be one or more selected from graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon fiber (carbon nanotube), graphene, carbon black, and the like.

[0435] Examples of the graphite include artificial graphite and natural graphite. Examples of the artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, MCMB may have a spherical shape, which is preferable. In addition, it is relatively easy to reduce the surface area of ​​MCMB, which may be preferable. Examples of the natural graphite include flake graphite and spheroidized natural graphite.

[0436] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), graphite exhibits a low potential similar to that of lithium metal (0.05 V to 0.3 V vs. Li / Li + ) This allows lithium-ion batteries using graphite to exhibit high operating voltages. In addition, graphite is preferred because it has the advantages of relatively high capacity per unit volume, relatively small volume expansion, low cost, and greater safety than lithium metal.

[0437] In addition, the negative electrode active material may be an element capable of undergoing a charge / discharge reaction by alloying / dealloying with lithium. For example, one or more materials selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. may be used. These elements have a larger capacity than carbon, and silicon in particular has a high theoretical capacity of 4200 mAh / g. Compounds containing these elements may also be used. For example, SiO, Mg 2 Si, Mg 2 Ge, SnO, SnO 2 , Mg 2 Sn, SnS 2 , V 2 Sn 3 , FeSn 2 , CoSn 2 , Ni 3 Sn 2 , Cu 6 Sn 5 , Ag 3 Sn, Ag 3 Sb, Ni 2 MnSb, CeSb 3 , LaSn 3 , La 3 Co 2 Sn 7 , CoSb 3 , InSb, SbSn, etc. Here, elements capable of carrying out charge-discharge reactions by alloying / dealloying reactions with lithium, and compounds containing such elements, are sometimes called alloy materials.

[0438] In this specification, "SiO" refers to, for example, silicon monoxide. Alternatively, SiO may be SiO x Here, x preferably has a value of 1 or close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0439] Titanium dioxide (TiO 2 ), lithium titanium oxide (Li 4 Ti 5 O 12 ), lithium-graphite intercalation compound (Li x C 6 ), niobium pentoxide (Nb 2 O 5 ), tungsten oxide (WO 2 ), molybdenum oxide (MoO 2 ) and the like can be used.

[0440] In addition, the negative electrode active material is a complex nitride of lithium and transition metals, Li 3 Li with N-type structure 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N 3 has a large discharge capacity (900mAh / g, 1890mAh / cm 3 ) and is preferred.

[0441] When a complex nitride of lithium and transition metals is used, the negative electrode active material contains lithium ions, so the positive electrode active material does not contain lithium ions. 2 O 5 , Cr 3 O 8 It is preferable that the negative electrode active material can be combined with a material such as lithium ions. Even when a material containing lithium ions is used as the positive electrode active material, a composite nitride of lithium and a transition metal can be used as the negative electrode active material by first removing the lithium ions contained in the positive electrode active material.

[0442] In addition, a material that undergoes a conversion reaction can be used as the negative electrode active material. For example, a transition metal oxide that does not form an alloy with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), or iron oxide (FeO), can be used as the negative electrode active material. Further examples of materials that undergo a conversion reaction include Fe 2 O 3 ,CuO,Cu 2 O, RuO 2 , Cr 2 O 3 Oxides such as CoS 0.89 , NiS, CuS and other sulfides, Zn 3 N 2 , Cu 3 N, Ge 3 N 4 Nitrides such as NiP 2 , FeP 2 , CoP 3 Phosphides such as FeF 3 , BiF 3 This also occurs with fluorides such as

[0443] In addition, a combination of a plurality of the above-mentioned negative electrode active materials may be used, for example, a negative electrode active material in which graphite and silicon particles are mixed may be used. Silicon particles are silicon powder as a material for the negative electrode active material of a lithium ion secondary battery, and refer to those having an average particle size in the particle size distribution, i.e., an average particle size of about 100 nm, and may be called nanosilicon particles. The silicon particles used are preferably adjusted to a uniform particle size by crushing a silicon raw material. The silicon particles may contain at least one of silicon, silicon oxide, and silicon alloy. The particle size can be measured by a representative laser diffraction particle size distribution measurement, but is not limited to the laser diffraction particle size distribution measurement, and the major axis of the particle cross section may be measured by analysis such as SEM (scanning electron microscope) or TEM (transmission electron microscope).

[0444] The conductive additive and binder that the negative electrode active material layer can have can be the same materials as the conductive additive and binder that the positive electrode active material layer can have.

[0445] <Negative electrode current collector> The negative electrode current collector may be made of the same material as the positive electrode current collector, or may be made of copper, etc. Note that it is preferable to use a material that does not form an alloy with carrier ions such as lithium for the negative electrode current collector.

[0446] [Electrolyte] The electrolyte has an organic solvent, but the organic solvent of the electrolyte according to one embodiment of the present invention is not limited to being liquid at 25° C., and may be solid at 25° C. or semi-solid at room temperature. The organic solvent of the electrolyte according to one embodiment of the present invention is preferably liquid in a wide temperature range including below freezing point to high temperatures, but is not limited thereto. The organic solvent may be liquid, solid, or semi-solid in a wide temperature range including below freezing point to high temperatures.

[0447] The organic solvent is preferably an aprotic organic solvent, and for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, and sultones can be used, or two or more of these can be used in any combination and ratio.

[0448] The organic solvents mentioned above are contaminated with particulate matter or molecules other than the constituent molecules of the organic solvent (hereinafter simply referred to as "impurities"), and oxygen (O 2 ), water (H 2O) or water. It is preferable that the content of ) is low and highly purified. Specifically, the amount of impurities in the electrolyte is 100 ppm or less, preferably 50 ppm or less, and more preferably less than 10 ppm. The water concentration can be detected by Karl Fischer titration.

[0449] In addition, by using one or more ionic liquids (room-temperature molten salts) that are flame-retardant and non-volatile as a solvent for the electrolyte, even if the internal temperature of the electricity storage device rises due to an internal short circuit or overcharging, the electricity storage device can be prevented from bursting or catching fire. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolyte include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, and aromatic cations such as imidazolium cations and pyridinium cations. Examples of the anion used in the electrolyte include monovalent amide anions, monovalent methide anions, fluorosulfonic acid anions, perfluoroalkylsulfonic acid anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, and perfluoroalkylphosphate anions.

[0450] The electrolyte to be dissolved in the above-mentioned solvent is, for example, LiPF 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiAlCl 4 , LiSCN, LiBr, LiI, Li 2 SO 4 , Li 2 B 10 Cl 10 , Li 2 B 12 Cl 12 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiC(CF 3 SO 2 ) 3, LiC(C 2 F 5 SO 2 ) 3 , LiN(CF 3 SO 2 ) 2 , LiN(C 4 F 9 SO 2 )(CF 3 SO 2 ), LiN(C 2 F 5 SO 2 ) 2 , lithium bis(oxalato)borate (Li(C 2 O 4 ) 2 Lithium salts such as LiBOB, ...

[0451] The electrolyte used in the electricity storage device is preferably a highly purified electrolyte with a low content of granular waste or elements other than the constituent elements of the electrolyte (hereinafter, simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolyte is preferably 1% or less, more preferably 0.1% or less, and even more preferably 0.01% or less.

[0452] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.

[0453] By using a polymer gel electrolyte, safety against leakage etc. is improved, and the secondary battery can be made thinner and lighter.

[0454] Examples of the polymer to be gelled include silicone gel, acrylic gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, and fluorine-based polymer gel. For example, polymers having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, and polyacrylonitrile, and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. The polymer to be formed may also have a porous shape.

[0455] In addition, as the electrolyte, a solid electrolyte containing inorganic materials such as sulfides or oxides, or a solid electrolyte containing polymeric materials such as PEO (polyethylene oxide) can be used. When a solid electrolyte is used, the installation of a separator or spacer becomes unnecessary. In addition, since the entire battery can be solidified, there is no risk of leakage, and safety is dramatically improved.

[0456] [Separator] When the electrolyte contains a liquid electrolyte (also called an electrolyte solution), a separator is disposed between the positive electrode and the negative electrode. As the separator, for example, a separator formed of fibers having cellulose such as paper, nonwoven fabric, glass fiber, ceramics, or synthetic fibers using nylon (polyamide), vinylon (polyvinyl alcohol fiber), polypropylene (referred to as PP), polyimide (referred to as PI), polyester, acrylic, polyolefin, polyurethane, etc. can be used. The porosity of the separator in the thickness can be 35% to 90%, preferably 60% to 85%. The porosity of the separator using polypropylene can be 35% to 45%. The porosity of the separator using polyimide can be 75% to 85%. The thickness of the separator is preferably 10 μm to 80 μm, more preferably 20 μm to 60 μm. A separator using polyimide is preferable because it can have a high porosity and can be made thick (typically, the thickness is 50 μm or more and 60 μm or less).

[0457] The separator is preferably formed into a bag shape and disposed so as to encase either the positive electrode or the negative electrode.

[0458] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene or polyethylene may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. As the ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As the fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As the polyamide material, for example, nylon or aramid (meta-aramid or para-aramid) may be used.

[0459] By using a separator with a multi-layer structure, the safety of the lithium-ion battery can be maintained even if the overall thickness of the separator is thin, so the capacity per volume of the lithium-ion battery can be increased.

[0460] [Exterior body] The exterior body of the lithium ion battery can be made of a metal material such as aluminum or a resin material. A film-shaped exterior body can also be used. As the film, a three-layer structure film can be used in which a thin metal film having excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide-based resin or polyester-based resin is further provided on the thin metal film as the outer surface of the exterior body.

[0461] This embodiment mode can be used in combination with other embodiment modes.

[0462] (Embodiment 5) In this embodiment, a lithium ion battery will be described as an example.

[0463] [Laminated lithium-ion battery] An example of a laminated lithium ion battery 500 is shown in Fig. 22(A) and Fig. 22(B). Fig. 22(A) and Fig. 22(B) are external views, and the lithium ion battery 500 has the electrolyte and separator (not shown in Fig. 22) described in the above embodiment, a negative electrode 506, and a positive electrode 507. In the lithium ion battery 500, the negative electrode 506 may have a larger area than the positive electrode 507. The lithium ion battery 500 further has a negative electrode lead electrode 510 electrically connected to the negative electrode 506, and a positive electrode lead electrode 511 electrically connected to the positive electrode 507. The electrolyte layer, the negative electrode 506, and the positive electrode 507 are housed in an exterior body 509, and a part of the negative electrode lead electrode 510 and a part of the positive electrode lead electrode 511 protrude from the exterior body 509. A bonding area 508 is provided on a part of the outer periphery of the exterior body 509. Fig. 22(A) shows an example in which the negative lead electrode 510 and the positive lead electrode 511 protrude from the same side of the exterior body 509, and the adhesive region 508 is located at least on the side from which each lead electrode protrudes and on two sides adjacent to that side. Fig. 22(B) shows an example in which the side from which the negative lead electrode 510 protrudes from the exterior body 509 and the side from which the positive lead electrode 511 protrudes from the exterior body 509 face each other, and the adhesive region 508 is located at least on the two sides from which each lead electrode protrudes and on one side sandwiched between the two sides. In Figs. 22(A) and 22(B), the side on which the adhesive region 508 is not located may correspond to the side on which the exterior body 509 is folded.

[0464] By using the positive electrode active material of the present invention in the laminated lithium ion battery 500, a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics can be obtained.

[0465] [Coin-type lithium-ion battery] An example of a coin-type lithium ion battery will be described. Fig. 23(A) is an exploded perspective view of a coin-type (single-layer flat) lithium ion battery, Fig. 23(B) is an external view, and Fig. 23(C) is a cross-sectional view thereof. Coin-type lithium ion batteries are mainly used in small electronic devices. In this specification and the like, coin-type lithium ion batteries include button-type lithium ion batteries.

[0466] In order to make it easier to understand, Fig. 23(A) is a schematic diagram showing the overlapping of components (upper and lower relationships and positional relationships). Therefore, Fig. 23(A) and Fig. 23(B) are not completely corresponding views.

[0467] 23(A) shows how the positive electrode 304, the negative electrode 307, the spacer 342, and the washer 332 are stacked and sealed with the negative electrode can 302 and the positive electrode can 301. Note that the electrolyte and the separator described in the above embodiment are not shown in FIG. 23(A). The spacer 342 and the washer 332 are used to protect the inside or to fix the position inside the can when the positive electrode can 301 and the negative electrode can 302 are crimped together. The spacer 342 or the washer 332 is made of stainless steel or an insulating material.

[0468] A laminated structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is used as a positive electrode 304 .

[0469] FIG. 23(B) is a perspective view of the completed coin-type lithium-ion battery 300.

[0470] In the coin-type lithium-ion battery 300, a positive electrode can 301 also serving as a positive electrode terminal and a negative electrode can 302 also serving as a negative electrode terminal may be insulated and sealed with a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector. The negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0471] In addition, the positive electrode 304 and the negative electrode 307 used in the coin-type lithium ion battery 300 each only need to have an active material layer formed on one side.

[0472] As shown in FIG. 23(C), positive electrode can 304, negative electrode 307, and negative electrode can 302 are stacked in this order with positive electrode can 301 facing down, and positive electrode can 301 and negative electrode can 302 are crimped together with gasket 303 interposed therebetween to produce a coin-shaped lithium ion battery 300.

[0473] By using the positive electrode active material of the present invention in the coin-type lithium ion battery 300, a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics can be obtained.

[0474] [Cylindrical lithium-ion battery] An example of a cylindrical lithium ion battery will be described with reference to Fig. 24(A). As shown in Fig. 24(A), a cylindrical lithium ion battery 616 has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap 601 and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.

[0475] Fig. 24(B) is a schematic diagram showing a cross section of a cylindrical lithium ion battery. The cylindrical lithium ion battery shown in Fig. 24(B) has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.

[0476] A battery element is provided inside a hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with an electrolyte layer 605 sandwiched therebetween. Although not shown, the battery element is wound around a central axis. One end of the battery can 602 is closed and the other end is open. Inside the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched between a pair of opposing insulating plates 608 and 609. An electrolyte (not shown) according to one embodiment of the present invention is injected into the inside of the battery can 602 in which the battery element is provided.

[0477] Since the positive and negative electrodes used in a cylindrical storage battery are wound, it is preferable to form active materials on both sides of the current collector. Although the lithium ion battery 616 in which the height of the cylinder is greater than the diameter of the cylinder is illustrated in Figures 24(A) to 24(D), this is not limited to this. A lithium ion battery in which the diameter of the cylinder is greater than the height of the cylinder may also be used. With such a configuration, for example, the lithium ion battery can be made smaller.

[0478] A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. Both the positive electrode terminal 603 and the negative electrode terminal 607 can be made of a metal material such as aluminum. The positive electrode terminal 603 is resistance-welded to a safety valve mechanism 613, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cap 601 via a PTC element (Positive Temperature Coefficient) 611. The safety valve mechanism 613 cuts off the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the increase in the internal pressure of the battery exceeds a predetermined threshold value. The PTC element 611 is a thermosensitive resistor element whose resistance increases when the temperature increases, and the increase in resistance limits the amount of current to prevent abnormal heat generation. The PTC element is made of barium titanate (BaTiO 3 )-based ceramic materials, etc. can be used.

[0479] FIG. 24C shows an example of a power storage system 615. The power storage system 615 has a plurality of lithium ion batteries 616 and may be called a battery pack. A positive electrode of each lithium ion battery is in contact with and electrically connected to a conductor 624 separated by an insulator 625. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, a negative electrode of each lithium ion battery is electrically connected to the control circuit 620 via a wiring 626. A protection circuit that prevents overcharging or overdischarging, or the like, can be applied as the control circuit 620.

[0480] 24(D) shows an example of a power storage system 615. The power storage system 615 has a plurality of lithium ion batteries 616, and the plurality of lithium ion batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of lithium ion batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 by wiring 627. The plurality of lithium ion batteries 616 may be connected in parallel, may be connected in series, or may be connected in parallel and then further connected in series. By configuring the power storage system 615 having a plurality of lithium ion batteries 616, it is possible to extract a large amount of power.

[0481] A number of lithium ion batteries 616 may be connected in parallel and then further connected in series.

[0482] A temperature control device may be provided between the multiple lithium ion batteries 616. When the lithium ion batteries 616 are overheated, they can be cooled by the temperature control device, and when the lithium ion batteries 616 are too cold, they can be heated by the temperature control device. This makes the performance of the power storage system 615 less susceptible to the effect of the outside air temperature.

[0483] 24(D), the power storage system 615 is electrically connected to a control circuit 620 via a wiring 621 and a wiring 622. The wiring 621 is electrically connected to a positive electrode of the plurality of lithium ion batteries 616 via a conductive plate 628, and the wiring 622 is electrically connected to a negative electrode of the plurality of lithium ion batteries 616 via a conductive plate 614.

[0484] By using the positive electrode active material of the present invention in the cylindrical lithium ion battery 616, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0485] [Other examples of lithium-ion battery structures] An example of the structure of a lithium ion battery will be described with reference to FIGS. 25 and 26. FIG.

[0486] A lithium ion battery 913 shown in FIG. 25A has a wound body 950 in which terminals 951 and 952 are provided inside a housing 930. The wound body 950 is impregnated with an electrolyte according to one embodiment of the present invention inside the housing 930. The terminal 952 contacts the housing 930, and the terminal 951 does not contact the housing 930 by using an insulating material or the like. Note that in FIG. 25A, the housing 930 is shown separated for convenience, but in reality, the wound body 950 is covered by the housing 930, and the terminals 951 and 952 extend outside the housing 930. The housing 930 can be made of a metal material (e.g., aluminum) or a resin material.

[0487] Note that as shown in Fig. 25(B), the housing 930 shown in Fig. 25(A) may be formed using a plurality of materials. For example, in a lithium ion battery 913 shown in Fig. 25(B), a housing 930a and a housing 930b are bonded together, and a wound body 950 is provided in a region surrounded by the housing 930a and the housing 930b.

[0488] The housing 930a can be made of an insulating material such as organic resin. In particular, by using a material such as organic resin on the surface on which the antenna is formed, it is possible to suppress shielding of the electric field by the lithium ion battery 913. Note that if the shielding of the electric field by the housing 930a is small, the antenna may be provided inside the housing 930a. The housing 930b can be made of, for example, a metal material.

[0489] 25(C) shows the structure of the wound body 950. The wound body 950 has a negative electrode 931, a positive electrode 932, and an electrolyte layer 933. The wound body 950 is a wound body in which the negative electrode 931 and the positive electrode 932 are stacked on top of each other with the electrolyte layer 933 sandwiched therebetween, and the laminated sheet is wound. Note that the stack of the negative electrode 931, the positive electrode 932, and the electrolyte layer 933 may be stacked a plurality of times.

[0490] 26(A) to 26(C) may be used as a lithium ion battery 913 having a wound body 950a. The wound body 950a shown in Fig. 26(A) has a negative electrode 931, a positive electrode 932, and an electrolyte layer 933. The negative electrode 931 has a negative electrode active material layer 931a. The positive electrode 932 has a positive electrode active material layer 932a.

[0491] The electrolyte layer 933 has a width wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. From the viewpoint of safety, it is preferable that the width of the negative electrode active material layer 931a is wider than that of the positive electrode active material layer 932a. Moreover, a wound body 950a having such a shape is preferable because of its high safety and productivity.

[0492] 26B, the negative electrode 931 is electrically connected to a terminal 951. The terminal 951 is electrically connected to a terminal 911a. The positive electrode 932 is electrically connected to a terminal 952. The terminal 952 is electrically connected to a terminal 911b.

[0493] 26(C), the wound body 950a is covered with the housing 930 to form the lithium ion battery 913. It is preferable that a safety valve, an overcurrent protection element, and the like are provided in the housing 930. The safety valve is a valve that opens when the inside of the housing 930 reaches a predetermined internal pressure in order to prevent the battery from exploding.

[0494] As shown in Fig. 26(B), the lithium ion battery 913 may have a plurality of wound bodies 950a. By using a plurality of wound bodies 950a, the lithium ion battery 913 can have a larger charge / discharge capacity. For other elements of the lithium ion battery 913 shown in Figs. 26(A) and (B), the descriptions of the lithium ion battery 913 shown in Figs. 25(A) to 25(C) can be referred to.

[0495] By using the positive electrode active material of the present invention in the lithium ion battery 913 having a wound body, a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics can be obtained.

[0496] The content of this embodiment mode can be appropriately combined with the content of the other embodiment modes.

[0497] (Embodiment 6) In this embodiment, an example of application to an electric vehicle (EV) will be shown with reference to FIG.

[0498] 27(A), an electric vehicle is equipped with first batteries 1301a and 1301b as main driving lithium ion batteries, and a second battery 1311 that supplies power to an inverter 1312 that starts a motor 1304. By using the positive electrode active material of the present invention for the first batteries 1301a and 1301b, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0499] The second battery 1311 is also called a cranking battery (also called a starter battery). The second battery 1311 only needs to have high output, and does not need to have a large capacity. The capacity of the second battery 1311 is smaller than that of the first batteries 1301a and 1301b.

[0500] The internal structure of the first battery 1301a may be a wound type or a laminated type. The first battery 1301a may use the all-solid-state battery of embodiment 6. By using the all-solid-state battery of embodiment 6 for the first battery 1301a, it is possible to achieve a high capacity, improve safety, and reduce the size and weight.

[0501] In this embodiment, an example is shown in which two first batteries 1301a and 1301b are connected in parallel, but three or more batteries may be connected in parallel. If the first battery 1301a can store sufficient power, the first battery 1301b may not be necessary. By configuring a battery pack having multiple lithium ion batteries, it is possible to extract large power. The multiple lithium ion batteries may be connected in parallel, in series, or in series after being connected in parallel. A plurality of lithium ion batteries is also called a battery pack.

[0502] In addition, in an on-vehicle lithium ion battery, in order to cut off power from a plurality of lithium ion batteries, a service plug or circuit breaker capable of cutting off high voltage without using tools is provided in the first battery 1301a.

[0503] The power of the first batteries 1301a and 1301b is mainly used to rotate the motor 1304, but also supplies power to 42V in-vehicle components (such as an electric power steering 1307, a heater 1308, and a defogger 1309) via a DCDC circuit 1306. When a rear motor 1317 is provided for the rear wheels, the first battery 1301a is used to rotate the rear motor 1317.

[0504] In addition, the second battery 1311 supplies power to 14V in-vehicle components (such as an audio system 1313, a power window 1314, and lamps 1315) via the DCDC circuit 1310.

[0505] The first battery 1301a will be described with reference to FIG.

[0506] FIG. 27B shows an example in which nine rectangular lithium ion batteries 1300 are used as one battery pack 1415. Nine rectangular lithium ion batteries 1300 are connected in series, one electrode is fixed by a fixing part 1413 made of an insulator, and the other electrode is fixed by a fixing part 1414 made of an insulator. In this embodiment, an example in which the batteries are fixed by the fixing parts 1413 and 1414 is shown, but the batteries may be stored in a battery storage box (also called a housing). Since it is assumed that the vehicle is subjected to vibration or shaking from the outside (such as a road surface), it is preferable to fix a plurality of lithium ion batteries by the fixing parts 1413 and 1414 and the battery storage box. One electrode is electrically connected to the control circuit part 1320 by a wiring 1421. The other electrode is electrically connected to the control circuit part 1320 by a wiring 1422.

[0507] A memory circuit including a transistor using an oxide semiconductor may be used for the control circuit unit 1320. A charge control circuit or a battery control system having a memory circuit including a transistor using an oxide semiconductor may be referred to as a Battery operating system (BTOS) or a Battery oxide semiconductor.

[0508] It is preferable to use a metal oxide that functions as an oxide semiconductor. For example, a metal oxide such as In-M-Zn oxide (wherein element M is one or more selected from aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten, and magnesium) may be used as the oxide. In particular, the In-M-Zn oxide that can be used as the oxide is preferably CAAC-OS (C-Axis Aligned Crystal Oxide Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). In-Ga oxide or In-Zn oxide may be used as the oxide. CAAC-OS is an oxide semiconductor that has a plurality of crystal regions, and the plurality of crystal regions have c-axes oriented in a specific direction. The specific direction is the thickness direction of the CAAC-OS film, the normal direction of the surface on which the CAAC-OS film is formed, or the normal direction of the surface of the CAAC-OS film. The crystalline region is a region in which the atomic arrangement has periodicity. If the atomic arrangement is regarded as a lattice arrangement, the crystalline region is also a region in which the lattice arrangement is uniform. Furthermore, the CAAC-OS has a region in which a plurality of crystalline regions are connected in the ab-plane direction, and the region may have distortion. Note that the distortion refers to a portion in which the direction of the lattice arrangement changes between a region in which the lattice arrangement is uniform and another region in which the lattice arrangement is uniform in a region in which a plurality of crystalline regions are connected. In other words, the CAAC-OS is an oxide semiconductor that is c-axis oriented and does not have a clear orientation in the ab-plane direction.

[0509] In addition, since it can be used in a low-temperature environment, it is preferable that the control circuit unit 1320 uses a transistor using an oxide semiconductor. In order to simplify the process, the control circuit unit 1320 may be formed using a unipolar transistor. The operating ambient temperature of a transistor using an oxide semiconductor in the semiconductor layer is wider than that of single-crystal Si, from -40°C to 150°C, and the characteristic change is smaller than that of a single crystal even when the lithium-ion battery is heated. The off-current of a transistor using an oxide semiconductor is below the lower measurement limit regardless of temperature even at 150°C, but the off-current characteristic of a single-crystal Si transistor is highly temperature-dependent. For example, at 150°C, the off-current of a single-crystal Si transistor increases, and the current on / off ratio does not become sufficiently large. The control circuit unit 1320 can improve safety.

[0510] The control circuit unit 1320 using a memory circuit including a transistor using an oxide semiconductor can function as an automatic control device for a lithium-ion battery against 10 causes of instability such as micro-short circuit. The functions for eliminating the 10 causes of instability include overcharging prevention, overcurrent prevention, overheating control during charging, cell balancing in a battery pack, over-discharging prevention, a remaining capacity meter, automatic control of charging voltage and current amount according to temperature, control of charging current amount according to deterioration degree, detection of abnormal behavior of micro-short circuit, and prediction of abnormality related to micro-short circuit, and the control circuit unit 1320 has at least one of these functions. In addition, the automatic control device for a lithium-ion battery can be made ultra-compact.

[0511] Micro-short circuits are tiny short circuits inside lithium-ion batteries. One of the causes of micro-short circuits is said to be localized current concentration in parts of the positive electrode and negative electrode due to uneven distribution of the positive electrode active material caused by multiple charge and discharge cycles, or the generation of by-products due to side reactions, resulting in micro-short circuits.

[0512] In addition to detecting micro-short circuits, the control circuit unit 1320 can also be said to detect the terminal voltage of the lithium-ion battery and manage the charge / discharge state of the lithium-ion battery. For example, to prevent overcharging, it can turn off both the output transistor and the cutoff switch of the charging circuit almost simultaneously.

[0513] FIG. 27C shows an example of a block diagram of the battery pack 1415 shown in FIG. 27B.

[0514] The control circuit unit 1320 has at least a switch unit 1324 including a switch for preventing overcharging and a switch for preventing overdischarging, a control circuit 1322 for controlling the switch unit 1324, and a voltage measurement unit for the first battery 1301a. The control circuit unit 1320 has an upper limit voltage and a lower limit voltage for the lithium ion battery used, and limits the upper limit of the current from the outside and the upper limit of the output current to the outside. The range between the lower limit voltage and the upper limit voltage of the lithium ion battery is within the voltage range recommended for use, and when it is outside that range, the switch unit 1324 operates and functions as a protection circuit. In addition, the control circuit unit 1320 can also be called a protection circuit because it controls the switch unit 1324 to prevent overcharging and overdischarging. For example, when the control circuit 1322 detects a voltage that is likely to cause overcharging, the switch unit 1324 is turned off to cut off the current. Furthermore, a PTC element may be provided in the charge / discharge path to provide a function of cutting off the current in response to an increase in temperature. In addition, the control circuit section 1320 has an external terminal 1325 (+IN) and an external terminal 1326 (-IN).

[0515] The switch unit 1324 can be configured by combining n-channel transistors and p-channel transistors. The switch unit 1324 is not limited to a switch having a Si transistor using single crystal silicon, and may be, for example, Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenide), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaOx The switch unit 1324 may be formed of a power transistor having an OS transistor (gallium oxide; x is a real number greater than 0). Memory elements using OS transistors can be freely arranged by stacking them on a circuit using Si transistors, and therefore integration can be easily achieved. A control circuit unit 1320 using an OS transistor can be stacked on the switch unit 1324 and integrated into a single chip, enabling miniaturization.

[0516] The first batteries 1301a and 1301b mainly supply power to 42V (high voltage) in-vehicle devices, and the second battery 1311 supplies power to 14V (low voltage) in-vehicle devices. Lead-acid batteries are often used as the second battery 1311 because they are cost-effective. The second battery 1311 is a lithium-ion battery, which has the advantage of being maintenance-free. However, after a long period of use, for example, three years or more, there is a risk of abnormalities occurring that cannot be detected at the time of manufacture. In particular, if the second battery 1311 that starts the inverter becomes inoperable, even if the first batteries 1301a and 1301b have remaining capacity, in order to prevent the motor from being unable to start, if the second battery 1311 is a lead-acid battery, power is supplied from the first battery to the second battery, and the battery is charged to always maintain a fully charged state.

[0517] In this embodiment, an example in which lithium ion batteries are used for both the first battery 1301a and the second battery 1311 is shown, but a lead storage battery, an all-solid-state battery, or an electric double layer capacitor may be used for the second battery 1311. By using the positive electrode active material of the present invention for the above-mentioned lithium ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0518] Moreover, regenerative energy due to the rotation of the tire 1316 is sent to the motor 1304 via the gear 1305, and is charged into the second battery 1311 from the motor controller 1303 and the battery controller 1302 via the control circuit unit 1321. Alternatively, the first battery 1301a is charged from the battery controller 1302 via the control circuit unit 1320. Alternatively, the first battery 1301b is charged from the battery controller 1302 via the control circuit unit 1320. In order to efficiently charge the regenerative energy, it is desirable that the first batteries 1301a and 1301b are capable of being quickly charged.

[0519] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b. The battery controller 1302 can set charging conditions in accordance with the charging characteristics of the lithium ion battery used, and can perform rapid charging.

[0520] Although not shown, when connecting to an external charger, the charger outlet or the connection cable of the charger is electrically connected to the battery controller 1302. The power supplied from the external charger is charged to the first batteries 1301a and 1301b via the battery controller 1302. Some chargers are provided with a control circuit and may not use the function of the battery controller 1302, but it is preferable to charge the first batteries 1301a and 1301b via the control circuit unit 1320 to prevent overcharging. In some cases, the connection cable or the connection cable of the charger is provided with a control circuit. The control circuit unit 1320 is also called an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) provided in the electric vehicle. The CAN is one of the serial communication standards used as an in-vehicle LAN. The ECU includes a microcomputer. The ECU uses a CPU or a GPU.

[0521] External chargers installed at charging stations and the like come in a variety of types, including 100V outlets, 200V outlets, and three-phase 200V and 50kW outlets. In addition, charging can also be achieved by receiving power from external charging equipment using a contactless power supply system or the like.

[0522] Next, an example in which the lithium-ion battery according to one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.

[0523] Furthermore, by installing lithium-ion batteries in vehicles, next-generation clean energy automobiles such as hybrid vehicles (HVs), electric vehicles (EVs), plug-in hybrid vehicles (PHVs), etc. Lithium-ion batteries can also be installed in transportation vehicles such as agricultural machinery, motorized bicycles including electrically assisted bicycles, motorcycles, electric wheelchairs, electric carts, small or large ships, submarines, aircraft such as fixed-wing aircraft and rotary-wing aircraft, rockets, artificial satellites, space probes, planetary probes, and spacecraft.

[0524] 28(A) to 28(D) show examples of transportation vehicles using one embodiment of the present invention. An automobile 2001 shown in FIG. 28(A) is an electric automobile that uses an electric motor as a power source for running. Or, it is a hybrid automobile that can appropriately select and use an electric motor and an engine as a power source for running. When a lithium-ion battery is mounted on a vehicle, an example of the lithium-ion battery described in the above embodiment is installed in one or more locations. By using the positive electrode active material of the present invention for a lithium-ion battery mounted on a vehicle, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0525] 28A includes a battery pack 2200, which includes a battery module to which a plurality of lithium ion batteries are connected. The battery pack 2200 preferably further includes a charge control device electrically connected to the battery module.

[0526] Moreover, the automobile 2001 can charge the lithium ion battery of the automobile 2001 by receiving power supply from an external charging facility by a plug-in method, a contactless power supply method, or the like. When charging, the charging method and connector standard may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or Combo. The lithium ion battery may be a charging station provided in a commercial facility, or may be a home power source. For example, a power storage device mounted on the automobile 2001 can be charged by an external power supply by plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.

[0527] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in a road or an exterior wall, charging may be performed not only while the vehicle is stopped but also while it is moving. This contactless power supply method may also be used to transmit and receive power between two vehicles. Furthermore, solar cells may be provided on the exterior of the vehicle, and the lithium ion battery may be charged while the vehicle is stopped and while it is moving. An electromagnetic induction method or a magnetic field resonance method may be used for such contactless power supply.

[0528] Fig. 28(B) shows a large transport vehicle 2002 having an electrically controlled motor as an example of a transport vehicle. The battery module of the transport vehicle 2002 is, for example, a four-cell unit of lithium ion batteries with a nominal voltage of 3.0 V to 5.0 V, with 48 cells connected in series to achieve a maximum voltage of 170 V. Apart from the number of lithium ion batteries in the battery pack 2201, the battery pack 2201 has the same functions as those in Fig. 27(B), and therefore a description thereof will be omitted. By using the positive electrode active material of the present invention for the lithium ion batteries in the battery pack 2201, a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics can be obtained.

[0529] Fig. 28(C) shows, as an example, a large transport vehicle 2003 having an electrically controlled motor. The battery module of the transport vehicle 2003 has, for example, a maximum voltage of 600 V, in which 100 or more lithium ion batteries with a nominal voltage of 3.0 V to 5.0 V are connected in series. Also, except for the number of lithium ion batteries constituting the battery module of the battery pack 2202, the battery module has the same functions as that of Fig. 27(B), and therefore a description thereof will be omitted. By using the positive electrode active material of the present invention for the lithium ion batteries of the module, a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics can be obtained.

[0530] Fig. 28(D) shows, as an example, an aircraft 2004 having an engine that burns fuel. The aircraft 2004 shown in Fig. 28(D) has wheels for takeoff and landing, and therefore can be said to be a part of a transportation vehicle, and has a battery pack 2203 including a battery module formed by connecting multiple lithium ion batteries and including a battery module and a charge control device.

[0531] The battery module of the aircraft 2004 is, for example, eight 4 V lithium ion batteries connected in series to produce a maximum voltage of 32 V. Other than the number of lithium ion batteries constituting the battery module of the battery pack 2203, it has the same functions as those in Fig. 27(B), and therefore a description thereof will be omitted.

[0532] The content of this embodiment mode can be appropriately combined with the content of the other embodiment modes.

[0533] (Embodiment 7) In this embodiment, an example will be described in which a lithium-ion battery according to one embodiment of the present invention is mounted on a vehicle such as a motorcycle or a bicycle.

[0534] 29A is an example of an electric bicycle using the lithium-ion battery of one embodiment of the present invention. The lithium-ion battery of one embodiment of the present invention can be applied to an electric bicycle 8700 shown in FIG. 29A. The lithium-ion battery of one embodiment of the present invention may have a protection circuit.

[0535] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 can supply electricity to a motor that assists a rider. The power storage device 8702 is portable and is shown in a state removed from the bicycle in FIG. 29B. The power storage device 8702 includes a plurality of lithium-ion batteries 8701 of one embodiment of the present invention, and the remaining battery charge and the like can be displayed on a display unit 8703. By using the positive electrode active material of the present invention for the lithium-ion battery 8701, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0536] The power storage device 8702 also includes a control circuit 8704 capable of controlling charging or detecting an abnormality of the lithium ion battery, an example of which is shown in Embodiment 8. The control circuit 8704 is electrically connected to the positive and negative electrodes of the lithium ion battery 8701. This can greatly contribute to preventing accidents such as fires caused by lithium ion batteries.

[0537] 29C is an example of a two-wheeled vehicle using a lithium-ion battery of one embodiment of the present invention. A scooter 8600 shown in FIG. 29C includes a power storage device 8602, a side mirror 8601, and a turn signal light 8603. The power storage device 8602 can supply electricity to the turn signal light 8603. By using the positive electrode active material of the present invention for the lithium-ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0538] 29C, a power storage device 8602 can be stored in an under-seat storage compartment 8604. The power storage device 8602 can be stored in the under-seat storage compartment 8604 even if the under-seat storage compartment 8604 is small in size.

[0539] The content of this embodiment mode can be appropriately combined with the content of other embodiment modes.

[0540] (Embodiment 8) In this embodiment, an example of mounting a lithium ion battery according to one embodiment of the present invention in an electronic device will be described. Examples of electronic devices mounting a lithium ion battery include television devices (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, portable information terminals, audio playback devices, and large game machines such as pachinko machines. Examples of portable information terminals include notebook personal computers, tablet terminals, e-book terminals, and mobile phones.

[0541] 30(A) shows an example of a mobile phone. The mobile phone 2100 includes a display unit 2102 built into a housing 2101, an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like. The mobile phone 2100 includes a lithium ion battery 2107. By using the positive electrode active material of the present invention for the lithium ion battery, a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics can be obtained.

[0542] The mobile phone 2100 is capable of executing a variety of applications, such as mobile phone calls, e-mail, document browsing and creation, music playback, Internet communications, and computer games.

[0543] The operation button 2103 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 2103 can be freely set by an operating system built into the mobile phone 2100.

[0544] The mobile phone 2100 is also capable of performing short-range wireless communication according to a communication standard. For example, the mobile phone 2100 can communicate with a wireless headset to enable hands-free calling.

[0545] The mobile phone 2100 also includes an external connection port 2104, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the external connection port 2104. Note that charging may be performed by wireless power supply without using the external connection port 2104.

[0546] It is preferable that the mobile phone 2100 has a sensor. For example, it is preferable that a fingerprint sensor, a pulse sensor, a human body sensor such as a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like is mounted as the sensor.

[0547] FIG. 30B shows an unmanned aerial vehicle 2300 having a plurality of rotors 2302. The unmanned aerial vehicle 2300 is sometimes called a drone. The unmanned aerial vehicle 2300 includes a lithium-ion battery 2301 which is one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely controlled via the antenna. By using the positive electrode active material of the present invention for the lithium-ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0548] Fig. 30C shows an example of a robot. The robot 6400 shown in Fig. 30C includes a lithium ion battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0549] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.

[0550] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.

[0551] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.

[0552] The robot 6400 includes a lithium ion battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component in an internal region thereof. By using the positive electrode active material of the present invention for the lithium ion battery, the secondary battery can have a high capacity, a high discharge capacity, and excellent cycle characteristics.

[0553] 30D shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a lithium ion battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port arranged on the bottom surface.

[0554] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may become entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a lithium ion battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component in an internal region thereof. By using the positive electrode active material of the present invention for the lithium ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0555] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0556] (Embodiment 9) In this embodiment, an example in which a lithium-ion battery according to one embodiment of the present invention is mounted on space equipment will be described.

[0557] 31A shows an artificial satellite 6800 as an example of space equipment. The artificial satellite 6800 has a body 6801, a solar panel 6802, an antenna 6803, and a lithium ion battery 6805. The solar panel may be called a solar cell module.

[0558] When the solar panel 6802 is irradiated with sunlight, the power required for the operation of the artificial satellite 6800 is generated. However, for example, in a situation where the solar panel is not irradiated with sunlight or the amount of sunlight irradiated to the solar panel is small, the generated power is small. Therefore, there is a possibility that the power required for the operation of the artificial satellite 6800 is not generated. In order to operate the artificial satellite 6800 even under a situation where the generated power is small, it is preferable to provide a lithium ion battery 6805 in the artificial satellite 6800. By using the positive electrode active material of the present invention in the lithium ion battery, it is possible to obtain a secondary battery having a high capacity, a high discharge capacity, and excellent cycle characteristics.

[0559] The satellite 6800 can generate a signal. The signal is transmitted via an antenna 6803, and can be received by, for example, a receiver installed on the ground or another satellite. By receiving the signal transmitted by the satellite 6800, for example, the position of the receiver that received the signal can be measured. Thus, the satellite 6800 can constitute, for example, a satellite positioning system.

[0560] Alternatively, the artificial satellite 6800 can be configured to have a sensor. For example, by configuring the artificial satellite 6800 to have a visible light sensor, the artificial satellite 6800 can have a function of detecting sunlight reflected by an object on the ground. Alternatively, by configuring the artificial satellite 6800 to have a thermal infrared sensor, the artificial satellite 6800 can have a function of detecting thermal infrared rays emitted from the earth's surface. From the above, the artificial satellite 6800 can have a function as, for example, an earth observation satellite.

[0561] FIG. 31(B) shows a probe 6900 having a solar sail (also called a sun sail) as an example of space equipment. The probe 6900 has a body 6901, a solar sail 6902, and a lithium ion battery 6905. By using the positive electrode active material of the present invention for the lithium ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained. When photons emitted from the sun hit the surface of the solar sail 6902, momentum is transferred to the solar sail 6902. Therefore, the surface of the solar sail 6902 preferably has a thin film with high reflectivity, and further preferably faces the sun.

[0562] The solar sail 6902 may also be designed to be folded up small until it leaves the atmosphere, and then deployed into a large sheet outside the Earth's atmosphere (in outer space) as shown in Figure 31(B).

[0563] FIG. 31(C) shows a spacecraft 6910 as an example of space equipment. The spacecraft 6910 has a body 6911, a solar panel 6912, and a lithium ion battery 6913. By using the positive electrode active material of the present invention for the lithium ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained. The body 6911 can have, for example, a pressurized compartment and a non-pressurized compartment. The pressurized compartment may be designed to accommodate a crew member. Electric power generated by irradiating the solar panel 6912 with sunlight can be charged into the lithium ion battery 6913.

[0564] 31(D) shows a rover 6920 as an example of space equipment. The rover 6920 includes a body 6921 and a lithium ion battery 6923. By using the positive electrode active material of the present invention for the lithium ion battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained. The rover 6920 may include a solar panel 6922.

[0565] The rover 6920 may be designed to accommodate a crew member. The lithium ion battery 6923 may be charged with electricity generated by irradiating the solar panel 6912 with sunlight, or may be charged with electricity generated by other power sources, such as a fuel cell, a radioisotope thermoelectric converter, or the like.

[0566] The content of this embodiment mode can be appropriately combined with the content of other embodiment modes. [Explanation of symbols]

[0567] 51 Cathode active material 52 Recess 54 Pit 55 Crystal Faces 57 Crack 58 Pit 100a Surface layer 100b internal 100 Cathode active material 101 Grain Boundary 102 Embedded part 104 Covering part 110 Manufacturing equipment 111 Furnace tube 112 Heating means 115 Rotational drive unit 116a Gas supply means 116b Gas exhaust means 118 Stages 119 Vibration means 120a Container 120b lid 219 Space 220 Heating Furnace 300 Lithium-ion battery 301 Positive electrode can 302 Anode can 303 Gasket 304 Positive electrode 305 Positive electrode current collector 306 Positive electrode active material layer 307 Negative electrode 308 Negative electrode current collector 309 Negative electrode active material layer 332 Washer 342 Spacer 500 Lithium-ion battery 506 negative electrode 507 Positive electrode 508 Adhesive area 509 Exterior body 510 Negative lead electrode 511 Positive lead electrode 550 Current collector 553 Carbon Black 554 Graphene 555 Carbon Fiber 561 Cathode active material 562 Second active material 601 Positive electrode cap 602 Battery Can 603 Positive terminal 604 Positive electrode 605 Electrolyte layer 606 negative electrode 607 Negative terminal 608 Insulating plate 609 Insulating plate 611 PTC element 613 Safety valve mechanism 614 Conductive plate 615 Energy Storage System 616 Lithium-ion battery 620 Control circuit 621 Wiring 622 Wiring 623 Wiring 624 Conductors 625 Insulators 626 Wiring 627 Wiring 628 Conductive plate 903 Lithium cobalt oxide 911a Terminal 911b Terminal 913 Lithium-ion battery 930a Case 930b Case 930 Case 931a Negative electrode active material layer 931 negative electrode 932a Cathode active material layer 932 Positive electrode 933 Electrolyte layer 950a Wound body 950 Wound body 951 Terminal 952 Terminal 1300 Square Lithium-ion Battery 1301a First Battery 1301b 1st Battery 1302 Battery Controller 1303 Motor Controller 1304 Motor 1305 Gear 1306 DC-DC circuit 1307 Electric power steering 1308 Heater 1309 Defogger 1310 DC-DC circuit 1311 Second Battery 1312 Inverter 1313 Audio 1314 Power window 1315 Lamps 1316 Tires 1317 Rear motor 1320 Control circuit section 1321 Control circuit section 1322 Control circuit 1324 Switch section 1413 Fixed part 1414 Fixed part 1415 Battery Pack 1421 Wiring 1422 Wiring 2001 Automobiles 2002 Transport vehicle 2003 Transport Vehicles 2004 aircraft 2100 Mobile phone 2101 Case 2102 Display section 2103 Operation button 2104 External connection port 2105 Speaker 2106 Mike 2107 Lithium-ion battery 2200 Battery Pack 2201 Battery Pack 2202 Battery Pack 2203 Battery Pack 2300 Unmanned Aircraft 2301 Lithium-ion battery 2302 Rotor 2303 Camera 6300 Cleaning robot 6301 Case 6302 Display section 6303 Camera 6304 Brush 6305 Operation button 6306 Lithium-ion battery 6310 Garbage 6400 Robot 6401 Light Sensor 6402 Microphone 6403 Upper Camera 6404 Speaker 6405 Display section 6406 Lower Camera 6407 Obstacle Sensor 6408 Moving mechanism 6409 Lithium-ion battery 6800 satellite 6801 Aircraft 6802 Solar Panel 6803 Antenna 6805 Lithium-ion Battery 6900 Probe 6901 Aircraft 6902 Solar Sail 6905 Lithium-ion battery 6910 Spaceship 6911 Aircraft 6912 Solar Panel 6913 Lithium-ion battery 6920 Rover 6921 Aircraft 6922 Solar Panel 6923 Lithium-ion battery 8600 Scooter 8601 Side mirror 8602 Energy storage devices 8603 Turn signal light 8604 Under-seat storage 8700 Electric Bike 8701 Lithium-ion battery 8702 Energy storage devices 8703 Display section 8704 Control circuit

Claims

1. forming a region or film containing a high concentration of an additive element on the inner surface of a container made of a heat-resistant material; A plurality of active material particles are placed in the container; placing a lid made of a heat-resistant material on the container; The container is heated to add the additive element to the surface layer portion of the active material particles; recovering the positive electrode active material from the container after the heat treatment; A method for producing a secondary battery using the positive electrode active material as a positive electrode.

2. 2. The method for producing a secondary battery according to claim 1, wherein a closed space is formed in the container, and the heat treatment causes the closed space to be filled with a gas containing an additive element, making the gas have a higher concentration than the space outside the container.

3. 2. The method for producing a secondary battery according to claim 1, wherein the container is rotated to agitate the active material particles when the container is heat-treated.

4. 2. The method for producing a secondary battery according to claim 1, wherein the additive element is one or more selected from the group consisting of magnesium, fluorine, aluminum, titanium, and nickel.

5. 2. The method for producing a secondary battery according to claim 1, wherein the active material particles are a lithium composite oxide.

6. 2. The method for producing a secondary battery according to claim 1, wherein the lid and the container are made of the same material.

7. 2. The method for producing a secondary battery according to claim 1, wherein the container is heated in an oxygen atmosphere.

Citation Information

Patent Citations

  • Method for producing positive electrode active substance

    WO2020201891A1

  • Method for producing positive electrode active material

    WO2020201892A1

  • Method for producing positive electrode active material, kiln, and heating furnace

    WO2021116819A1